UFMylation in lipid metabolism disorders-associated diseases - Zi-Ping Ning; Ya-Ling Tang; Lin Cao; Hong-Feng Gu (Molecular Biology Reports, 2026)

Epigallocatechin-3-gallate enhances in vitro maturation and developmental competence of sheep oocytes - Ruigang Wang; Zhenliang Zhang; Jesse Oluwaseun Ayantoye; Wen Wu; Jingjing Wang; Yucheng Liu; Zhanmin Lv; Lei Gao; Jianhong Ni; Changbin Liu; Ling Tang; Yuxuan Hua; et al. (Theriogenology, 2026)

Foggy-UAVCD and DSRF-Net: Benchmarking robust satellite–UAV change detection under fog degradation - Xiu-Wen Huang; Qing-Ling Shu; Kai-Xuan Jiang; Wei Lu; Si-Bao Chen; Jin Tang; Bin Luo (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Extension-layer fine-tuning for transfer learning in multi-agent reinforcement learning-based HVAC control - Xudong Tang; Xiaosong Su; Yongqiang Luo; Ling Zhang (Energy and Buildings, 2026)

Machine learning-guided discovery of poly(ethylene terephthalate)-binding modules to enhance durable whole-cell degradation - Rui Long; Yaxin Tang; Chengyong Wang; Tangli Yang; Wei Liu; Ling Jiang (Bioresource Technology, 2026)

Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Baicalein suppresses mitochondrial biogenesis via the RBM43/PGC-1α axis in triple-negative breast cancer cells - Yu Zhu; Ling Tang; Yun Dong; Meitong Pan; Cheng Tian; Xiaolan Yu; Jiyi Xia (Tissue and Cell, 2026)

Corrigendum to “Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development” [Theriogenology 2026; 118017] - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Photoinduced/proton-assisted cyclopropanation of 3-diazooxindoles and vinylpyridine derivatives: A concise access to cis HIV-1 non-nucleoside reverse transcriptase inhibitor - Fei Tan; Hongwei Tang; Jian Yang; Peiting Wen; Tao Song; Wei Wang; Xiao Huang; Ling Mei; Jian Wang; Hongbo Dong (Sustainable Chemistry and Pharmacy, 2026)

Contact dynamics characteristics of a deepwater drilling riser-drillstring coupled system - Yangyang Wang; Min Lou; Yaokang Luo; Zhihao Wan; Ling Wang; Qian Tang (Ocean Engineering, 2026)

Artificial intelligence-based response surface stochastic dynamic programming for long-term operation rule derivation of cascade hydropower reservoirs - Zhong-kai Feng; Xuan Chao; Yang Xiao; Hong-wu Tang; Wen-jing Niu; Tao-tao Zhang; Ling-zhong Kong (Journal of Hydrology, 2026)

Establishment of a novel brain cell line from grass carp (Ctenopharyngodon idella) with high transfection efficiency and CRISPR/Cas9-mediated genome editing capacity - Zi-Ling Qu; Tao Liu; Tang-Kai-Yuan Qin; Hua-Mei Yue; Ling Huang; Rui Ruan; Chang-Song Wu; Huan Ye; Chuang-Ju Li (Fish & Shellfish Immunology, 2026)

Gecko tail regeneration-inspired composite hydrogel scaffolds with “socket-plug” architecture for dynamically programmed repair of infected bone defects - Minglang Zou; Yi Tang; Yongming Wang; Ling Mo; Menghuan Wang; Qing He; Zhenjin Xu; Liu Su; Pengfei Wang; Fang Luo; Da Huang; Jiewei Luo; et al. (Chemical Engineering Journal, 2026)

Advanced nitrogen removal system coupling partial nitritation, anammox, denitrification and oxygen-permeable hollow-fibre membranes for precise oxygen regulation - Xifang Tang; Bao-Shan Xing; Yong-Ning Feng; Liguo Wan; Ling-Hu Li; Xin-Xin Sun; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Microalgae bioenergy with carbon capture, utilization and storage: A sustainable technology to net-negative emissions and circular economy - Chao-Wen Wang; Kai Ling Yu; Hwai Chyuan Ong; Brandon Han Hoe Goh; Cheng-Tang Pan (Biomass and Bioenergy, 2026)

Curcumin maintains pseudorabies virus latent infection by inhibiting the phosphorylation level of EGFR protein - Yuhang Li; Fan Yang; Dingqiu Zou; Pei Liu; Kexin Qi; Jingyi Wang; Chenlu Sun; Yanru Tang; Ruihan Zhang; Junyan Ren; Zijie Cui; Ruoxian Li; et al. (Veterinary Microbiology, 2026)

Lateral dynamic response of a vertical pile under ice impact: linking ice fragmentation, pile-soil interaction and displacement demand - Wenqiang Xing; Ke Wang; Shengyi Cong; Shanzhen Li; Liang Tang; Xianzhang Ling (Ocean Engineering, 2026)

Cyclic biomineralization by incorporating iron-oxidizing and sulfate-reducing microorganisms for sustainable iron removal and sulfur recovery from acid mine drainage: Efficiency and mechanism - Xingjie Wang; Ling Liu; Yuxuan Yang; Jiaming Du; Liyuan Ma; Jie Tang; Peng Liu; Jianwei Zhou (Minerals Engineering, 2026)

The carbon reduction effects of industrial land transition: Intelligently constructed dataset of 16,067 parcels reveals multi-dimensional interactions and nonlinear mechanisms - Weilong Kong; Yuxin Pan; Huixin Zhou; Geoffrey Qiping Shen; Dong Zhang; Ling Tang; Zhi Zhang; Zhengfeng Zhang; Qiyu Hu (Land Use Policy, 2026)

Integrative transcriptomic and functional analysis reveals fatty acyl elongases involved in sex pheromone biosynthesis in rice leaffolder, Cnaphalocrocis medinalis (Lepidoptera: Pyraloidea) - Ling-Yue Chen; Xiao-Yang Lin; Ke-Xin Wang; Xiao Feng; Hong-Ting Tang; Shuang-Lin Dong; Ling-Ling Zheng; Yi-Han Xia (Insect Biochemistry and Molecular Biology, 2026)

Effects of light-shielding treatment on the quality and flavor of ‘Ziyan’ tea wine during storage: Insights from color, taste, and aroma - Ling Lin; Yinan Wu; Jingwen Yang; Ziyan Zhu; Xue Xia; Yixuan Gao; Yao Zou; Qian Tang; Liqiang Tan; Zhonghua Liu; Wei Xu (Food Chemistry, 2026)

Insights into distinct biocarbon assembly and graphitization derived from large-scale bioresource by integrating machine learning with Raman and XRD spectroscopic profiling - Junsheng Yu; Jing Hong; Yujia Fang; Jiacheng Kang; Zongtai Tang; Lei Zhu; Bing Gao; Ling Luo; Dan Sun; Yanting Wang; Liangcai Peng; Hua Yu (Bioresource Technology, 2026)

Integrated multi-matrix bile acid metabolic metrics (BAMMs): A methodological framework for functional metabolic phenotyping in human subjects - Cheng-Hung Yang; Hsiang-Yu Tang; Chun-Ming Fan; Jui-Fen Lin; Mei-Ling Cheng (Analytica Chimica Acta, 2026)

Cu-MOF-confined Co nanoparticle nanozymes with synergistic peroxidase-like activity for highly selective colorimetric detection of hydroquinone - Tanzeel Riaz Ahmad; Xin Li; Ling Jiang; Jie Jin; Xiupei Yang; Fenglin Tang (Analytica Chimica Acta, 2026)

Diffusion-attenuation characteristics of grout in water-bearing soft strata: a pressure-attenuation correction model accounting for hole depth effect - Ling Zeng; Yong-Chao Wang; Jing-Cheng Chen; Jie Liu; Li Yi; Jing Tang; Gui-Jin Zhang; Ming Fan; Cai-Ying Chen (Bulletin of Engineering Geology and the Environment, 2026)

Chromosome‐Level Genome Assembly of Otocolobus manul Provides Insights Into High‐Altitude Adaptation and Evolutionary Traits - Shuo Feng; Xin Tang; Qiang Gao; Xin‐Zhang Qi; De‐Ling Qi (Zoologica Scripta, 2026)
The Otocolobus manul , a small felid endemic to the high‐altitude Qinghai‐Tibet Plateau, lacks a high‐quality chromosome‐level genome, hindering study of its evolutionary adaptations. This study aimed to construct such a genome and investigate its genetic basis for high‐altitude adaptation. We generated a de novo chromosome‐scale assembly using an integrated approach of PacBio HiFi long‐reads, Illumina short‐reads, and Hi‐C scaffolding. The resulting 2.55 Gb genome was anchored to 19 chromosomes (contig N50 = 96.32 Mb) and contained 22,699 protein‐coding genes. Comparative genomic analysis across felids revealed 13 expanded gene families in O. manul , functionally enriched in processes like glycolysis/gluconeogenesis and the HIF‐1 signalling pathway. Phylogenetic analysis placed O. manul as sister to Prionailurus , with an estimated divergence time of 6.10–7.04 million years ago, and identified positive selection signals linked to adaptation. Furthermore, we found that the nuclear genome supports a sister relationship between O. manul and Prionailurus (they are closely related species), while the mitochondrial genome suggests a closer relationship with Felis . This significant mito‐nuclear phylogenetic discordance is primarily attributed to incomplete lineage sorting (ILS). This de novo chromosome‐level genome assembly of O. manul provides a crucial resource for evolutionary and conservation studies. The findings specifically highlight significant genetic enrichments in hypoxia‐responsive pathways, suggesting its molecular adaptation to the extreme plateau environment.

Correction: Salvia miltiorrhiza (Danshen) and its extracts in the alternative treatment of diabetic nephropathy: mechanisms and clinical perspectives - Lu Song; Yan Li; Huakui Zhan; Ling Wu; Li Tang; Xinyu Wang; Qinyuan Deng (Journal of Natural Medicines, 2026)

Macro and mesoscopic mechanical responses analysis of EPB shield under bias-load effects in soil-rock composite strata using FDM-DEM coupled method - Changrui Yao; Xiangxun Kong; Liang Tang; Xianzhang Ling; Wenchong Tang (Transportation Geotechnics, 2026)

Thermodynamic-kinetic integrated analysis of heat exchanger scaling and control techniques: A case study from a potash processing plant in northwest China - Qian Zheng; Hengtao Deng; Zhen Wang; Huanhuan Song; Ling Xia; Gao Tang; Shaojie Huang; Zhuolin Xie; Yingying He; Hang Li; Nasriddinov Zamoniddin; Hojiev Saidmukbil; et al. (Journal of Cleaner Production, 2026)

Nitrogen levels and milling degree jointly regulate starch digestibility and rice taste quality in high-quality rice - Lin Ling; Beiyun Tang; Yintao Liu; Siyu Liu; Shijie Shi; Cougui Cao; Yang Jiang (Journal of Cereal Science, 2026)

Characterization and mechanism probe of enzymatic extraction and thiolation modification of wheat bran arabinoxylan - Chengming Jin; Ling Zhu; Jia Tang; Yayu Xiao; Junlian Wan; Hui Zhang (Food Research International, 2026)

Nanoconfinement of phase separation toward high-performance and reversible all-solid-state CuS batteries - Xianwei Wang; Jiawu Cui; Kang Yang; Qi Ling; Zhen Wang; Liang Xie; Chao Wu; Chengwei Wu; Yuping Wu; Chengyong Shu; Shenghua Chen; Wei Tang (Chemical Engineering Journal, 2026)

Corrigendum to “Highly structured solvents enable integrated organogel networks with robust adhesion and mechanics” [Chemical Engineering Journal Volume 538, 15 June 2026, 176931] - Dongyong Sha; Yang Zhao; Ding Ding; Shuaimin Tang; Jianxing Zhang; Xiaofeng Ling; Changsheng Liu; Liang Gao; Yuan Yuan (Chemical Engineering Journal, 2026)

An integrated design of multi-component two-dimensional catalysts for all-solid-state NaO2 batteries - Hanyu Yang; Xianjian Tang; Zihan Qiao; Chang Sun; Qi Sun; Lingxin Kong; Xiaoyan Zhang; Ling Wang; Shan Liu (Chemical Engineering Journal, 2026)

Pollution characteristics and gas-particle partitioning of PFAS and VMSs in urban China: Influence of aerosol chemical composition - Siquan Wang; Qing Yan; Weihao Li; Jiangfeng Ling; Ruicong Tang; Fuhai Zhang; Zhengxin Xie; Jun Tang (Atmospheric Pollution Research, 2026)

Correction: Mesenchymal Stem Cell-Derived Exosomes for Ovarian Reserve: A Systematic Review and Network Meta‑Analysis Based on Animal Studies - Mingyue Yu; Yiming Ma; Xiaohui Sun; Jingjing Zhao; Tianlin Sun; Ling Tang (Stem Cell Reviews and Reports, 2026)

An IDA peptide from Boea hygrometrica enhances desiccation tolerance but lacks activity in Arabidopsis - Ling Tang; Xiaohua Wang; Yuxi Wang; Xiuxiu Chen; Yuanyuan Wang; Xuanyang Wu; Runze Sun; Xin Deng (Planta, 2026)

Revealing phenological vulnerabilities in wheat yield formation under climate warming: a process-based framework for adaptive breeding - Ming Li; Shizhao Li; Xiaoli Wu; Ling Wu; Miao Liu; Tao Xiong; Chaosu Li; Yonglu Tang (Agricultural and Forest Meteorology, 2026)

Treatment patterns and outcomes of second/third-line therapy in advanced non-small cell lung cancer with actionable genomic alterations (RECAP) - Hanxiao Chen; Xiangjiao Meng; Ling Cai; Wei Lei; Yu Tang; Xi Shi; Leilei Ma; Jun Zhao (Clinical & Experimental Metastasis, 2026)
Treatment choices for metastatic non-small-cell lung cancer (NSCLC) after first-line targeted therapy progression are heterogeneous. This study aimed to characterize real-world treatment patterns and outcomes of advanced NSCLC harboring actionable genomic alterations (AGAs) in second- (2 L) or third-line (3 L) settings. This retrospective cohort study across six Chinese centers included stage IV NSCLC patients with confirmed AGAs. Therapies were divided into six categories: targeted monotherapy (T), targeted combinations (T+), chemotherapy monotherapy (C), chemotherapy combinations (C+), anti-angiogenic monotherapy (A), and other regimens (O). The primary outcome was the treatment pattern. Secondary outcomes included biomarker testing and effectiveness. A total of 658 patients were enrolled, with the majority harboring EGFR mutations ( n = 590, 89.7%). In the 2 L-enrolled group ( n = 602), T use declined from 75.3% in the 1 L setting to 49.3% in 2 L, while utilization of A + C increased to 16.5%. Within the EGFR-mutant subgroup, therapeutic sequences were highly dependent on 1 L TKI generation and T790M resistance status. Over half (51.1%) of T790M-negative patients continued T in 2 L following progression on 1 L first- or second-generation TKIs. Among the 3 L-enrolled patients ( n = 56), A + C (35.7%) and C (14.3%) were predominant. The overall median real-world progression-free survival for the 2 L-enrolled group was 7.4 months in the 2 L setting (7.5 months for the EGFR-mutant subgroup) and 5.4 months in 3 L. This multicenter real‑world cohort predominantly comprised patients with EGFR‑mutant NSCLC, with smaller numbers of other AGA subtypes. Targeted therapies remain the cornerstone of later-line advanced NSCLC management. The prevalent real-world reliance on continued TKI therapy, even in T790M-negative patients, highlights the clinical dilemma of limited post-resistance options and the need to integrate emerging novel therapeutics.

High-performance quantum interconnect between bosonic modules beyond transmission loss constraints - Hongwei Huang; Jie Zhou; Weizhou Cai; Weiting Wang; Yilong Zhou; Yunlai Zhu; Ziyue Hua; Yifang Xu; Lida Sun; Juan Song; Tang Su; Ming Li; et al. (Science Bulletin, 2026)

Phosphate-buffered saline as pH regulators for citrus postharvest handling water, maintain fruit quality by enhancing the phenylpropanoid metabolic pathway - Yanfei Zhu; Huan Liu; Yunxi Xiao; Zhiqiang Xiong; Ling Shen; Jiajun Tang; Zhifeng Zhu; Linlin Zhong; Rangwei Xu; Quan Sun; Feng Zhu; Yunjiang Cheng (Postharvest Biology and Technology, 2026)

A high-accuracy and cost-effective optimization method for rudder propeller design - Daiyu Zhang; Jiacheng Tang; Hongjie Ling; Yongdong Shu; Peng Du; Qingshan Ji (Ocean Engineering, 2026)

Corrigendum to “Decomposition-based prediction of slamming forces on two-dimensional curved bodies using deep neural network” [Ocean. Eng. 357 (2026) 125689] - Xupeng Sui; Kamal Djidjeli; Zhe Sun; Jing Tang Xing; Jun Ding; Ling Liu (Ocean Engineering, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Histamine reduction and microbial safety enhancement in soy-based nuoc mam chay fermented with Bacillus subtilis - Yo-Chia Chen; Tang Thi Huynh Nhu; Wen-Hsin Hsu; Shu-Ling Hsieh; Hui-Yun Tsai; Chun-Yi Hu (Food Bioscience, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Bimetallic synergistic effect of chromium‑gallium nanoparticles on ZSM-5 framework for robust propane dehydrogenation - Kang Guo; Chengliang Tang; Ling Cen; Lei Liu; Hanzi Liu; Zhiqiang Sun (Chemical Engineering Journal, 2026)

Dynamic changes in PAH sequestration and bioremediation driven by humic acid and degrading bacteria - Lei Tang; Rongxin Lv; Hao Sun; Yong Wen; Chao Qin; Xuwen Chen; Wanting Ling (Applied Soil Ecology, 2026)

The Therapeutic Potential of Fractional CO2 Laser for Hyperpigmentation: Evidence From Network Meta-analysis, Clinical and Animal Studies - Haoran Guo; Hui Li; Ling Jiang; Chuhan Fu; Jianyun Lu; Zhen Tang; Jing Chen; Qinghai Zeng (Phenomics, 2026)

Water-quality responses and management-oriented spatial thresholds in a complex river-estuary continuum - Jiang Wu; Tang Liu; Dian-Bao Li; Li-Juan Zhang; Hua-Peng Qin; Wei-Ling Sun; Nan Xu (Water Research, 2026)

A coupled macro–micro prediction model for desiccation shrinkage deformation of freeze–thawed expansive soils incorporating the pore size-volume dual microstructure parameters - Shengyi Cong; Xinyu Li; Liang Tang; Xianzhang Ling; Ze Li; Sai K. Vanapalli (Transportation Geotechnics, 2026)

MiR-29a/DNMT3A axis participates in Dihydroartemisinin's suppression on lung adenocarcinoma: Implications for overcoming acquired resistance to EGFR-TKIs - Yayu Zhu; Ping Qiu; Jing Tang; Renjie Chen; Yaqing Liu; Huijuan Ling; Yu Liu; Liwen Chen (Toxicology and Applied Pharmacology, 2026)

Epimedium polysaccharide alleviates adenine-induced oligoasthenozoospermia in mice by inhibiting ferroptosis and inflammation through TLR4/NF-κB and SLC7A11/GPX4 axis - Kun-Yang Tang; Wang Ai; Xiao-Cui Jiang; Min Xiao; Yan-Yan Zhou; Xiao-Ming Yu; Shu-Hui Chen; Jing-Ling Zhao (Reproductive Biology, 2026)

A genome-wide study of the AP2/ERF gene family in mangrove Avicennia marina reveals the role of AmERF1 in salt tolerance through mediating proline biosynthesis and H₂O₂ homeostasis - Jiakun Liu; Hanchen Tang; Ling Sun; Jicheng Wang; Hezi Huang; Lihan Zhuang; Zhaoyu Guo; Xingyue Hong; Yupeng Zhang; Hai-Lei Zheng (Plant Science, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Hirsutanines H−O, monoterpene indole alkaloids from Uncaria hirsuta with neuroprotective effects - Nan An; Lei-Ming Wu; Shu-Qi Wu; Jia-Luo Huang; Dong Huang; Fang-Yu Yuan; Yi-Ling Liao; Run-Zhu Fan; Xian-Yuan Yang; Gui-Hua Tang; Lu Gan; Sheng Yin (Phytochemistry, 2026)

Decomposition-based prediction of slamming forces on two-dimensional curved bodies using deep neural network - Xupeng Sui; Kamal Djidjeli; Zhe Sun; Jing Tang Xing; Jun Ding; Ling Liu (Ocean Engineering, 2026)

First mapping of subsurface soil temperature profiles by integrating diurnal cycles of microwave and thermal infrared observations - Dabiao Chen; Huazhu Xue; Tianjie Zhao; Yuyang Xiong; Ning Li; Jingyao Zheng; Yipeng Cao; Yu Bai; Songbo Qu; Ling Yao; Tang Liu; Chi Wang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Secondhand and thirdhand smoke exposure and the risk of liver cancer: a prospective cohort study of 315,833 Chinese never smokers - Zhi Li; Ling-Xiang Xu; Chun-Rui Wang; Zhang-You Guo; Chen-Wei Tang; Xin Dai; Guo-Chao Zhong (Environmental Pollution, 2026)

Highly structured solvents enable integrated organogel networks with robust adhesion and mechanics - Dongyong Sha; Yang Zhao; Ding Ding; Shuaimin Tang; Jianxing Zhang; Xiaofeng Ling; Changsheng Liu; Liang Gao; Yuan Yuan (Chemical Engineering Journal, 2026)

Preparation, properties of bond energy-driven LKCC sequential drug-releasing hydrogel and its application in biofilm-infected wound repair - Jiangchuan He; Huan Wang; Yunhe Zheng; Yu Huang; Ting Wang; Hanchao Zhou; Kailai Liu; Yuchen Zhang; Jinpeng Wen; Jingya Qu; Pengchong Wang; Ling Liu; et al. (Chemical Engineering Journal, 2026)

Pressurized Pulsed Water Jet: A New Type of Pulsed Jet Technology for Hard Rock-Breaking - Jiren Tang; Jun Li; Wenchuan Liu; Yuanfei Ling; Yangkai Zhang; Lei Wang; Qi Yao; Zhidan Zhu (Rock Mechanics and Rock Engineering, 2026)

Machine learning-enhanced UAV multispectral remote sensing for monitoring rice leaf area index across critical growth stages - Chao Su; Zaiying Ling; Liwang Han; Yanmin Shuai; Jianguang Wen; Xingwen Lin; Haifeng Tang; Alexandre Maniçoba da Rosa Ferraz Jardim; Hoi Leong Lee; Xuguang Tang (Precision Agriculture, 2026)

Exploring the effects of canola and daylily on deep soil desiccation and jujube tree root traits in semiarid agroforestry systems on the Loess Plateau, China - Qiang Ling; Wenhao Sun; Min Tang; Xiaodong Gao; Xining Zhao; Dan Liu (Plant and Soil, 2026)

Benzalkonium chlorides compromise oocyte maturation and developmental competence by disrupting mitochondrial function and the SIRT3-SOD2 antioxidant axis - Khienduc Lay; Dandan Zhang; Hui Wang; Mengchan Li; Yongteng Zhang; Qimei Xu; Bo Jia; ThiHien Nguyen; Chunhuan Ren; Xiaoyan Zhou; Heng Tang; Yinghui Ling; et al. (Animal Reproduction Science, 2026)

Circ-Hipk3 in Adipose Derived Stem Cells Exosome Alleviates Myocardial Infarction Induced Myocardial Damage by Regulation miR-138-5p/Sirt1 Axis Mediated Autophagy - Guoxun Yang; Danpeng Nong; Xiao Tang; Ling Tan; Peng Yang; Haien Ning (Biochemical Genetics, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Highly efficient hydrogen production via photothermal-catalytic methanol steam reforming over high-entropy metal oxides - Xingyu Yin; Linjun Tang; Zhiwei Zhan; Chun Zhu; Jingtai Zhang; Xiaoxiang Zhou; Shaohua Chen; Chuanyun Yang; Ling Li; Tetsuya Kako; Jinhua Ye; Shangbo Ning (Science Bulletin, 2026)

Development and validation of a step-wise coupled model for offshore floating wind-aquaculture integration platforms considering flexible nets - Mingsheng Chen; Zhaokun Zeng; Yichang Tang; Yang Yang; Ling Ma; Guanju Lu (Ocean Engineering, 2026)

Unintentional Weight Loss as a Predictor of Adverse Prognosis in Older Adults With Chronic Obstructive Pulmonary Disease in the Intensive Care Unit: A Retrospective Cohort Study - Hongtao Cheng; Yonglan Tang; Shanyuan Tan; Simeng Song; Jia-Ming Xiong; Xiaxuan Huang; Yitong Ling; Zichen Wang; Fuling Zhou; Jun Lyu (Journal of the Academy of Nutrition and Dietetics, 2026)

Identifying seasonal spatiotemporal differentiation and factor contributions to risk bundles of water ecosystem services in a river basin by machine learning - Jia Tang; Ling Liu; Yuwei Guo; Xijun Hu; Yuncai Wang (Journal of Cleaner Production, 2026)

Foliar silicon application enhances rare earth element accumulation in the hyperaccumulator Phytolacca americana - Rui-Qi Zhang; Cui-Ling Huang; Ling-Xiu Zhou; Rong-Liang Qiu; Chong Liu; Antony van der Ent; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Environmental Sciences, 2026)

Machine learning-driven lipase engineering for highly enantioselective synthesis of chiral florfenicol intermediate via enzymatic resolution-chemical racemization coupling system - Jing-Peng Li; Hui-Hang Zhang; Zeng-Hua He; Jun-Bo Tian; Ren-Chao Zheng; Xiao-Ling Tang; Yu-Guo Zheng (Chemical Engineering Journal, 2026)

Carrier-free nanoparticles derived from Huanglian Jiedu decoction target ATP5F1C to eliminate senescent cells and ameliorate pulmonary fibrosis - Ying Zhang; Lirun Zhou; Yajian Li; Weiling Wang; Tong Yang; Qianyu Zhang; Hechen Tang; Jiayun Guo; Ling Huang; Chen Wang; Zheng Chu; Ang Ma; et al. (Chemical Engineering Journal, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Mesenchymal Stem Cell-Derived Exosomes for Ovarian Reserve: A Systematic Review and Network Meta‑Analysis Based on Animal Studies - Mingyue Yu; Yiming Ma; Xiaohui Sun; Jingjing Zhao; Tianlin Sun; Ling Tang (Stem Cell Reviews and Reports, 2026)

Environmental triggers of acute Stanford type A aortic dissection: The roles of ambient temperature, air pollution, and workplace thermal conditions - Yeni Li; Ning Niu; Ling Zhu; Manli Wu; Xiaoxu Zhang; Xiaotong Tang (International Journal of Biometeorology, 2026)

Insights on enhancing the microbial degradation potential under high-temperature conditions to remediate aged PAH-contaminated soils - Lei Tang; Zhenkai Ma; Mengyuan Wang; Bonface Oginga; Jiashuo Wang; Yixin Yuan; Rongxin Lv; Chao Qin; Xuwen Chen; Wanting Ling (Applied Soil Ecology, 2026)

Exploring the role of surface-enhanced Raman spectroscopy (SERS) in ensuring dairy quality and safety: recent progress and future prospects - Jiaqi Tian; Liyao Tang; Gang Lu; Jingshun Yang; Shuang Liu; Dexin Zhang; Pengfei Wang; Ling Kong; Zhiwei Chen; Mati Ullah Khan (Critical Reviews in Food Science and Nutrition, 2026)

An LLM-driven Agent framework for resilient modulus prediction: Integrating modified consistency index model and residual compensation - Xuanxuan Chu; Wenjun Zhang; Ling Zhao; Lin Tang; Hongjian Cai; Chengchao Guo (Transportation Geotechnics, 2026)

Experimental investigation on dynamic characteristics of gravel soil filler for railway subgrade affected by varying initial moisture content - Mengyao Qiu; Xuesi Luo; Liang Tang; Shuang Tian; Yuxuan Sun; Subhamoy Bhattacharya; Xianzhang Ling (Transportation Geotechnics, 2026)

Macro-meso mechanical response of ice-bearing glaciofluvial deposits under thaw–freeze–thaw cycles - Yifan Zhang; Liang Tang; Xiangxun Kong; Shuang Tian; Xianzhang Ling; Shanzhen Li; Guoyu Li (Transportation Geotechnics, 2026)

Viruses regulate soil C:N stoichiometry by boosting C-cycling under long-term N fertilization - Hanpeng Liao; Chen Liu; Tian Gao; Chaofan Ai; Ning Ling; Shuping Qin; Chunsheng Hu; Dong Zhang; Xiang Tang; Ville-Petri Friman; Shungui Zhou (Soil Biology and Biochemistry, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Jasmonic acid affects epidermal cell fate determination via influencing cell cycle related gene expression in mangrove Avicennia marina - Xingyue Hong; Hanchen Tang; Hezi Huang; Mingyue Wei; Mengqi Wu; Zhaoyu Guo; Jiakun Liu; Lihan Zhuang; Ling Sun; Jicheng Wang; Hanxin Zheng; Hai-Lei Zheng (Plant Science, 2026)

Numerical study of the effect of the pitch ratio of a helical strake on the vortex-induced vibration of a cylinder - Xiumei Ling; Xiangxi Han; Junlong Su; Hongqi Luo; Jiahao Zhang; Liping Fang; Zhanbin Meng; Youhong Tang; Di Ren (Ocean Engineering, 2026)

Strontium and sulfur isotope constraints on climate fluctuations and marine incursions in the lacustrine Subei Basin during the late Paleocene - Yang Liu; Xuerui Liang; XiPeng He; Xuan Tang; Yuqiao Gao; Ling Zan; Caixia Hua; Peixian Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Aeration strategy and nitrogen loading for stable partial nitrification coupled with oxygen-permeable membranes: Long-term performance, biofilm characteristics, and microbial succession - Xifang Tang; Bao-Shan Xing; Yong-Ning Feng; Ling-Hu Li; Xin-Xin Sun; Yu-You Li; Rong Chen (Journal of Water Process Engineering, 2026)

Glomalin related soil protein enhances the capacity of PAH natural attenuation in soils through modulation of soil organic matter and microbiota - Xian Zhou; Pengfei Li; Yin Cao; Lei Tang; JunChao Ma; Jian Wang; Wanting Ling (Journal of Environmental Management, 2026)

Screening, risk assessment, and rapid detection of mycotoxins in edible herbs based on UPLC-MS/MS and FT-NIR - Kangnan Liu; Ling Fang; Yaling An; Zijun Tang; Wenjie Zhao; Chunqian Song; Lin Feng; Xiaokang Liu; Zhenwei Li; Daidi Zhang; De-an Guo (Food Research International, 2026)

Promoting the formation of β-lactoglobulin amyloid fibrils induced by cold plasma treatment: self-assembly mechanism, emulsifying properties, and stability - Gongshuai Song; Tian Zhao; Yingcong Yang; Yangcheng Ge; Wei Tang; Taijiao Xiang; Danli Wang; Tinglan Yuan; Ling Li; Yong Cheng; Mengna Zhang; Jinyan Gong (Food Research International, 2026)

Occurrence, landscape impact, and risk assessments of pesticides in a major river basin of a tropical island, South China - Ling Mo; Bin Tang; Li-Ke Chen; Jun Xiang; Ming-Yang Wang; Kai-Yi Wu; Ming-Zhong Ren; Qiao Xing; Li-Cheng Wang; Jing Zheng (Environmental Pollution, 2026)

Seismic risk assessment of railway embankments on spatially variable loose deposit slopes: A stacking ensemble machine learning-based approach - Pan Si; Liang Tang; Shuang Tian; Yanfang Liu; Xianzhang Ling (Computers and Geotechnics, 2026)

Bacillus velezensis-derived methylmalonic acid inhibits Aspergillus flavus growth and aflatoxin biosynthesis by interfering with tryptophan metabolism - Ming Li; Qin Han; Xiulan Zhao; Yuxuan Hong; Ye Zhu; Can Liu; Jinyan Chai; Ling Cheng; Xiaofeng Yue; Xiaoqian Tang; Jing Mao; Qi Zhang; et al. (Chemical Engineering Journal, 2026)

Electrolyte-free organic/inorganic semiconductor heterojunction all-solid-state electrochromic device: photoelectric synergy and interfacial properties - Yuzhi Zhou; Xiao Tang; Lin Xu; Yanhong Li; Faling Ling; Hongmei Yang; Chuan Jing; Shengnan Duan; Xianju Zhou (Chemical Engineering Journal, 2026)

Elastic ceramic aerogels via multiscale structural engineering for thermal superinsulation in extreme environments - Zhen Xu; Junhua Zhang; Ling Xu; Feiyang Ni; Sihan Hu; Shengkui Tang; Lei Zhang; Nannan Ge; Bo Wu; Zhenzhen Xu; Dingsheng Wu; Quan Feng (Chemical Engineering Journal, 2026)

Chemical constituents from the twigs and leaves of Viburnum utile Hemsl. (Adoxaceae) and their taxonomic distribution - Dong-Mei Zhou; Lijin Jiao; Huai-Qin Liu; Bang-Quan Tang; Guo-Bo Xu; Qin-Feng Zhu; Xi-Rong Luo; Shang-Gao Liao; Ling-Ling Yu (Biochemical Systematics and Ecology, 2026)

The Bra1K array: an efficient and versatile 1K liquid-phase SNP chip for genetics and breeding in Chinese cabbage - Shuangjuan Yang; Ling Zhang; Zhaojun Wang; Hao Tang; Xiaochun Wei; Zhiyong Wang; Henan Su; Yanyan Zhao; Wenjing Zhang; Lin Li; Haohui Yang; Xiaowei Zhang; et al. (Theoretical and Applied Genetics, 2026)

Protective role and mechanism of sonic hedgehog signaling pathway in spinal cord injury - Li Li Yin; Xiao Zhen Ji; Min Tang; Li Hui Chen; Jiu Zhou Lin; Ya Ling Jin; Wei Ting Chen (Molecular & Cellular Toxicology, 2026)

Adoption of tree-based machine learning algorithms and CPT data for liquefaction potential assessment - Shuang Tian; Pan Si; Liang Tang; Xianzhang Ling; Yanfang Liu (Earthquake Engineering and Engineering Vibration, 2026)

Assessment of female fertility and oocyte quality in mice after exposure to polystyrene microplastics and polybrominated diphenyl ethers, alone and in combination - Wenwen Hou; Zaishan Yang; Xiaoyan Zhou; Heng Tang; Yongteng Zhang; Mengchan Li; Sien Yao; Changyin Zhou; Yunhai Zhang; Zubing Cao; Yinghui Ling; Yang Gao; et al. (Apoptosis, 2026)

Metabolomic profiling reveals activity-correlated chemotypes and strain-specific metabolites in mangrove-derived actinomycetes - Bonan Yan; Ming Chen; Ling Li; Peixi Zhang; Ki Shi; Li Guo; Yixin Tang; Chunlan Li; Yanjun Di; Chen Zhu; Yuting Wu; Chenlei Lian; et al. (Natural Product Research, 2026)

Oyster-derived Zinc Exhibits Superior Anti-anemic Efficacy and Bioavailability Compared with Conventional Zinc Supplements - Yen-Hua Chen; Hui-Lin Feng; Jia-Ling Tang; Chen-Wei Chang; Sen-Shyong Jeng (Biological Trace Element Research, 2026)

Moisture-Proof Herbal Extract Pellets Prepared via Asymmetric Liquid Layering Technology Combined with Mesoporous Silica and Magnesium Stearate - Shilin Ma; Yupeng Feng; Panao Yuan; Yunlong Xu; Ping Shao; Lifeng Lin; Zimin Wang; Ling Han; Xing Tang (AAPS PharmSciTech, 2026)

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Quantifying ground temperature characteristics affected by underground buildings in spatial-temporal distributions - You Tang; Yongqiang Luo; Ling Zhang; Jiang Chen; Xudong Tang; Zhenghong Wu (Urban Climate, 2026)

Water migration in frozen high-speed railway subgrades under traffic vibration: Piston suction versus mud pumping and pot cover effect - Ke Wang; Tianxiao Tang; Shanzhen Li; Shuang Tian; Lianzhen Zhang; Shuang Liu; Xianzhang Ling (Transportation Geotechnics, 2026)

Subspecies-specific epigenetic remodeling drives differential cold adaptation in geng/xian rice - Dong-Ao Li; Xiao-Long Xu; Yu-Hong Luo; Zu-Wen Zhou; Yong-Qing Qian; Qian Tang; Xi-Tong Zhu; Jia-Ming Song; Ling-Ling Chen (Plant Science, 2026)

Reversible hydrogen storage in Mg-functionalized B-doped graphene: A study based on density functional theory - Xiao Ling Liu; Shun Ping Shi; Lei Lei Tang; Kai Diao; Jia Bao Hu; Yi Liang Liu (Fuel, 2026)

Dihydromyricetin-loaded TPGS/gelatin grafted-β-Cyclodextrin/ chitosan grafted-β-Cyclodextrin nano-delivery system for improving oral absorption - Ling Tang; Jinqing Chen; Jiali Luo; Huijuan Wei; Lina Lan; Hailan Qin; Qiumei He; Xiangyu Kong; Liting Lai; Wenya Ding; Jian Xiao (Food Research International, 2026)

Preparation of responsive photonic crystals and their application in the detection of food hazards - Ting Li; Haihu Tan; Yang Liu; Chao Ge; Zhouyu Sun; Zengmin Tang; Ling Yang (Food Control, 2026)

Microplastics affect the quality of Cucumis melo. L by regulating the jasmonic acid signaling pathway - Tianyu Liu; Jinpeng Zhang; Mao Xu; Zhengkun Zhang; Yanjun Li; Xuedong Tang; Ling Liu; Yong Yu (Environmental Pollution, 2026)

Triple-field coupling in organic-mineral hybrids: Activating peroxymonosulfate for singlet oxygen formation and rapid imidacloprid degradation - Zhanpeng Zhou; Hao Zeng; Ling Li; Huiling Liu; Yuelin Huang; Chenyu Zhang; Wenbo Li; Rongdi Tang; Ying Huang; Yaocheng Deng (Chemical Engineering Journal, 2026)

Synergistic effect of choline cation and chlorine anion boosts four-electron zinc‑iodine battery - Ling He; Jiamin Tang; Zhihao Ying; Xinyang Wang; Wenqing Jiang; Haichuan He; Jie Wang; Zhengxin Zhu (Chemical Engineering Journal, 2026)

Nr4a2, A Key Factor Controlling the Development and Functional Maintenance of Forebrain Car3 Neurons - Yun-Chao Tao; Li Zhao; Qiong Zhang; Xi-Yue Liu; Wei-Tang Liu; Ze-Xuan Li; Ling Hu; Lei Zhang; Jia-Yin Chen; Yu-Qiang Ding; Ning-Ning Song (Neuroscience Bulletin, 2026)
Nr4a2 ( Nurr1 ) is well known to be vital for midbrain dopaminergic neurons. Recent single-cell RNA analyses reveal that Nr4a2 is expressed in lateral cerebral regions, within neurons named L4/L5/L6 IT Car3 . These neurons have attracted intense attention for the molecular mechanisms underlying their development and functions. We classified Car3 neurons into neocortical (Ncx- Car3 ), claustral (CLA- Car3 ), and dorsal endopiriform nucleus (dEn- Car3 ) subpopulations, focusing on the characterization of Ncx- Car3 neurons. These neurons exhibit distinct birthdates and migratory morphologies compared to CLA- and dEn- Car3 neurons, but share a common transcriptomic profile when Nr4a2 is deleted at the embryonic stage or in adulthood. Notably, Nr4a2 misexpression ectopically induces Car3 -enriched genes in vivo . Mice lacking Nr4a2 in Car3 ensembles during the embryonic stage or in adulthood display hyperactivity and reduced anxiety-like behaviors. Therefore, our results demonstrate that Nr4a2 is a key factor in regulating the development and functional maintenance of the forebrain Car3 neurons.

Changes in Soil Phosphorus Fractions Across Soil Depths Under Continuous Wheat-Faba Bean Intercropping - Wenlian Bai; Rong Dai; Ling Qian; Weiwu Changjin; Li Tang; Yi Zheng; Jingxiu Xiao (Journal of Soil Science and Plant Nutrition, 2026)

Salvia miltiorrhiza (Danshen) and its extracts in the alternative treatment of diabetic nephropathy: mechanisms and clinical perspectives - Lu Song; Yan Li; Huakui Zhan; Ling Wu; Li Tang; Xinyu Wang; Qinyuan Deng (Journal of Natural Medicines, 2026)

Bernardetia aquimarina sp. nov., Isolated from Sargasso Samples from the Yellow Sea - Hai-Xia Zhu; Shi-Ning Cai; Ning-Hua Liu; Zhi-Gang Tang; Xue-Yun Geng; Xiao-Yan Song; Mei-Ling Sun; Xi-Ying Zhang (Current Microbiology, 2026)

Proanthocyanidin B2 regulates epidermal growth factor receptor (EGFR) and activates the PI3K/AKT pathway to promote the in vitro maturation of sheep oocytes - Yucheng Liu; Jingjing Wang; Zhenliang Zhang; Jiachen Bai; Houru Li; Zhanmin Lv; Lei Gao; Jianhong Ni; Shouliang Lu; Changbin Liu; Guiping Hai; Weijun Liu; et al. (Theriogenology, 2026)

Urban flood susceptibility decoded: A GeoAI workflow for urban flood-prone area delineation and mitigation mechanism inference - Junhao Wu; Yuanpeng Tang; Ling Ma; Dongfang Liang; Ioannis Brilakis; Svetlana Besklubova (Sustainable Cities and Society, 2026)

Comprehensive single-cell profiling uncovers TsMHC-II expression predicting response to neoadjuvant immunotherapy in gastric cancer - Zhiyuan Xu; Zhichun Tang; Simeng Hu; Litao Yang; Jingli Xu; Pengfei Yu; Yian Du; Yanqiang Zhang; Jiahui Chen; Xiaoxiao Wu; Siwei Pan; ShengJie Zhang; et al. (Science Bulletin, 2026)

Spatial distribution and determinants of large old trees in the upper and middle reaches of the Tarim basin, Xinjiang, China - Haijun Zhang; Wanqing Zhao; Mengying Tang; Ling Li; Jianjun Yang (Journal of Arid Environments, 2026)

Insight into the antioxidant mechanism of astaxanthin geometric isomers by quantum chemical calculations and molecular simulations - Yanbo Chen; Ling Liu; Xiaohan Fu; Tianyue Zhou; Shuge Tang (Food Chemistry, 2026)

NaCl and light quality reprogram carbohydrate metabolism to modulate growth, quality, and flavor in mustard (Brassica juncea) sprouts - Hongmei Di; Ling Li; Liping Su; Lisha Peng; Ling Rao; Zhifeng Chen; Victor Hugo Escalona; Jing Yang; Yu'nong Zhou; Yong Li; Xuena Yu; Kehao Liang; et al. (Food Chemistry, 2026)

Polyphthalocyanine-based nanostructure for sono-immunotherapy by reprogramming the tumor microenvironment and blocking immune checkpoint - Lingfeng Jiang; Jiawei Wang; Wenjun Liu; Xin Xie; Xiao Luo; Ling Tu; Liangqing Tang; Qing Zhang; Hongmei Yuan; Hanfeng Yang; Qi Li; Sujiao Cao; et al. (Chemical Engineering Journal, 2026)

The efficient ethane oxychlorination to ethylene on Cu Zn LDO through confinement-interface synergy - Kunhao Bi; Baosen Tang; Wei Cui; Shaoqing Qu; Weizhen Sun; Ling Zhao (Chemical Engineering Journal, 2026)

Lattice engineering of Li1.6Mn1.6O4 adsorbent materials mitigates Jahn-Teller distortion for efficient and stable lithium extraction from brine - Lu-Ri Bao; Zhi Ai Huang; Ling Zang; Wei Ping Tang; Shu-Ying Sun (Chemical Engineering Journal, 2026)

Rill and interrill erosion on slopes in granite red soil quantified by using Sm and Eu as tracers: An indoor rainfall simulation study - Zhe Lin; Yusong Deng; Qiuyue Tang; Jianyu Wang; Yuanfeng Yang; Jiangxing Wei; Ling He; Xiaoqian Duan (CATENA, 2026)

High lytic activity of endolysin LysDCp1 from phage DCp1 against Clostridium perfringens and biofilms - Ruixue Ma; Zhaohui Tang; Jianchao Zhao; Ziyang Li; Yanshun Cui; Can Zhang; Huiying Ren; Shouzhen Xu; Ling Zou; Jing Ma; Jianbao Dong; Xiaojing Hao; et al. (Veterinary Research Communications, 2026)

Multifaceted Role of RIMBP2 in Promoting Hearing in Murine Cochlear Hair Cells - Menghui Liao; Xin Chen; Ling Lu; Qing Liu; Rongrong Guo; Yuyang Qiu; Yangnan Hu; Yuhua Zhang; Qiaojun Fang; Panpan Zhang; Yige Li; Shuijin He; et al. (Neuroscience Bulletin, 2026)

Rational design of fused-ring-modified rhodamine chemosensors for salicylic acid detection: its mechanistic insights and biological application - Mei-Hong Ge; A-Ling Tang; Feng Gao; Shuai Tan; Wei Niu; Xiang Zhou; Song Yang (Molecular Diversity, 2026)

miR-19b-3p regulates autophagy of BMSCs in hypoxia through PTEN/Akt/mTOR pathway to promote fracture healing - Shouyu Xiang; Wei Liu; Cheng Tang; Chuhai Xie; Hailan Hu; Jianhui Zhou; Yanming Cao; Long Ling (Journal of Molecular Histology, 2026)

Moderate grazing strengthens the responses of plant diversity and ANPP to climatic factors in semi-arid grasslands - Jing Hou; Jun Liu; Zhiyu Liu; Yunmeng Tang; Chen Liu; Xuekai Sun; Kaimeng Wang; Huimei Zhang; Siyu Li; Ling Wang; Deli Wang; De-Hui Zeng; et al. (Agriculture, Ecosystems & Environment, 2026)

Microplastic pollution in Chinese Rivers: A detailed analysis of distribution, risk factors, and ecological impact - Xin Xiang; Yang Liu; Ling Tang; Li Xueying; S.U. Xinrong (Marine Pollution Bulletin, 2026)

Triaxial creep test and damage model study of coarse-grained materials from red-bed soft rocks under freeze–thaw cycles: A multiscale analysis - Xiao Han; Shuang Tian; Xianzhang Ling; Liang Tang; Ruotong Sun; Chao Zhou; Luidmila Pestryakova (Transportation Geotechnics, 2026)

Probabilistic seismic performance analysis of railway embankments on spatially variable loose deposit slopes - Liang Tang; Pan Si; Shuang Tian; Yanfang Liu; Xianzhang Ling (Transportation Geotechnics, 2026)

Influence of clay content on static shear strength of sand-clay mixture - Tao Li; Yongfei Lin; Ling Zeng; Xiaowei Tang; Gang Yang; Shun Liu (Soil Dynamics and Earthquake Engineering, 2026)

Centrifuge test determination of wharf responses due to spatially and temporally varying interactions between wharf piles and liquefied soil - Zheng Zhang; Liang Tang; Shengyi Cong; Xianzhang Ling; Chouw Nawawi (Soil Dynamics and Earthquake Engineering, 2026)

Development of a new surface sediment connectivity model based on network analysis and application to the Yeji River watershed in the karst region of southern China - Feiyang Cai; Rui Li; Benjin Yu; Linlv Xiao; Ling Xiong; Zhengyi Tang (Journal of Hydrology, 2026)

Long-term ozone exposure and risks of diabetes and hypertension: Mediated by inflammatory, lipid and oxidative stress biomarkers in a prospective cohort - Yishu Yang; Hongyue Sun; Zhuohan Jiang; Mengfan Yan; Huajie Yang; Zinuo Wang; Honglu Zhang; Xueli Yang; Fang Hou; Pei Yu; Ling Zhang; Zhiwei Sun; et al. (Journal of Hazardous Materials, 2026)

Hydrochemical characteristics, evolution, and controlling factors of a karstic river with reservoirs: Insights from spatial-temporal analysis - Jiang Wu; Ting Wang; Tang Liu; Jia-Ju Liu; Nan Xu; Hui Zeng; Ling-Yan He (Journal of Environmental Sciences, 2026)

The synergistic impacts of green finance and the digital economy on urban low-carbon transition: Insights from 293 Chinese cities - Ling Tang; Hui Yu; Yan Huang; Jianhui Ruan; Ziyu Qin; Shouyang Wang (Energy Policy, 2026)

Order-level data reveal the impact of enterprises' behavior on their profits in China's national ETS - Ling Tang; Shuangyue Qian; Jianhui Ruan; Yan Huang; Ruxing Wan; Bofeng Cai; Gang Yan (Environmental Impact Assessment Review, 2026)

Hypoxia-sensitive copper(II) nanoparticles achieve broad-spectrum anticancer therapy through synergistic cuproptosis, ferroptosis, and apoptosis - Xiang Ling; Hanchen Zhang; Dongsheng Tang; Yanqing Gong; Haihua Xiao; Xuesong Li (Chemical Engineering Journal, 2026)

Top-down selection of pit mud local microbial community for efficient anaerobic digestion of distilled grain waste - Tao Xu; Mengya Han; Yan Zeng; Rujie Yang; Ling Xiang; Hanlan Tang; Xiaotong Liu; Yuanlong Chi; Zhenghong Xu; Suyi Zhang; Danqun Huo; Xiaozhong Zhong (Bioresource Technology, 2026)

Genetic and transcriptomic identification of WPG1 controlling nitrogen allocation-related leaf chlorisis and premature senescence in wheat - Haili Zhang; Li’ao Zhang; Qiang Li; Ling Yi; Juanyu Zhang; Yanyan Tang; Jinhui Wang; Junjun Liang; Tao Li; Fangyan Zhang; Yiran Cheng; Yi Wang; et al. (Theoretical and Applied Genetics, 2026)

Terrestrial in situ cosmogenic nuclide production rate scaling models: Theory, progress, and prospects - Jie Zhou; Weijian Zhou; Yunchong Fu; Feng Xian; Du Wang; Xianlin Yang; Guocheng Dong; Li Zhang; Ling Tang; Guoqing Zhao; Mengyu Zang (Science China Earth Sciences, 2026)

Seismic Response of Utility Tunnels Under Oblique SV Wave Incidence in Horizontally Nonhomogeneous Sites - De-long Huang; Hui-yue Wang; Yang Ding; Hang Cen; Qiang Liu; Zhong-ling Zong; Dian-rui Mu; Ai-ping Tang (Geotechnical and Geological Engineering, 2026)

Land subsidence and groundwater storage change from decadal InSAR measurements in southern Tangshan, China - Xuguo Shi; Yuan Jin; Daqing Ge; Wei Tang; Guijie Wang; Li Zhang; Shaocheng Zhang; Ling Zhang (Advances in Space Research, 2026)

A Fiber-Driven Finite Element Model for Predicting Residual Limb Soft Tissue Deformation: Applications in Prosthetic Socket Design - Ling Wang; Ziyan Qiu; Lei Tang; Fuhao Huang; Pingping Wei; Senay Mihcin; Changning Sun; Hongyuan Zhao; Lei Shi; Song Han; Dichen Li (Annals of Biomedical Engineering, 2026)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Infrared imaging detection for gas leakage based on residual-enhanced nnUNetv2: Taking methane leakage from a natural gas pipeline as a case study - Xiaoyu Ji; Lei Xu; Jiale Xiao; Qi Gao; Ling Tang; Bihua Ou; Changyun Li (Process Safety and Environmental Protection, 2025)

Contrast of composition and sources of PM2.5 and PM10 in Shenzhen, China: Revealing key factors on health risks - Xing Peng; Li He; Ling-Yan He; Jiang-Yao Tan; Ke-Jin Tang; Wen-Jie Yu; Wen-Wei He; Xiao-Feng Huang (Journal of Environmental Management, 2025)

Microbial drivers controlling arsenic mobilization in paddy soils and arsenic accumulation in rice grains - Zi-Kun Dong; Bao-Ling Han; Chuan Chen; A-Xiang Gao; Zhong Tang; Fang-Jie Zhao (Environmental Pollution, 2025)

Cucurbit[6]uril-barium synergistic assembly: A supramolecular strategy for solvent stable graphene oxide nanochannel membranes - Mei-Ling Liu; Ying Tang; Chen-Hao Yi; Lan Hong; Ren-Jie Fan; Shi-Peng Sun; Weihong Xing (Chemical Engineering Journal, 2025)

Lead-free X-ray imaging scintillators based on zero-dimensional manganese hybrid metal halide - Guangya Zheng; Zizhen Bao; Linyue Liu; Ling Xu; Kuan Yew Cheong; Zhiping Zheng; Xiaoping Ouyang; Guangda Niu; Haodi Wu; Jiang Tang (Chemical Engineering Journal, 2025)

Actinobacteria mediate anaerobic methane oxidation in iron-rich environment - Shubing Li; Zhenzhen Peng; Shuguang Xie; Weiqi Chen; Ying Zhu; Wenwen Huang; Yi Tang; Mengchen Lu; Xunsen Chen; Teng Guo; Fangrong Wei; Jinshao Ye; et al. (Bioresource Technology, 2025)

A herbaceous peony WRKY transcription factor PlWRKY70 enhances tolerance to salt stress in transgenic Arabidopsis thaliana - Ling Tang; Weili Long; Yanhua Pan; Jiaxuan Ren; Weicheng Wang; Rong Huang; Fei Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Human umbilical cord mesenchymal stem cells improve the ovarian function through oxidative stress-mediated PERK/eIF-2α/ATF4/CHOP signaling in premature ovarian insufficiency mice - Pei-Ling Wu; Shi-Huan Tang; Han-Yue Wang; Hong-Mei Zhang; Lu Peng; Yao Liu; Yuan Yang; Chun-Bing Zheng; Xian-ping Zhang (Molecular Biology Reports, 2025)

Shear characteristics and damage mechanism of carbonaceous mudstone soil-rock mixed fillers based on electrical resistivity - Ling Zeng; Jing Tang; Saize Zhang; Jing Tang; Jingcheng Chen (Journal of Mountain Science, 2025)

Robust and Explainable Objective Classification of Extreme Precipitation Events Using Machine Learning - Tao Tang; Ping He; Wenqiang Shen; Hao Qian; Junping Zhao; Xiaofen Lou; Ling Luo (Journal of Meteorological Research, 2025)

Comparative analysis of deep learning models for cell counting in microalgae samples - Vimal Angela Thiviyanathan; Pin Jern Ker; Hassan Mohamed; Hasan Firdaus Mohd Zaki; Hui Jing Lee; Shirley G.H. Tang; Kai Ling Yu; Nazlina Haiza Mohd Yasin (Algal Research, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Determination of dynamic shear stress and strain thresholds in frozen coarse-grained materials: experimental and M-K statistical analysis - Shanzhen Li; Shuang Tian; Liang Tang; Xianzhang Ling; Huijun Jin; Wenjian Zhao; Ke Wang; Xiao Han (Transportation Geotechnics, 2025)

Effective control disinfection byproducts in municipal wastewater by UV-based advanced oxidation/reduction pre-treatments: Insights from FT-ICR-MS analysis - Bingliang Zhang; Qiyi Wang; Ling Zhou; Xinqi Li; Fuyao Tong; Xiaomeng Wang; Yueke Wang; Chang Xu; Xifeng Shi; Bo Tang (Journal of Hazardous Materials, 2025)

Fractionation of highly siderophile elements in forearc magmas: Influence of mantle source and magmatic differentiation - Ling Chen; Limei Tang; Xiaohu Li; Jie Zhang; Wei Wang (Geochimica et Cosmochimica Acta, 2025)

Synergistic air pollution and CO2 emission reduction in China's iron and steel industry based on real-time monitoring data - Ling Tang; Qing Yu; Jiabao Qu; Ruxing Wan; Min Jia; Shuangyue Qian; Song Lv; Jieyi Li; Shuo Qi (Environmental Pollution, 2025)

A dual-mode response fiber paper-based sensor based on curcumin and sodium alginate for soil moisture monitoring - Yu Zhou; Ruqiang Zhang; Youping Tang; Yifeng Huang; Weidong Zhang; Yulong Hu; Xichao Liang; Wenjun Li; Ling Yang; Zhu Long (Chemical Engineering Journal, 2025)

Naringenin targets and inhibits Monoamine Oxidase A/B to bidirectionally regulate intestinal motility. - Qi Li; Yi Chen; Yige Zhang; Canwei Xu; Ting Tang; Yunzhi Qian; Ong Shun seng; Yujuan Wang; Ling Fang; Tianshu Xu (Chemico-Biological Interactions, 2025)

Various formation pathways of size-resolved secondary organic aerosols at a coastal site in Eastern China - Meng-Xue Tang; Jia-Yuan Wang; Ke-Jin Tang; Wen-Jie Yu; Li He; Xiao-Feng Huang; Ling-Yan He; Hui Zeng; Si-Hua Lu; Min Hu (Atmospheric Environment, 2025)

Mendelian randomization combined with real-world study reveals that Streptococcus anginosus exacerbates dietary triglyceride metabolism disorders in obese mice - Xian-Long Shu; Jia-Ling Xie; Xi Li; Guo Wang; Jie Tang (World Journal of Microbiology and Biotechnology, 2025)

Real-time extraction of multi-GNSS ionospheric observables based on PPP-AR - Yan Xiang; Yifan Zhao; Tiantian Tang; Ningbo Wang; Zishen Li; Ling Pei; Wenxian Yu (Journal of Geodesy, 2025)

Co-occurrence networks dominated by rare and abundant fungal species influence the potential function of fungal communities in Eucalyptus urophylla plantations under successive planting - Yuting Yang; Aoyu Ling; Lingyue Zhu; Qinzhan Wu; Kangting Huang; Dexu Zhang; Zhengye Wang; Zuoyu Qin; Lichao Wu; Jian Tang (Applied Soil Ecology, 2025)

Gynogenetic offspring from distant hybridization of red crucian carp × blunt snout bream: Insights into barbel origin - Zhengkun Liu; Xinyi Deng; Wanjing Peng; Siyang Li; Ling Xiong; Enkui Hu; Yan Tang; Zeyang Li; Qian Xiao; Yuhan Yang; Xu Huang; Chongqing Wang; et al. (Aquaculture, 2025)

Interaction effects of organic mulch application rates and rainfall intensities on soil and water loss in karst sloping farmlands: Insights from a laboratory simulation experiment - Panpan Wu; Rui Li; Feiyang Cai; Ling Xiong; Zhengyi Tang; Linlv Xiao (Soil and Tillage Research, 2025)

Interpretable machine learning models for predicting hormesis of binary antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Pei-Pei Zhang; Yan-Peng Liang; Hong-Hu Zeng; Yong-Hong Zhang; Li-Tang Qin (Journal of Hazardous Materials, 2025)

Autophagy and glycolysis synergistically mediate Cd²⁺ transport to enhance Cd tolerance in Arabidopsis - Hanchen Tang; Shoujian Zang; Xingyue Hong; Ruiyuan Jiang; Hezi Huang; Shengwei Hu; Mengqi Wu; Qinghua Li; Jicheng Wang; Ling Sun; Yupeng Zhang; Dekai Chen; et al. (Journal of Hazardous Materials, 2025)

Human-intensive activities altered seasonal fingerprint of antibiotic resistome and their health risks in lake sediments - Ling Zhang; Junhong Bai; Yaqi Wang; Yujia Zhai; Ruoxuan Tang (Journal of Environmental Chemical Engineering, 2025)

Enhanced low-temperature catalytic activity and SO2 resistance in ethane oxidation over Pt-CoZr catalysts: Insights into the promoting effects of Pt and Zr - Ling Wang; Beilong Lin; Zhiyuan Gong; Minghui Tang; Shengyong Lu; Jianhua Yan (Journal of Environmental Chemical Engineering, 2025)

Activation and reaction mechanism of persulfate in the removal of antibiotic resistance genes - Weijie Song; Lei Tang; Wenjie Li; Wanting Ling; Xuwen Chen (Journal of Environmental Chemical Engineering, 2025)

Regulating the surface-interface structure of CdS by inexpensive co-catalyst CoS2: Promoting photocatalytic degradation of antibiotics - Yuxin Zheng; Shuang Luo; Heng Huang; Yueyue Tang; Jiadai He; Haijie Yu; Jiayi Peng; Renhui Ling; Xiao Li; Jianjian Wang (Journal of Environmental Chemical Engineering, 2025)

Experimental analysis of evaporation and heat transfer characteristics during the ignition process of RP-3 liquid flow on a curved hot surface - Chen Wang; Ling Yang; Mengqi Tang; Weixin Tong; Jie Ji (Fuel, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Temporal dynamics of gonadal development and reproduction of wild Manila clam (Ruditapes philippinarum) in the Xiaoqing River estuary, Laizhou Bay - Lulei Liu; Suyan Xue; Ang Li; Yushui Ren; Ling Zhu; Jiaqi Li; Longzhen Liu; Yuze Tang; Yanguo Qiu; Yuze Mao (Estuarine, Coastal and Shelf Science, 2025)

A high charging rate self-charging power system with Zeolitic Imidazolate Framework (ZIF-8)@MXene/carbon nanofibers based micro-supercapacitors for wearable electronics - Haonan Zhang; Huaibao Tang; Ling Fang; Yunchuan Luo; Jie Zhou; Leilei Shu; Olim Ruzimuradov; Shavkat Mamatkulov; Butanov Khakimjan Turamuradovich; Kamoladdin Saidov; Dae Joon Kang; Wen He; et al. (Chemical Engineering Journal, 2025)

First Isolation of a Multi-azole-Resistant Aspergillus fumigatus cyp51A TR46/Y46F/F70L Mutant in a Patient with Fungal Keratitis - Xiang Han; Heng Zhang; Yuqi Mao; Wenhao Ling; Lu Ge; Menghua Tang; Yi Sun; Zhiqin Wu (Mycopathologia, 2025)

Subclinical atrial fibrillation prediction based on deep learning and strain analysis using echocardiography - Sung-Hao Huang; Ying-Chi Lin; Ling Chen; Sayan Unankard; Vincent S. Tseng; Hsuan-Ming Tsao; Gau-Jun Tang (Medical & Biological Engineering & Computing, 2025)
Subclinical atrial fibrillation (SCAF), also known as atrial high-rate episodes (AHREs), refers to asymptomatic heart rate elevations associated with increased risks of atrial fibrillation and cardiovascular events. Although deep learning (DL) models leveraging echocardiographic images from ultrasound are widely used for cardiac function analysis, their application to AHRE prediction remains unexplored. This study introduces a novel DL-based framework for automatic AHRE detection using echocardiograms. The approach encompasses left atrium (LA) segmentation, LA strain feature extraction, and AHRE classification. Data from 117 patients with cardiac implantable electronic devices undergoing echocardiography were analyzed, with 80% allocated to the development set and 20% to the test set. LA segmentation accuracy was quantified using the Dice coefficient, yielding scores of 0.923 for the LA cavity and 0.741 for the LA wall. For AHRE classification, metrics such as area under the curve (AUC), accuracy, sensitivity, and specificity were employed. A transformer-based model integrating patient characteristics demonstrated robust performance, achieving mean AUC of 0.815, accuracy of 0.809, sensitivity of 0.800, and specificity of 0.783 for a 24-h AHRE duration threshold. This framework represents a reliable tool for AHRE assessment and holds significant potential for early SCAF detection, enhancing clinical decision-making and patient outcomes. Graphical abstract

Sex-Associated Indels and Candidate Gene Identification in Fujian Oyster (Magallana angulata) - Yi Han; Yue Ning; Ling Li; Qijuan Wan; Shuqiong Li; Ying Yao; Chaonan Tang; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Fishes, 2025)
Sex determination is a fundamental biological process governing animal reproduction. Although substantial progress has been made in elucidating its genetic basis, the genetic architecture underlying complex sex determination systems remains poorly understood. In this study, we identify sex-associated insertion–deletion (indel) variants, screen candidate genes, and compare sex-associated variation across populations with different genetic backgrounds in the Fujian oyster (Magallana angulata). Based on whole-genome resequencing data of a culture strain (designated FL), a total of 299,774 high-quality indels were identified. By integrating genome-wide association analysis (GWAS), fixation index (FST) analysis, and sex-biased genotype frequency comparisons, 77 overlapping sex-associated indels were identified, predominantly clustered within a 1.8 Mb (8.3–10.1 Mb) region on chromosome 9. Principal component analysis (PCA) based on the sex-associated markers and their subsets consistently separated male and female individuals in the FL strain. For two representative sex-associated indels, PCR-based genotyping methods were developed and validated. Functional annotation identified putative candidate genes for sex determination, including PKD1L1, 5-HTRL, SCP, and CCKRa. Comparative analysis of variants within PKD1L1 across wild, farmed, and selectively bred populations revealed a progressive enrichment of male-linked alleles in domesticated and selectively bred groups, particularly in male individuals. This study provides direct evidence that sex in the Fujian oyster is genetically determined and reveals that domestication and artificial selection may drive the emergence of major sex-determining loci, offering important insights into the genetic basis of sex determination in the Fujian oyster, and establishing a theoretical and practical foundation for molecular marker-assisted breeding of monosex lines for this species.

Dietary isoleucine requirement of grass carp (Ctenopharyngodon idella) based on growth performance, muscle nutritional value, and extracellular matrix gene expression - Kaixuan Ren; Lin Feng; Pei Wu; Yang Liu; Dong Han; Wenbing Zhang; Ling Tang; Shuwei Li; Shengyao Kuang; Xiaoqiu Zhou; Weidan Jiang (Aquaculture, 2025)

Low VTG1 levels trigger failed development of yellow follicles in ZZ female Chinese soft-shelled turtles - Jiequn Tang; An Huang; Jinni Wang; Yanyan Zhang; Wei Sun; Ling Xiao; Chutian Ge; Yin Guo (Aquaculture, 2025)

Hinokitiol induces developmental and cardiovascular toxicity in zebrafish larvae and potential mechanisms - Chenkai Ge; Ziang Wang; Weitao Hu; Qinyuan Shen; Weirong Li; Wenwen Zha; Zhonghao Xiao; Jingrong Tang; Ling Huang; Huimin Li; Zigang Cao; Jianjun Chen (Toxicology and Applied Pharmacology, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Sulfur-synergized dual-cobalt anchoring configuration in carbon nitride: Deciphering cooperative mechanisms for boosted peroxymonosulfate activation - Wenbo Li; Hao Zeng; Zhanpeng Zhou; Ling Li; Rongdi Tang; Chunxia Ding; Daoxin Gong; Yaocheng Deng (Chemical Engineering Journal, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Screening of efficient Antimony-oxidizing bacterium Lysinibacillus HC02 and its effect on preventing the absorption and accumulation of Sb in Brassica napus - Zicong Xiong; Caiyuan Ling; Qian Zhang; Junwei Tang; Jingying Gu; Yuan Su; Weiwei Yang; Chaolan Zhang (Plant and Soil, 2025)

Calycosin alleviates ovariectomy-induced osteoporosis by promoting BMSCs autophagy via the PI3K/Akt/mTOR pathway - Shouyu Xiang; Yinji Luo; Wei Liu; Cheng Tang; Tianyu Zhu; Lai Tian; Tiansheng Zheng; Long Ling; Mingyang Jia; Xing Li; Yanming Cao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Ecological security evaluation and early warning of ski tourism destinations - Chengcai Tang; Ying Han; Ling Jiang (Journal of Geographical Sciences, 2025)

Correction: Comprehensive assessment of chemical and microbial inducers for coral larval settlement across diverse coral species - Huiming Sun; Qingsong Yang; Junde Dong; Jie Li; Chang Chen; Xiaoyu Tang; Ying Zhang; Juan Ling (Frontiers in Marine Science, 2025)

Hybrid of glioma growth model and deformable image registration for longitudinal brain MRIs synthesis - Fulian Zhong; Yujian Liu; Jianquan Zhong; Ling He; Zhonglan Tang; Jing Zhang (Journal of Theoretical Biology, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Synergizing meat science and interpretable AI: Quantifying crispness gradients for quality authentication of Tilapia fillet processing - Shuqi Tang; Ling Zhang; Xingguo Tian; Manni Zheng; Hu Zhang; Nan Zhong (Food Chemistry, 2025)

Tailoring a donor-acceptor structure in oxygen and cyano group co-modified carbon nitride for enhanced photocatalytic imidacloprid degradation - Ling Li; Hao Zeng; Liqiao Zhong; Hao Wu; Jin Zheng; Zhanpeng Zhou; Jiawei Liu; Rongdi Tang; Yaocheng Deng; Ying Huang (Chemical Engineering Journal, 2025)

Decoding STING’s roles in cancer: immunity, pain, dormancy, and autophagy - Huan-xin Lin; Ya-ling Tang; Xin-hua Liang (Molecular and Cellular Biochemistry, 2025)

Establishment of the Diagnostic Signature of Ferroptosis Genes in Multiple Sclerosis - Yang Yang; Qianqian Bai; Fangfei Liu; Shumin Zhang; Wenchao Tang; Ling Liu; Zhehua Xing; Hao Wang; Chi Zhang; Yanhui Yang; Hua Fan (Biochemical Genetics, 2025)
Ferroptosis is a novel form of membrane-dependent cell death that differs from other cell death modalities such as necrosis, apoptosis, and autophagy. Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system primarily affecting brain and spinal cord neurons. Although the pathogenesis of these two conditions may seem unrelated, recent studies have indicated a connection between ferroptosis and multiple sclerosis. In fact, ferroptosis plays a significant role in the development of MS, as evidenced by the presence of elevated iron levels and iron metabolism abnormalities in the brains, spinal cords, and other neurons of MS patients. These abnormalities disrupt iron homeostasis within cells, leading to the occurrence of ferroptosis. However, there is currently a lack of research on the diagnostic value of ferroptosis-related genes in multiple sclerosis. In this study, we employed bioinformatics methods to identify ferroptosis-related genes ( ATM, GSK3B, HMGCR, KLF2, MAPK1, NFE2L1, NRAS, PCBP1, PIK3CA, RPL8, VDAC3 ) associated with the diagnosis of multiple sclerosis and constructed a diagnostic model. The results demonstrated that the diagnostic model accurately identified the patients’ condition. Subsequently, subgroup analysis was performed based on the expression levels of ferroptosis-related genes, dividing patients into high and low expression groups. The results showed differences in immune function and immune cell infiltration between the two groups. Our study not only confirms the correlation between ferroptosis and multiple sclerosis but also demonstrates the diagnostic value of ferroptosis-related genes in the disease. This provides guidance for clinical practice and direction for further mechanistic research.

AHNAK2 Regulates NF-κB/MMP-9 Signaling to Promote Pancreatic Cancer Progression - Na-na Tang; Rong-bo Xu; Bo Jiang; Hai-ling Zhang; Xiao-song Wang; Dan-dan Chen; Ji-jun Zhu (Biochemical Genetics, 2025)

Synergistic effects of air pollutants and CO2 at Chinese thermal power plants based on real-monitored data - Ling Tang; Shuangyue Qian; Ruxing Wan; Song Lv; Jieyi Li; Jiaxin Zhang; Wei Shuai; Shuo Qi; Peng Wang; Jiabao Qu; Yinghao Chu (Journal of Environmental Management, 2025)

Dual-opto-CRISPRi-mediated dynamic regulation of fructose metabolism for high-efficiency D-allulose biosynthesis in E. coli - Yuwei Wang; Yingmengyu Qin; Tongjian Li; Dandan Tang; Yuting Lu; Wei Liu; Ling Jiang (Food Bioscience, 2025)

Carbon negative technology empowered adsorption behaviour and mechanism of porous geopolymer - Lingling Zhang; Xiao Ling; Yang Liu; Zhaohou Chen; Bingyang He; Yanlin Wang; Zian Tang; Daqiang Cang (Environmental Research, 2025)

Continuous manufacturing of solvent-driven poly(vinyl alcohol)-based flexible electrodes with vias conductive gels for sensitive skin-integrated electronics - Dongyong Sha; Ding Ding; Shuaimin Tang; Jianxing Zhang; Xuan Tang; Changsheng Liu; Xiaofeng Ling; Lili Sun; Yuan Yuan (Chemical Engineering Journal, 2025)

Dynamic changes in DNA methylation and correlated expressing genes during somatic embryogenesis in Hevea brasiliensis - Ling Li; Jia Miao; Jin Liu; Ming-Chun Gui; Min Tang; Hai Tian; Wan-Yuan Shi; Guo-Ping Liang; Xiao-Long Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Spring Rapid Temperature Variability in Southern China: Characteristics, Decadal Trend and Associated Climate Impacts on Crop Yield - Xianke Yang; Yixuan Zhang; Haosu Tang; Ping Huang; Xiaoxia Ling; Shaobing Peng; Dongliang Xiong (International Journal of Climatology, 2025)
Climate‐related risks are shaped not only by changes in mean temperatures, but also by temperature variability, which raises the likelihood of extreme weather events with profound impacts on society and ecosystems. Previous studies have documented contrasting seasonal trend differences in summer and winter temperature variability across most land areas. However, spring—a phenologically sensitive season for agricultural systems—has received limited attention for its temperature variability. Focusing on the major rice‐growing regions in southern China, this study employs three indices—daily temperature standard deviation (STD), day‐to‐day temperature variability (DTD) and rapid cooling events (RCE)—to analyse the decadal trends and causes of spring temperature variability and assess its climate effects on rice yield anomalies. Our results reveal decadal trends in the spatial distribution of temperature variability, with increasing frequency and intensity in the Yangtze River Basin and Yunnan Province, and a decreasing trend across much of South China, closely following regional climatological patterns. Overall, the frequency and intensity of RCE trend exhibit a “strong gets weaker, weak gets stronger” pattern, likely linked to increased STD trends caused by spatial non‐uniformity of warming. Through a multiple regression statistical model employing dominance analysis, we find that climate factors, including both mean climate and climate variability, explained 19%–45% of the variance in provincial rice yield anomalies, with up to 13% of the explained variance attributable to spring climate factors related to temperature variability. This study underscores the critical role of spring temperature variability in climate resilience, highlights the urgent need to enhance the adaptability of agricultural systems to extreme climate events.

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Corrigendum to “Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella)” [Aquaculture Volume 598, 15 March 2025, 742053] - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Lactoferrin in health and disease: A review of its bioavailability and evidence-based benefits across study models - Zhang Jin Ng; Mohamad Fikri Addeen bin Md Daud; Karen Ong Bee Lian; Suguna Migeemanathan; Goh Kar Shin; Thavan Raj Shunmugham; Joshua Chew Thian Hee; Tang Hock Wei; Kong Yee Ling; Nurhazwani Sa'aid; Teoh Jia Thong; Foo Huey Ci; et al. (Trends in Food Science & Technology, 2025)

Developing effective intervention strategies to improve public participation in household waste recycling program: A data-driven agent-based behavior analysis approach - Yan Xu; Xinzhu Wu; Meihuan Tang; Chung-Hsing Yeh; Ling Zhang (Sustainable Cities and Society, 2025)

Degradation of o-DCB and dioxins by MnCe catalysts prepared via the mechanochemical method - Fan Yao; Yaqi Peng; Zhiyuan Gong; Ling Wang; Hongxian Li; Qi Liu; Guanjie Wang; Minghui Tang; Ang Cao; Shengyong Lu (Journal of Environmental Chemical Engineering, 2025)

Au-modified Cu2O with CO-enriched active sites for tandem catalysis of CO2 deep-reduction to C2H4 - Ji-song Yan; Wei Qiu; Hao Liu; Qing-shan Wang; Ling-qi Yu; Sheng-hui Guo; Rui-tang Guo (Journal of Environmental Chemical Engineering, 2025)

Exploring the effects of fermentation time and the addition of paraprobiotic strain K-1 on the physicochemical, chemical, and antioxidant properties of black and green tea kombuchas sweetened with different sugars - Yee Lin Lau; Pei Ling Tang (International Journal of Gastronomy and Food Science, 2025)

The effect of catalyst preparation methods on biomass hydrothermal liquefaction: Exploring cleaner and more efficient pathways for catalytic hydrothermal liquefaction of biomass - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Si-hao Ling; Fu-xiang Yang; Shun-guo Wang (Fuel, 2025)

Mahua oil fraction: A sustainable and functional 1,3-dipalmitoyl-2-oleoylglycerol (POS)-enriched cocoa butter equivalent for chocolate production - R.C.N. Thilakarathna; Lee Fong Siow; Teck-Kim Tang; Ling-Zhi Cheong; Yee-Ying Lee (Food Chemistry, 2025)

Nitrogen‑phosphorus responses and Vis/NIR prediction in fresh tea leaves - Qing Luo; Ting Tang; Yuxin Duan; Junlin Li; Caijin Ling; Ting Gao; Weibin Wu (Food Chemistry, 2025)

DSSAT modeling of oilseed flax (Linum usitatissimum L.): Sensitivity analysis of yield to weather variability and nitrogen application - Zechen Lin; Yue Li; Gerrit Hoogenboom; Yuhong Gao; Bing Wu; Ling Wu; Lili Wu; Hui Zhou; Bin Yan; Peina Lu; Jie Tang; Shunchang Su; et al. (Field Crops Research, 2025)

Species-specific bioaccumulation and biotransformation of two novel brominated flame retardants in fish: Insights from isotope fractionation - Ling Mo; Guang-Yu Liao; Bin Tang; Cheng-Zhong Fu; Dong-Jing Zhou; Dong-Wei Du; Wei-Keng Luo; Rong-Fa Xu; Ming-Zhong Ren; Jing Zheng (Environmental Research, 2025)

Microbial mechanism and CO2 emission from coastal saline soil: The role of corn stover and nutrient additions - Qiao Xu; Ling Zhang; Yingdong Zhao; Caixian Tang; Yinjuan Li; Meiling Xu; Xiaozhi Wang (Environmental Research, 2025)

The effect and mechanisms of nano cerium dioxide (Nano-CeO2) on cardiovascular development in zebrafish (Danio rerio) - Yiyun Liu; Yan-Ling Liao; Jin-Xia Wang; Bao-Fu Zhang; Qi-Ping Tang; Yuan Ding; Si-Jia Zuo; Qin-Hong Zhou; De-Sheng Pei (Environmental Pollution, 2025)

Constructing metal-site isolation in phosphate-modified Sn-doped LaMnO3 for inhibiting the generation of toxic by-products in catalytic combustion of Cl-VOCs - Ling Ding; Ningjie Fang; Qiongyue Zhang; Ben Fan; Haopeng Tang; Kunming Huang; Yinghao Chu (Chemical Engineering Journal, 2025)

An ultrafast dual-channel ratiometric fluorescence probe based on functionalized N-GQDs for dynamic monitoring of salicylic acid in plants - Hou-Yun Huang; A-ling Tang; Feng Gao; Shuai Tan; Zhi-Min Rao; Li-Wei Liu; Shi-Tao Liu; Xiang Zhou; Lin-Lin Yang; Song Yang (Chemical Engineering Journal, 2025)

Integrating Bulk RNA and Single-Cell Sequencing Data Unveils Efferocytosis Patterns and ceRNA Network in Ischemic Stroke - Jing Yuan; Yu-sha Liao; Tie-chun Zhang; Yu-qi Tang; Pei Yu; Ya-ning Liu; Ding-jun Cai; Shu-guang Yu; Ling Zhao (Translational Stroke Research, 2025)

Seropositive Rate and Associated Factors of Schistosomiasis in Hunan Province, China: A Three-Year Cross-Sectional Survey - Lingqi Xu; Yu Zhou; Ling Tang; Benjiao Hu; Liyun Zhu; Yanfeng Gong; Liang Shi; Junhui Huang; Jiamin Wang; Ning Xu; Yue Chen; Qingwu Jiang; et al. (Acta Parasitologica, 2025)

Comprehensive assessment of chemical and microbial inducers for coral larval settlement across diverse coral species - Huiming Sun; Qingsong Yang; Junde Dong; Jie Li; Chang Chen; Xiaoyu Tang; Ying Zhang; Juan Ling (Frontiers in Marine Science, 2025)
Introduction Coral restoration efforts increasingly focus on enhancing larval settlement and post-settlement survival. However, the species-specific efficacy of different settlement inducers remains inadequately understood, limiting optimization of restoration protocols. Methods This study systematically assessed the effectiveness of three settlement inducers—Crustose coralline algae (CCA), Chemical (CaCl 2 ), and Microbial ( Metabacillus sp. cB07)—across seven coral species, including both brooders and broadcast spawners. Larvae were exposed to gradient concentrations of each inducer to determine optimal concentrations and treatment durations. Effects on larval survivorship, metamorphosis, and settlement were measured. Post-settlement recruits treated with optimized procedures were further evaluated for metabolic rates, morphology, survival, and growth. Results Optimal inducer concentrations and treatment durations varied significantly among coral species, with CaCl 2 (10–60 mmol/L) and cB07 (3 × 10 6 –3 × 10 7 cfu/mL) showing broad-spectrum activity comparable to CCA. CCA induced the highest settlement rates (43.3%–93.3%) within 1–2 days, CaCl 2 showed moderate induction (23.3%–60.3%) within 0.5–4 days, and cB07 exhibited similar efficacy (26.7%–60.0%) within 2–4 days. Biological effects differed: CaCl 2 accelerated metamorphosis but lowered survival in sensitive species, while cB07 delayed metamorphosis and suppressed respiratory rates, indicating higher toxicity. Post-settlement, recruits induced by CCA and CaCl 2 had higher survival and calcification rates than those induced by cB07. Discussion These findings underscore the necessity of tailoring settlement inducer protocols to the species-specific life histories and physiological responses of corals. Integrating metabolic and ecological insights offers practical guidelines to enhance coral restoration success amid growing environmental pressures.

Transepithelial Transport of Hemp Protein-Derived Bioactive Peptide Trp–Tyr–Thr (WYT) in Human Caco-2 Cell Monolayers - Ping Wei; Dongning Ling; Yayuan Tang; Zhonglin Deng; Zhen Wei; Guoming Liu (International Journal of Peptide Research and Therapeutics, 2025)

Two new sesquiterpene glycosides from the stems of Dendrobium henanense and their anti-inflammatory activity - Si-Yu Wu; Hui-Yang Jie; De-Ling Wu; Shi-Hui Qin; Xu Tang; Ren-Zhong Wang; Feng-Qing Xu (Natural Product Research, 2025)

Integrated volatile metabolomics and transcriptomics provide insights into the formation of characteristic flavor in gynogenetic grass carp and its offspring - Jinhai Bai; Yan Tang; Xinyi Deng; Zhengkun Liu; Siyang Li; Enkui Hu; Ling Xiong; Wanjing Peng; Xu Huang; Chongqing Wang; Xidan Xu; Xiaowei Xu; et al. (Aquaculture, 2025)

Probabilistic demand models and fragility analysis of railway embankments subjected to multi-pulse ground motions - Pan SI; Liang TANG; Shuang TIAN; Yanfang LIU; Xianzhang LING (Transportation Geotechnics, 2025)

Assessing on-orbit radiometric performance of SDGSAT-1 MII for turbid water remote sensing - Wenkai Li; Shilin Tang; Liqiao Tian; Hongmei Zhao; Haibin Ye; Wendi Zheng; Yupeng Liu; Ling Sun (Remote Sensing of Environment, 2025)

Surface passivated 3D halide perovskite single crystal by 2D perovskite towards high performance soft X-ray detection and gamma-ray spectrum - Yan Xiong; Min Li; Shunsheng Yuan; Yuting Liu; Tong Jin; Jincong Pang; Sihao Xia; Mingquan Liao; Lingling Liu; Lingfeng Wu; Kuan Yew Cheong; Huayang Yu; et al. (Chemical Engineering Journal, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

ABT263 Ameliorates Cellular Senescence, Aβ-Dependent Pathology and Cognitive Decline in Aged APP/PS1 Mice via Regulating PI3K/AKT/GSK-3β Pathways - Zhi Tang; Xiao-Ling Wang; Yu-Xin Deng; Yan Xiao; Jian-wei Xu; Li Wang; Xiao-Lan Qi (Cell Biochemistry and Biophysics, 2025)

Research on Variable Circulation Design Method and Internal Flow Characteristic of the Axial Flow Pump - Xuewei Yu; Qili Gan; Zifan Ling; Jiahui Gong; Jiajia Tang; Lijian Shi (Journal of Marine Science and Engineering, 2025)
To investigate the influence of circulation distribution on axial-flow pump performance, this study integrates numerical simulation and theoretical analysis methods, establishing a simulation framework based on MATLAB and CFX. By adjusting the circulation distribution function from the hub to the tip of the impeller, various design models were constructed. Three-dimensional parametric modeling of the blades was achieved through MATLAB programming, generating key parameters such as blade profile coordinates. Subsequently, the geometric data were imported into CFX to establish a full-flow passage numerical model. The simulation employed the RANS equations with the k-ε turbulence model to analyze flow field characteristics and hydraulic performance under different circulation schemes. Numerical results indicate that under identical circulation distributions, the head–flow curve exhibits a monotonically decreasing trend, while the efficiency curve demonstrates a distinct single-peak characteristic. Notably, under specific design conditions, variations in design parameters can shift the best efficiency point while simultaneously improving efficiency. Cavitation performance analysis reveals that as the hub-to-tip ratio increases, the velocity circulation initially rises rapidly before gradually stabilizing. This distribution pattern effectively optimizes the pressure gradient at the impeller outlet, thereby significantly enhancing cavitation resistance across a wide operational range. The proposed circulation control methodology provides critical theoretical support and engineering guidance for the hydrodynamic optimization of low-head axial flow pumps.

Combined toxicity evaluation of polystyrene nanoplastics and Nano-ZnO of distinctive morphology on human lung epithelial cells - Henghui Li; Simin Tang; Xiaoyu Jia; Xinyi Zhu; Ling Cai; Mingxiu Duan; Shaozhuo Wang; Huijun Jiang; MingHui Ji; Shoulin Wang; Jin Chen (Science of The Total Environment, 2025)

10Be records of the Matuyama-Brunhes polarity reversal in the northeastern Chinese loess Plateau - Ling Tang; Weijian Zhou; Xisheng Wang; Feng Xian; Xianghui Kong; Yajuan Du; Jie Zhou; Guoqing Zhao; Yunchong Fu; Ning Chen (Quaternary Science Reviews, 2025)

Dynamic analysis of fungal community and metabolome associated with postharvest diseases in banana peel under natural condition - Ping Yi; Ming Zhao; Fang Huang; Li Li; Jian Sun; Lihong Xie; Dongning Ling; Jiemin Li; Min Huang; Ting Gan; Yayuan Tang; Changbao Li; et al. (Postharvest Biology and Technology, 2025)

Path planning of USV in confined waters based on improved A ∗ and DWA fusion algorithm - Jiadong Zhang; Hongjie Ling; Zhihao Tang; Wandi Song; Anqi Lu (Ocean Engineering, 2025)

Complete genome sequence of Alteromonas marina OM2201, a marine bacterium degrading Ulva prolifera polysaccharides isolated from surface of the Yellow Sea - Shi-Ning Cai; Hai-Xia Zhu; Zhi-Gang Tang; Xue-Yun Geng; Mei-Ling Sun (Marine Genomics, 2025)

Activation of peroxymonosulfate via g-C3N4/CeO2 heterojunction for efficient degradation of nitenpyram under visible light - Fanqi Yi; Wenbo Li; Ling Li; Zhanpeng Zhou; Rongdi Tang; Chunxia Ding; Yaocheng Deng; Daoxin Gong (Journal of Environmental Chemical Engineering, 2025)

Comparative analysis of three extraction methods for ginger leaf polysaccharide: Chemical composition, antioxidant activity, and hypolipidemic effects - Zhong-hao Zhang; Zhong-hua Zhao; Tian-yi Cao; Cai-rong Yang; Zi-zhong Tang; Shi-ling Feng; Shu Yuan; Sheng-lin Hu; Ming Yuan (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

A magnetic nanoreactor with microenvironment regulation capability for targeted and enhanced tumor chemodynamic therapy - Xia-Nan Li; Qin-Ying Tang; Meng-Cheng Tang; Hai-Rui Deng; Kang Hu; Ling-Feng Pan; Shi-Bo Wang; Bin Li; Xiang-Dong Kong (Chemical Engineering Journal, 2025)

The first morphological and molecular identification of Quilonia sp. (Nematoda: Strongylidae) from wild Asian elephant (Elephas maximus) in China - Jieyao Zhu; Mingpeng Hou; Shaoyun Zhang; Xiaoxia Yan; Ling Tang (Veterinary Research Communications, 2025)

Physiological and transcriptome sequencing analysis of exogenous ABA to regulate maturation of Korean pine somatic embryos - Shuoran Tang; Ling Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Identification of male-specific molecular markers under the low-quality and non-chromosome-level genome revalidated the male heterogamety in bullfrog Aquarara catesbeiana - Yanzhe Wang; Guodong Wang; Lili Zhang; Jingyan Tang; Ling Wang; Chunxiao Zhang; Guiling Zhang; Hui Ge (Aquaculture International, 2025)

Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella) - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

The key role of tyrosinase in color variation of the autotetraploid Carassius auratus - Xi-Dan Xu; Wan-Jing Peng; Yue Zhou; Chong-Qing Wang; Kun Zhang; Xu Huang; Xiao-Wei Xu; Jin-Hai Bai; Ling Xiong; Zheng-Kun Liu; Xin-Yi Deng; Yan Tang; et al. (Aquaculture, 2025)

Effects of karst vegetation-soil-rock composite structure on soil and water flow/leakage processes and driving factors at the micro-plot scale - Rui Li; Jun Jing; Zhengyi Tang; Ling Xiong (Soil and Tillage Research, 2025)

Complete genome sequence of Vreelandella sp. SM1641, a marine exopolysaccharide-producing bacterium isolated from deep-sea hydrothermal sediment of the Southwest Indian Ocean - Hai-Xia Zhu; Zhi-Gang Tang; Shi-Ning Cai; Jun-Hui Cheng; Peng Wang; Mei-Ling Sun (Marine Genomics, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Development of cinnamaldehyde/aminated gelatin film as pH-responsive controlled-release packaging for cherry preservation: Effects of CO2 and humidity in the microenvironment - Xianhui Tang; Meiyan Zhu; Ling Zhang; Liang Zhu (Food Packaging and Shelf Life, 2025)

Analyzing spatial structure and low-carbon development considering criteria interactions: Evidence from Chinese urban agglomerations - Qianya Pian; Ling Zhang; Ou Tang; Shiqi Wang (Environmental Impact Assessment Review, 2025)

miR-9a and miR-10482-5p regulate the expression of chitin synthase and chitinase genes, enhancing lufenuron tolerance in Spodoptera frugiperda - Shanshan Ling; Zhimin Guo; Mengyan Wu; Jiahui Tang; Haixiang Lv; Jianhong Li; Kangsheng Ma (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Exploration SMX degradation mechanism triggered by copper-loaded and fly ash based geopolymer - Lingling Zhang; Yanlin Wang; Bingyang He; Zian Tang; Xiaohuan Jing; Xiao Ling (Chemical Engineering Journal, 2025)

Dietary lysine deficiency causes intestinal immune dysfunction partially via Janus kinases (JAKs)/signal transducers and activators of transcription (STATs) signalling pathways of on-growing grass carp (Ctenopharyngodon idella) - Yangyang Hu; Lin Feng; Weidan Jiang; Pei Wu; Yang Liu; Shengyao Kuang; Ling Tang; Lu Zhang; Haifeng Mi; Xiaoqiu Zhou (Animal Feed Science and Technology, 2025)

Recent advances in bioinspired multienzyme engineering for food applications - Xianhan Chen; Yujin Chen; Dandan Tang; Mengyu Li; Yuting Lu; Yi Cao; Quanyu Zhao; Shuai Jiang; Wei Liu; Ling Jiang (Trends in Food Science & Technology, 2025)

Acidosis induces autophagic cell death through ASIC1-mediated Akt/mTOR signaling in HT22 neurons - Miao Guo; Ming-Yue Qiu; Lin Zeng; Ya-Xiong Nie; Ya-Ling Tang; Yan Luo; Hong-Feng Gu (Toxicology, 2025)

Chinese loess 10Be records for the Jaramillo polarity subchron - Weijian Zhou; Yajuan Du; Xiaolong Zhou; Xianghui Kong; Feng Xian; Ling Tang; Jie Zhou; Guoqing Zhao; Yunchong Fu; Mengyu Zang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Binary response of runoff generation and erosion processes to karst vegetation-soil-rock structure and its hydrodynamic mechanisms - Jun Jing; Rui Li; Ling Xiong; Zhengyi Tang (Journal of Hydrology, 2025)

Chloroplast-localized transporter OsNTP1 mediates cadmium transport from root to shoot and sugar metabolism in rice - Jingxin Wang; Lingwei Yang; Bo Xu; Ruijie Cao; Sidra Charagh; Suozhen Hui; Liang Zhou; Yuanyuan Zhang; Yujuan Chen; Zhonghua Sheng; Guiai Jiao; Gaoneng Shao; et al. (Journal of Hazardous Materials, 2025)

Hydroxylation and N-doping synergistically enhance the CO2 adsorption and regeneration of amine-loaded mesoporous carbon in flue gas - Hongxian Li; Minghui Tang; Ling Wang; Qi Liu; Fan Yao; Zhiyuan Gong; Shengyong Lu (Journal of Environmental Chemical Engineering, 2025)

Application of the non-linear three-component model for simulating accelerated creep behavior of polymer-alloy geocell sheets - Yang Zhao; Hanqing Xiao; Ling Chen; Penghui Chen; Zheng Lu; Chuxuan Tang; Hailin Yao (Geotextiles and Geomembranes, 2025)

Improving physicochemical properties and gel formation mechanism of nutty plant-based yogurt with Tremella fuciformis polysaccharides - Ling Lin; Xiaoqing Qian; Junyu He; Yuting Shao; Yao Zeng; Mengxin Tang; Yong Fang; Xiaoyi Jiang; Jian Ding (Food Chemistry, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

Optimized near infrared reflectance model based on preprocessing selection strategy for rapid analysis of 2-acetyl-1-pyrroline content in rice flour - Li-Hong Xie; Shao-Qing Tang; Gao-Neng Shao; Zhong-Hua Sheng; Shi-Kai Hu; Xiang-Jin Wei; Gui-Ai Jiao; Ling Wang; Pei-Song Hu (Food Control, 2025)

Presence and sources of per- and polyfluoroalkyl substances (PFASs) in the three major rivers on Hainan Island - Wang-Qing Tang; Tuan-Tuan Wang; Jiang-Wei Miao; Hua-Dong Tan; Hong-Jin Zhang; Tuan-Qi Guo; Zhong-Bing Chen; Chun-Yuan Wu; Ling Mo; Bi-Xian Mai; Sai Wang (Environmental Research, 2025)

Nanostructured MnFe2O4/MnO heterojunctions as highly-efficient bi-functional catalyst for complementary conversions of polysulfides toward robust lithium-sulfur batteries - Feiyang Teng; Ling Zhu; Jie Ma; Jingxuan Tang; Liqian Ke; Yao Tang; Jia Kang; Yonggang Huang; Xiangsi Wu; Lizhi Xiong; Qiaobao Zhang; Xianwen Wu (Chemical Engineering Journal, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

SaTDT enhanced plant tolerance to NaCl stress by modulating the levels of malic acid and citric acid in cells - Xiangyu Wei; Li Xu; Suisui Dong; Nina He; Qianqian Xi; Dan Yao; Qianqian Wang; Yue Zuo; Chen Ling; Meiting Qi; Wen Bai; Kai Han; et al. (Plant Molecular Biology, 2025)

Hydrodynamic performance of swimming fish in the wake region of a semi-cylinder - Hao Wang; Saiyu Yuan; Hongwu Tang; Carlo Gualtieri; Yuxiang Ling (Ocean Engineering, 2025)

Alkalinity enhanced hydrolysis of primary sludge for carbon source recovery and its impact on denitrification in wastewater treatment - Xiaodong Wang; Mei Huang; Shanshan Chen; Xuejun Bi; Ling Wang; Mingyue Tang; Zhen Liu; Qing Huang; Shuai Gao; Zakhar Maletskyi (Journal of Environmental Management, 2025)

Corrigendum to “Soybean glycinin impaired immune function and caused inflammation associated with PKC-ζ/NF-κb and mTORC1 signaling in the intestine of juvenile grass carp (Ctenopharyngodon idella)” [Fish and Shellfish Immunol. 106 (2020) 393–403] - Ya-Lin Zhang; Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2025)

Life-cycle environmental burdens of cultivated seaweed as blue food: The case study of Wakame and Kelp in Dalian, China - Haoyu Wu; Xiaoyang Liu; Ling Tang; Huade Zhao; Fanghua Wei; Chunsheng Liu; Guobao Song (Environmental Impact Assessment Review, 2025)

Hyaluronanized gold nanoparticles functionalized with CTX-II antibody for early diagnosis and treatment of knee osteoarthritis - Cheng Chen; Cong Tang; Kaiquan Chen; Muhai Deng; Xiangling Pu; Tao Hu; Zhiyu Chen; Ling Zhong; Yunsheng Jiang; Yang Huang (Chemical Engineering Journal, 2025)

Pyrite geochemistry and its implications for ore formation in reduced copper skarn systems: A case study of the Saibo deposit, Northwest China - Qing-Fei Sun; Ju-Xing Tang; Shun-Da Li; Qiu-Ming Pei; Xin-Hao Sun; Chuan Chen; Ling-Ling Gao; Xiao-Fei Du; Jin-Ling Xie (Chemical Geology, 2025)

Long-term performance of subway tunnels induced by the symmetrical excavation of semicircular deep foundation pits in the Northeast Region hard silty clay - Wenchong Tang; Liang Tang; Xianzhang Ling; Xiangxun Kong; Yifan Zhang (Tunnelling and Underground Space Technology, 2024)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

Prediction and pathway models for assessing soil properties influencing soil selenium enrichment and bioavailability in Aksu Prefecture, northwest China - Hui Zhai; Yunshu Zhang; Wanli Xu; Wenyu Hou; Guangmu Tang; Chunhui Ge; Huawei Shao; Haotian Gong; Yujian Wang; Yumeng Liu; Lei Pan; Li Ling (Science of The Total Environment, 2024)

QSAR models for predicting key hormesis parameters of quinolone antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Xia-Chang-Li Xu; Li-Tang Qin; Fan Jiang (Science of The Total Environment, 2024)

Bearing performance and failure mechanisms of HSCM piles in marine soft soil under lateral loads - Hang Cen; Jun-nan Zhao; Zhong-ling Zong; De-long Huang; Ding-wen Zhang; Hui-yue Wang; Ai-ping Tang (Ocean Engineering, 2024)

Relationship between root characteristics and saturated hydraulic conductivity in a grassed clayey soil - Ling-Xin Cui; Qing Cheng; Pui San So; Chao-Sheng Tang; Ben-Gang Tian; Cong-Ying Li (Journal of Hydrology, 2024)

Contribution of plastic solid components to volatile organic compounds formation during plastics combustion - Xinglei Wang; Simeng Tang; Ling Ding; Xinran Qiu; Zhenming Zhang; Li Xu; Xujun Liang; Xianfei Huang; Xuetao Guo (Journal of Hazardous Materials, 2024)

AmTPS6 promotes trehalose biosynthesis to enhance the Cd tolerance in mangrove Avicennia marina - Ling-Yu Song; Jing Li; Lu-Dan Zhang; Zhao-Yu Guo; Chao-Qun Xu; Li-Wei Jiang; Jin-Yu Liu; Ji-Cheng Wang; Qing-Hua Li; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2024)

Activated carbon-mediated arsenopyrite oxidation and arsenic immobilization: ROS formation and its role - Shuang Zhou; Xianglong Qi; Yetao Tang; Weijian Yu; Qingjun Guan; Yongjie Bu; Ling Tan; Guohua Gu (Journal of Hazardous Materials, 2024)

Co-management enhances social capital and recognition of protected area: Perspectives from indigenous rangers on the Qinghai-Tibet Plateau - Zhi Zhang; Yu Wei; Ling Tang; Zhi Wang; Xuetian Hu; Xinting Li; Yixing Bi; Baorong Huang (Journal of Environmental Management, 2024)

Recent progress of piezoelectric materials applied in photocatalytic CO2 reduction: A review - Yi-fu Liu; Rui-tang Guo; Sheng-hui Guo; Ling-qi Yu; Ji-song Yan; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Untargeted metabolomics study of mature human milk from women with and without gestational diabetes mellitus - Dan Yao; Cai Shen; Xinghe Zhang; Jiayue Tang; Jingwen Yu; Maolin Tu; Worawan Panpipat; Manat Chaijan; Hong Zhang; Xuebing Xu; Yanan Liu; Ling-Zhi Cheong (Food Chemistry, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

Fabrication of Aspergillus oryzae lipase-immobilized magnetic Cu3(PO4)2∙3H2O nanoflowers for efficient synthesis of structured phospholipids - Hua-Wei Zhang; Ke Cheng; Jing-Jing Tang; Ling-Zhi Liu; Ruo-Xuan Qin; Yi-Nuo Sun; Jiang-Hua Zhang; Da-Yong Zhou (Food Bioscience, 2024)

Sinensetin from citrus peel alleviates DSS-induced inflammation by regulating gut microbiota and serum metabolism in mice - Zuomin Hu; Zhongxing Chu; Xuke Ling; Yuchi Wu; Dandan Qin; Feiyan Yang; Xudong Yu; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

Bacteria contribute more than fungi to SOC decomposition in a paddy field under long-term free-air CO2 enrichment - Meiling Xu; Feifan Zhang; Ling Zhang; Hongze Zhang; Caixian Tang; Xiaozhi Wang; Jing Ma; Qiao Xu (European Journal of Soil Biology, 2024)

Taxonomic and functional changes in wheat rhizosphere microbiome caused by imidazoline-based herbicide and genetic modification - Farman Ali; Zhaocheng Tang; Gangao Mo; Baolong Zhang; Xitie Ling; Zeyu Qiu (Environmental Research, 2024)

Advances and hotspots of phosphorus form analysis of sediments based on different extraction methods using CiteSpace - Ruoxuan Tang; Junhong Bai; Ling Zhang; Yaqi Wang; Haizhu Liu; Jiangbao Xia (Ecohydrology & Hydrobiology, 2024)

Activating copper by creating low-coordinated copper sites for antibiotic detoxification through Electrocatalytic hydrodechlorination reaction - Xiangyi Tang; Fei Shen; Wei Fan; Jianhui Liu; Lingpiao Chen; Yinan Liu; Liang Ao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Ling Chen; Yan Jiang; et al. (Chemical Engineering Journal, 2024)

Highly selective capture of lead(II) by a barium-zinc-antimony-oxo cluster-based material: Ion-exchange pathway with single-crystal-to-single-crystal structural transformation - Wei-Yang Wen; Jia-Hua Luo; Hai-Yan Sun; Yu-Wei Ren; Lu Yang; Tian-Yu Pan; Jun-Hao Tang; Wen Ma; Jia-Ting Liu; Bing Hu; Mei-Ling Feng; Xiao-Ying Huang (Chemical Engineering Journal, 2024)

Green fabrication of hierarchical pore starch with controllable pore size and shape based on different amylose-amylopectin ratios - Ruiling Lv; Yi Chen; Jianwei Zhou; Ling Jiang; Enbo Xu; Jiangang Ling; Junyu Tang (Carbohydrate Polymers, 2024)

Hinokiflavone from Platycladi cacumen as a potent broad-spectrum inhibitor of gut microbial Loop-1 β-glucuronidases: Inhibition kinetics and molecular simulation - Yue Han; Yu-Tong Liu; Lu Chen; Hao-Fan Sun; Guang-Hao Zhu; Dong-Ning Kang; Qi Zhou; Hui Tang; Yu-Ling Yin; Jie Hou (Chemico-Biological Interactions, 2024)

Is 3D building morphology really related to land surface temperature? Insights from a new homogeneous unit - Ling Yang; Yang Chen; Yue Li; Hui Zhu; Xin Yang; Sijin Li; Guoan Tang (Building and Environment, 2024)

Regulation of Keap1-Nrf2 signaling in health and diseases - Jiang-Ling Xiao; Heng-Yuan Liu; Chen-Chen Sun; Chang-Fa Tang (Molecular Biology Reports, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

Azotosporobacter soli gen. nov., sp. nov., a novel nitrogen-fixing bacterium isolated from paddy soil - Cheng-Jie Xie; Ling Yao; Rong Tang; Shuang Han; Shang Yang; Hend Alwathnani; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2024)

Coupling coordination between financial support efficiency and carbon efficiency for resource recycling industry in China - Jing Tang; Ling Zhang; Huijun Wu; Zhanfeng Dong (Environment, Development and Sustainability, 2024)

Designing ballastless high-speed railways in frozen regions: A dynamic analysis using three-dimensional numerical modelling - Shuang Tian; Liang Tang; Xianzhang Ling; Shi Liu; Ting Li (Transportation Geotechnics, 2024)

Mirids secrete a TOPLESS targeting protein to enhance JA-mediated defense and gossypol accumulation for antagonizing cotton bollworms on cotton plants - Yu-Pei Mu; Dian-Yang Chen; Yu-Jie Liu; Ming-Yu Zhu; Xian Zhang; Yin Tang; Jia-Ling Lin; Mu-Yang Wang; Xiao-Xia Shangguan; Xiao-Ya Chen; Chengshu Wang; Ying-Bo Mao (Molecular Plant, 2024)

Classification and regression machine learning models for predicting the combined toxicity and interactions of antibiotics and fungicides mixtures - Li-Tang Qin; Jun-Yao Zhang; Qiong-Yuan Nong; Xia-Chang-Li Xu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Environmental Pollution, 2024)

Acid-assisted pretreatment for sweet elephant grass in choline chloride/glycerol DES: Experimental and mechanism study - Yining Zhang; Weizhen Xie; Weidong Li; Yue Tang; Jiali Wu; Lihui Gan; Ling-Ping Xiao; Xu Zhang; Lu Lin; Xing Tang (Chemical Engineering Journal, 2024)

Unveiling potential sex-determining genes and sex-specific markers in autotetraploid Carassius auratus - Kun Zhang; Xu Huang; Chongqing Wang; Xidan Xu; Xiaowei Xu; Xiaoping Dong; Qingwen Xiao; Jinhai Bai; Yue Zhou; Zhengkun Liu; Xinyi Deng; Yan Tang; et al. (Science China Life Sciences, 2024)

Refining urban morphology: An explainable machine learning method for estimating footprint-level building height - Yang Chen; Wenjie Sun; Ling Yang; Xin Yang; Xingyu Zhou; Xin Li; Sijin Li; Guoan Tang (Sustainable Cities and Society, 2024)

Machine learning-based predictors for maximum pile bending moment of the soil-pile-superstructure system in liquefiable soils - Liang Tang; Pan Si; Xianzhang Ling; Shuang Tian; Wanting Zhang (Ocean Engineering, 2024)

Deciphering microbial metabolic interactions and their implications for community dynamics in acid mine drainage sediments - Shao-Ming Gao; Pandeng Wang; Qi Li; Wen-Sheng Shu; Ling-Yun Tang; Zhi-Liang Lin; Jin-Tian Li; Li-Nan Huang (Journal of Hazardous Materials, 2024)

Thermal performance study of PCM embedded radiant cooling ceiling assisted by infrared-transparent silicon wafers - Riqin Nong; Ling Zhang; Xudong Tang; Xiaosong Su; You Tang (Energy and Buildings, 2024)

Piezoelectric plasma synergistic catalytic degradation of organic pollutants on BNBT/Ag composite nanofibers - Zhaowei Liu; Ziyun Luo; Ling Kang; Xi Chen; Yufei Tang; Qian Liang; Chen Tang; Kang Zhao (Desalination, 2024)

2D metal borides (MBenes): Synthesis methods for energy storage applications - Abdul Jabbar Khan; Syed Shaheen Shah; Shaukat Khan; Abdul Mateen; Bushra Iqbal; Mizna Naseem; Liang He; Yi Zhang; Yong Che; Ya Tang; Miao Xu; Ling Gao; et al. (Chemical Engineering Journal, 2024)

Excellent electrocaloric performance achieved by the high-entropy strategy - Xiaofan Sun; Cuiping Xu; Yanzhou Lu; Min Zhao; Shulin Jiao; Zheng Tang; Dong Li; Hong-Ling Cai; X.S. Wu (Chemical Engineering Journal, 2024)

Multifunctional pH-responsive hydrogel dressings based on carboxymethyl chitosan: Synthesis, characterization fostering the wound healing - Mingxin Xiong; Yu Chen; Han-Jian Hu; Hao Cheng; Wei-Xiong Li; Shipeng Tang; Xiaolong Hu; Ling-Min Lan; Hongyan Zhang; Gang-Biao Jiang (Carbohydrate Polymers, 2024)

Screening and identification of differential-expressed RNAs in thrombin-induced in vitro model of intracerebral hemorrhage - Ling Gao; Li Peng; Hong Tang; Chuang Wang; Qingsong Wang; Yujie Luo; Weiming Chen; Ying Xia (Molecular and Cellular Biochemistry, 2024)

Alleviating Coral Thermal Stress via Inoculation with Quorum Quenching Bacteria - Qingsong Yang; Bing Yang; Bin Yang; Wenqian Zhang; Xiaoyu Tang; Huiming Sun; Yanying Zhang; Jie Li; Juan Ling; Junde Dong (Marine Biotechnology, 2024)

Phenotypic and genetic effect of carotid intima-media thickness on the risk of stroke - Wenqiang Zhang; Jingwei Zhu; Xuan Wu; Tianle Feng; Wei Liao; Xuan Li; Jianci Chen; Li Zhang; Chenghan Xiao; Huijie Cui; Chao Yang; Peijing Yan; et al. (Human Genetics, 2024)

High mantle helium flux unveils active mantle melting beneath the cathaysia block, south China - Shuai Wang; Xuelian Huang; Sijia Wang; Min Zhang; Ling Tang; Shihua Qi (Applied Geochemistry, 2024)

Nontarget analysis and characterization of p-phenylenediamine-quinones and -phenols in tire rubbers by LC-HRMS and chemical species-specific algorithm - Caiming Tang; Yizhe Zhu; Ruifen Zheng; Ling Liu; Yan-Hong Zeng; Xiao-Jun Luo; Bi-Xian Mai (Analytica Chimica Acta, 2024)

Simultaneous removal of Cd(II) and phosphate by nanoscale zero-valent iron from solution: Co-sorption and implication of corrosion - Haoyang Fu; Jie Sheng; Chenliu Tang; Wei-xian Zhang; Lan Ling (Chemosphere, 2024)

Eco-friendly, highly interpenetrated and slightly swollen pHEMA hydrogel foam for durable underwater superoleophobicity and emulsion separation - Jinjin Zeng; Yi Zhu; Yin Tian; Kexin Tang; Mengwen Duan; Yuanpeng Wang; Ling Lin; Ning He (Chemosphere, 2024)

Immunosuppressive alkaloids from Narcissus tazetta subsp. Chinensis and the mechanism of (+)-narciclasine in vitro and in vivo - Wen-Ling Wang; Xiu-Yin Wu; Xing-Yan Luo; Yu-Qin Tang; Jia Cui; Xin-Yue Huang; Yu-Chen Jiang; Yang Liu; Li-Mei Li (Phytochemistry, 2024)

Hydrothermal enrichment of rare earth elements in the Lower Permian Lijiatian bauxite deposit, southern China - Kunyue Ling; Yongzhen Long; Suxiong Guo; Yanwen Tang; Zhihui Dai; Hanjie Wen (Journal of Geochemical Exploration, 2024)

Improving photochemical indicators for attributing ozone sensitivities in source apportionment analysis - Xiaohui Du; Wei Tang; Zhongzhi Zhang; Yang Yu; Yang Li; Ling Huang; Greg Yarwood; Fan Meng (Journal of Environmental Sciences, 2024)

Efficient catalysis and products regulation of methane dry reforming under mild temperature conditions using novel high-entropy catalyst - Xu Ma; Wei-Wei Yang; Xin-Yuan Tang; Ya-Ling He (Fuel, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Experimental and DFT study of Na4SiO4 doped with oxysalts for high-temperature CO2 capture - Changjian Ling; Xin Luo; Zirui Wang; Zhongfeng Tang (Chemical Engineering Journal, 2024)

Kurarinone, a flavonoid from Radix Sophorae Flavescentis, inhibits RANKL-induced osteoclastogenesis in mouse bone marrow–derived monocyte/macrophages - Ling Long; Hao Luo; Yi Wang; Jiaxiang Gu; Jiachao Xiong; Xiaokai Tang; Hao Lv; Faxin Zhou; Kai Cao; Sijian Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Epidemiologic trends and changes in humoral immunity and lymphocyte subsets levels among hospitalized children with Mycoplasma pneumoniae infection during 2019–2023 - Linyan Tang; Kaiwen Zheng; Lanlan Ma; Ling Chen; Yuling Zhao; Li Li; Ke Wang; Jing Zhang; Xing Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Characterization and source apportionment of pharmaceuticals in surface water of the Yangtze Estuary and adjacent sea - Chunzhao Chen; Jian Tang; Fei Li; Rui Xue; Yihua Xiao; Ling Chen; Gang Yu (Environmental Science and Pollution Research, 2024)

Activation of GPR30 Ameliorates Cerebral Ischemia–Reperfusion Injury by Suppressing Ferroptosis Through Nrf2/GPX4 Signaling Pathway - Yong-qiang Zhang; Ting Sun; Zhen Zhao; Jing Fu; Le Yang; Yuan Xu; Jing-feng Zhao; Xiu-ling Tang; An Liu; Ming-gao Zhao (NeuroMolecular Medicine, 2024)

Deciphering the pathogenic risks of microplastics as emerging particulate organic matter in aquatic ecosystem - Ling-Zi Yin; Xiao-Qing Luo; Jia-Ling Li; Zetao Liu; Li Duan; Qi-Qi Deng; Chen Chen; Shaojun Tang; Wen-Jun Li; Pandeng Wang (Journal of Hazardous Materials, 2024)

Tourmaline/pyrite dual mineral photocatalysis with a powerful surface electric field for efficient antibiotic removal - Xiangwei Tang; Rongdi Tang; Wenbo Li; Xiao Li; Jin Zheng; Ling Li; Zhanpeng Zhou; Fanqi Yi; Yaocheng Deng; Daoxin Gong (Journal of Environmental Management, 2024)

Electrode structural effects on the mechanism of high-voltage pulse rock breaking - Xiaohua Zhu; Wuji Tang; Weiji Liu; Ling He; Youjian Zhang (Journal of Applied Geophysics, 2024)

Rapid non-destructive evaluation of texture properties changes in crispy tilapia during crispiness using hyperspectral imaging and data fusion - Shuqi Tang; Ling Zhang; Xingguo Tian; Manni Zheng; Zihao Su; Nan Zhong (Food Control, 2024)

A novel long non-coding RNA linc-93.2 participates in bisphenol induced oxidative stress and macrophage polarization in red common carp (Cyprinus carpio) - Ting Yu; Qing Wei; Yiran Tang; Ling Cai; Bei Chen; Ming Yang (Fish & Shellfish Immunology, 2024)

Exploring the novel benefits of leucine: Protecting nitrite-induced liver damage in sub-adult grass carp (Ctenopharyngodon idella) through regulating mitochondria quality control - Lu-Lu Zhen; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Role of NiO in wide-bandgap perovskite solar cells based on self-assembled monolayers - Afei Zhang; Mingyu Li; Chong Dong; Wenjiang Ye; Yongxin Zhu; Jiakuan Yang; Long Hu; Xiong Li; Ling Xu; Ying Zhou; Haisheng Song; Chao Chen; et al. (Chemical Engineering Journal, 2024)

Enhanced mechanical and thermal properties of expanded graphite/ice phase change materials through in-situ polymerization of sodium polyacrylate in cold chain logistics - Lei Tang; Ziye Ling; Zhengguo Zhang; Xiaoming Fang (Chemical Engineering Journal, 2024)

Acoustic comfort in educational buildings: An integrative review and new directions for future research - Dadi Zhang; Ling-Tim Wong; Kwok-Wai Mui; Shiu-Keung Tang (Building and Environment, 2024)

Simplified Calculation of Earthquake Energy Transfer of Different Pipe Supports Inside Utility Tunnel at Horizontal Non-Homogeneous Field - De-long Huang; Hang Cen; Jin Wang; Hui-yue Wang; Qiang Liu; Zhong-ling Zong; Ai-ping Tang; Song-ling Xue (Geotechnical and Geological Engineering, 2024)

Preparation of (S)-epichlorohydrin using a novel halohydrin dehalogenase by selective conformation adjustment - Xiao-Jian Zhang; Meng-Yu Huang; Xin-Xin Peng; Min Cao; Han-Zhong Deng; Yi-Chuan Gong; Xiao-Ling Tang; Zhi-Qiang Liu; Yu-Guo Zheng (Biotechnology Letters, 2024)

Taurine prevented the decline of fillet quality and muscle antioxidant capacity in on-growing grass carp (Ctenopharyngodon idella) fed non-fishmeal diet - Shun-Shi Sun; Liang-Chao Yan; Lin Feng; Wei-Dan Jiang; Yang Liu; Ling Tang; Pei Wu; Xiao-Qiu Zhou (Aquaculture, 2024)

Fabrication of bimetallic Ag@ZnO nanocomposite and its anti-cancer activity on cervical cancer via impeding PI3K/AKT/mTOR pathway - Qinghua Yin; Qiang Zhou; Jianbing Hu; Jie Weng; Songlian Liu; Leilan Yin; Ling Long; Yajun Tong; Kewei Tang; Site Bai; Ludi Ou (Journal of Trace Elements in Medicine and Biology, 2024)

Proteomic analysis of milk fat globule membrane proteins in mature human milk of women with and without gestational diabetes mellitus - Dan Yao; Cai Shen; Jingwen Yu; Jiayue Tang; Hong Zhang; Xuebing Xu; Maolin Tu; Ling-Zhi Cheong (Food Chemistry, 2024)

Electric field driven tourmaline/hematite dual mineral photocatalysis for efficient antibiotic removal - Xiangwei Tang; Rongdi Tang; Yaocheng Deng; Xiao Li; Ling Li; Zhanpeng Zhou; Wenbo Li; Meng Yuan; Rucheng Xie; Daoxin Gong (Environmental Pollution, 2024)

Study of the dynamic interactions between helix-stiffened cement mixing piles and soft soil under oblique incidence of SV waves in arbitrary space - Hang Cen; Zhong-ling Zong; De-long Huang; Hui-yue Wang; Xiao-xuan Zhuang; Zi-yuan Huang; Ai-ping Tang (Computers and Geotechnics, 2024)

Preparation of inorganic salt particles by reactive crystallization in an annular swirling flow reactor - Wei-Wei Wang; Wang-Ze Xiao; Xiang Li; Gang Luo; Yan-Ling Tang; Zi-Bin Huang; Zhen-Min Cheng (Chemical Engineering Journal, 2024)

Fe-Doped CoNi layered hydrogencarbonate hierarchical Nano-Array assisted growth of ZIF-67 as an efficient OER/UOR bifunctional catalyst reaction for Overall Urea-Water electrolysis - Hongwen Tang; Zeyu Sun; Shuyan Fan; Siwen Feng; Ling Li; Ling Fang; Cuijuan Wang (Chemical Engineering Journal, 2024)

Genome-wide association studies dissect low-phosphorus stress response genes underling field and seedling traits in maize - Bowen Luo; Guidi Zhang; Ting Yu; Chong Zhang; Guohui Yang; Xianfu Luo; Shuhao Zhang; Jianyong Guo; Haiying Zhang; Hao Zheng; Zirui Tang; Qile Li; et al. (Theoretical and Applied Genetics, 2024)

Exploring the phosphorus–starch content balance mechanisms in maize grains using GWAS population and transcriptome data - Bowen Luo; Haiying Zhang; Zheng Han; Xiao Zhang; Jianyong Guo; Shuhao Zhang; Xianfu Luo; Jin Zhao; Wei Wang; Guohui Yang; Chong Zhang; Jing Li; et al. (Theoretical and Applied Genetics, 2024)

Validating the use of ROS-scavenging bacteria as probiotics to increase coral resilience to thermal stress - Xiaoyu Tang; Qingsong Yang; Ying Zhang; Hanzhang Wang; Juan Ling; Haiyan Sun; Junde Dong; Yanying Zhang (Journal of Oceanology and Limnology, 2024)

Chronic Fluoride Exposure Induces Ovarian Dysfunction and Potential Association with Premature Ovarian Failure in Female Rats - Xiaoke Tang; Hongjuan Li; Yali Wang; Li Zeng; Ling Long; Yajun Qu; Hui Yang; Xiaolin Zhang; Yanmin Li; Yanni Yu; Qi Zhou; Man Luo (Biological Trace Element Research, 2024)

ResoNet: Robust and Explainable ENSO Forecasts with Hybrid Convolution and Transformer Networks - Pumeng Lyu; Tao Tang; Fenghua Ling; Jing-Jia Luo; Niklas Boers; Wanli Ouyang; Lei Bai (Advances in Atmospheric Sciences, 2024)

Assessment of benthic ecological status and heavy metal contamination in an estuarine intertidal mudflat in the Northern Bohai Sea - Ang Li; Jiaqi Li; Fang Liu; Ling Zhu; Lulei Liu; Suyan Xue; Meng Zhang; Yuze Tang; Yuze Mao (Marine Pollution Bulletin, 2024)

Physicochemical characteristics of grease-trap wastewater with different potential mechanisms of FOG solid formation, separation, and accumulation inside grease traps - Ling Ying Tang; Ngie Hing Wong; Thion Am Chieng; Alex Kwong Jun Kiu; Chung Siung Choo; Yali Li; Chin Ping Tan; Abu Zahrim Yaser; Deni Shidqi Khaerudini; Gui Hua Chen; Jaka Sunarso (Water Research, 2024)

Application of fermented Chinese herbal medicines in food and medicine field: From an antioxidant perspective - Yuzhu Zhang; Jing Zhang; Jingwen Yan; Xinrui Qi; Yuehan Wang; Zitong Zheng; Jianqi Liang; Jitao Ling; Yixuan Chen; Xiaoyi Tang; Xinxing Zeng; Peng Yu; et al. (Trends in Food Science & Technology, 2024)

Exposure to volatile organic compounds and mortality in US adults: A population-based prospective cohort study - Xiaobing Feng; Feng Qiu; Ling Zheng; Yue Zhang; Yuji Wang; Min Wang; Han Xia; Bingrong Tang; Chunxiang Yan; Ruyi Liang (Science of The Total Environment, 2024)

Genomic analysis of Cobetia sp. D5 reveals its role in marine sulfur cycling - Xiao-Mei Geng; Shi-Ning Cai; Hai-Xia Zhu; Zhi-Gang Tang; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Hai-Yan Cao; Peng Wang; Mei-Ling Sun (Marine Genomics, 2024)

Puissant synergistic effect between g-C3N4 and MIL-100(Fe) for highly stable enhanced activation of H2O2 to degrade antibiotic tetracycline hydrochloride - Qingkai Shi; Naif Abdullah Al-Dhabi; Min Cheng; Yang Liu; Jun Wang; Guangfu Wang; Gaoxia Zhang; Ling Li; Li Du; Hongda Liu; Suzhao Yang; Wangwang Tang (Journal of Environmental Chemical Engineering, 2024)

Submerged plant-biochar composite system exhibits effective control over residual organic pollutants in the benthic organisms of aquaculture ponds - Juan-Ying Li; Siyu Yao; Zilong Mo; Yabo Miao; Yiqin Chen; Wenhui He; Ling Jin; Wenzhong Tang (Environmental Pollution, 2024)

Adding fine woody debris accelerates the turnover of soil carbon pool in high-latitude urban plantations in China - Honglin Xing; Hao Zhang; Guoru Tang; Tianhe Yuan; Hailong Shen; Ling Yang (Journal of Soils and Sediments, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Methyl contributes to the directed phosphorus doping of g-C3N4: pH-dependent selective reactive oxygen species enable customized degradation of organic pollutants - Zhanpeng Zhou; Hao Zeng; Ling Li; Rongdi Tang; Chengyang Feng; Daoxin Gong; Ying Huang; Yaocheng Deng (Water Research, 2024)

A hybrid method for assessing the city emission status toward carbon peak - Jianhui Ruan; Ziyu Qin; Shuangyue Qian; Mingyu Li; Min Jia; Li Zhang; Zhe Zhang; Shuying Zhu; Hanying Jiang; Bofeng Cai; Shouyang Wang; Ling Tang (Urban Climate, 2024)

Toxic interactions at the physiological and biochemical levels of green algae under stress of mixtures of three azole fungicides - Li-Tang Qin; Yu-Xue Lei; Min Liu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Science of The Total Environment, 2024)

Dissolved organic matter influences the indigenous bacterial community and polycyclic aromatic hydrocarbons biodegradation in soils - Lei Tang; Jiayi Yan; Xian Zhou; Jian Wang; Yanzheng Gao; Ahmed Mosa; Bozena Czech; Patryk Oleszczuk; Wanting Ling (Science of The Total Environment, 2024)

Experimental and numerical investigation on the response characteristic of the crane-wharf structure in liquefiable site - Yi Zhang; Shuang Tian; Liang Tang; Xianzhang Ling (Ocean Engineering, 2024)

A novel remediation strategy of mixed calcium peroxide and degrading bacteria for polycyclic aromatic hydrocarbon contaminated water - Lei Tang; Yulong Sun; Wenyi Lu; Xuwen Chen; Ahmed Mosa; Tatiana Minkina; Yanzheng Gao; Wanting Ling (Journal of Hazardous Materials, 2024)

Remediation potential of an immobilized microbial consortium with corn straw as a carrier in polycyclic aromatic hydrocarbons contaminated soil - Xian Zhou; Yuhao Sun; Tingting Wang; Lei Tang; Wanting Ling; Ahmed Mosa; Jian Wang; Yanzheng Gao (Journal of Hazardous Materials, 2024)

Designing regional joint prevention and control schemes of PM2.5 based on source apportionment of chemical transport model: A case study of a heavy pollution episode - Yangjun Wang; Miao Ning; Qingfang Su; Lijuan Wang; Sen Jiang; Yueyi Feng; Weiling Wu; Qian Tang; Shiyu Hou; Jinting Bian; Ling Huang; Guibin Lu; et al. (Journal of Cleaner Production, 2024)

Iron additions accelerate carbon loss from drained soil but promote carbon accumulation in waterlogged soil of Zoige plateau peatland - Ruixuan Li; Hanqing Luo; Ling Luo; Yan He; Shihuai Deng; Chengyi Huang; Ouping Deng; Xiaoyan Tang (International Biodeterioration & Biodegradation, 2024)

Organogel assisted salting out for strong and anti-fatigue hydrogels as wearable strain sensors - Haidi Wu; Yongchuan Wu; Jun Yan; Wei Xiao; Yuqing Wang; Hechuan Zhang; Xuewu Huang; Huaiguo Xue; Ling Wang; Longcheng Tang; Yiuwing Mai; Jiefeng Gao (Chemical Engineering Journal, 2024)

A siloxane-based self-healing gel electrolyte with deep eutectic solvents for safe quasi-solid-state lithium metal batteries - Yuxin Chen; Canhui Ling; Kecheng Long; Xinsheng Liu; Pengfei Xiao; Ying-Zhi Yu; Weifeng Wei; Xiaobo Ji; Wenyan Tang; Gui-Chao Kuang; Libao Chen (Chemical Engineering Journal, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

Enhancing mechanism of extrusion pretreatment on bioconversion of distiller’s grains into microbial protein feed - Chenjie Wang; Yao Liu; Ruoyun Yuan; Ling Xu; Chunhui Xin; Yang Tang; Chengye Ma; Shanfeng Chen; Hongjun Li (Animal Feed Science and Technology, 2024)

In the context of the triple burden of malnutrition: A systematic review of gene-diet interactions and nutritional status - Pui Yee Tan; J. Bernadette Moore; Ling Bai; GuYuan Tang; Yun Yun Gong (Critical Reviews in Food Science and Nutrition, 2024)

The emerging role of zinc on alleviating inflammatory responses and enhancing immunity in grass carp (Ctenopharyngodon idella) - Xin Zeng; Zheng-Xing Song; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Juan Yang; Lin Feng (Aquaculture, 2024)

Occurrence, distribution, and risk assessment of antibiotics in a typical aquaculture area around the Dongzhai Harbor mangrove forest on Hainan Island - Tuan-Tuan Wang; Shuai Shao; Shi-Di Fan; Wang-Qing Tang; Jiang-Wei Miao; Sai Wang; Xiao-Cong Cao; Chuan Liu; Guang-Guo Ying; Zhong-Bing Chen; Hai-Long Zhou; Xiao-Ping Diao; et al. (Science of The Total Environment, 2024)

Geochemistry and petrogenesis of gabbroic rocks from the Yap forearc in the western Pacific: Implications for early arc magmatism - Ling Chen; Limei Tang; Jie Zhang; Xiaohu Li; Wei Wang; Yanhui Dong; Jie Li; Zhenggang Li; Hao Wang; Zhimin Zhu; Xingwei Meng; Wei Yan; et al. (Lithos, 2024)

Molten salt-promoted MgO-based CO2 adsorbents: Selective adsorption on polycrystalline surfaces - Changqing Gui; Zirui Wang; Changjian Ling; Zhongfeng Tang (Journal of Environmental Chemical Engineering, 2024)

A novel hollow CuMn-PBA@NiCo-LDH nanobox for efficient detection of glucose in food - Xin Tang; Xiangwei Yuan; Yao Jin; Jiaying Wu; Chengshuang Ling; Ke Huang; Liping Zhu; Xiaoli Xiong (Food Chemistry, 2024)

Effects of maternal and perinatal factors on human milk fat globule membrane proteome: A data independent acquisition approach - Jiayue Tang; Dan Yao; Cai Shen; Jingwen Yu; Hong Zhang; Xuebing Xu; Maolin Tu; Ling-Zhi Cheong (Food Bioscience, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Structure characterization of an agavin-type fructan isolated from Polygonatum cyrtonema and its effect on the modulation of the gut microbiota in vitro - Ya Gao; Jinyan Wang; Ying Xiao; Ling Yu; Qingjiu Tang; Yipeng Wang; Jianjin Zhou (Carbohydrate Polymers, 2024)

GRMPose: GCN-based real-time dairy goat pose estimation - Ling Chen; Lianyue Zhang; Jinglei Tang; Chao Tang; Rui An; Ruizi Han; Yiyang Zhang (Computers and Electronics in Agriculture, 2024)

Automatic detection and counting of planthoppers on white flat plate images captured by AR glasses for planthopper field survey - Haiyuan Sheng; Qing Yao; Ju Luo; Yongjian Liu; Xiangfu Chen; Zhongru Ye; Tiezhuang Zhao; Heping Ling; Jian Tang; Shuhua Liu (Computers and Electronics in Agriculture, 2024)

New directions on membranes for removal and degradation of emerging pollutants in aqueous systems - Die Ling Zhao; Wangyi Zhou; Liguo Shen; Bowen Li; Hongyu Sun; Qianqian Zeng; Chuyang Y. Tang; Hongjun Lin; Tai-Shung Chung (Water Research, 2024)

Inertial and kinematic demands of isolated pile-supported wharves in liquefiable soils: Centrifuge tests - Liang Tang; Zheng Zhang; Xianzhang Ling; Shengyi Cong; Pan Si (Soil Dynamics and Earthquake Engineering, 2024)

Revealing the synergistic effect between radical and non-radical species of sulfur-doped carbon nitride for ciprofloxacin removal: Based on density functional theory study - Hao Zeng; Zhanpeng Zhou; Wenbo Li; Ling Li; Rongdi Tang; Sheng Xiong; Daoxin Gong; Ying Huang; Lianyang Bai; Yaocheng Deng (Science of The Total Environment, 2024)

Coarse particles compensate for missing daytime sources of nitrous acid and enhance atmospheric oxidation capacity in a coastal atmosphere - Meng-Xue Tang; Ling-Yan He; Shi-Yong Xia; Zhen Jiang; Dong-Yi He; Song Guo; Ren-Zhi Hu; Hui Zeng; Xiao-Feng Huang (Science of The Total Environment, 2024)

Multimedia distribution, partitioning, sources, comprehensive toxicity risk and co-occurrence network characteristics of trace elements in a typical Chinese shallow lake with high antibiotic risk - Ling Zhang; Junhong Bai; Yujia Zhai; Kegang Zhang; Yaqi Wang; Ruoxuan Tang; Rong Xiao; Milko A. Jorquera (Journal of Hazardous Materials, 2024)

Modelling monthly-gridded carbon emissions based on nighttime light data - Ruxing Wan; Shuangyue Qian; Jianhui Ruan; Li Zhang; Zhe Zhang; Shuying Zhu; Min Jia; Bofeng Cai; Ling Li; Jun Wu; Ling Tang (Journal of Environmental Management, 2024)

Promoting effect of FeOx addition on the mechanochemically prepared vanadium-based catalyst for real PCDD/Fs removal and mechanism insight - Minghui Tang; Ling Wang; Hongxian Li; Xinlei Huang; Cuicui Du; Shengyong Lu (Journal of Environmental Sciences, 2024)

Pollution levels and potential ecological risks of trace elements in relation to bacterial community in surface water of shallow lakes in northern China before and after ecological water replenishment - Ling Zhang; Junhong Bai; Yujia Zhai; Kegang Zhang; Yaqi Wang; Ruoxuan Tang; Rong Xiao; Milko A. Jorquera (Journal of Contaminant Hydrology, 2024)

Dynamic surface-enhanced Raman spectroscopy and positively charged probes for rapid detection and accurate identification of fungal spores in infected apples via deep learning methods - Jinghong Wang; Rui Zhu; Yehang Wu; Le Tang; Cong Wang; Mengqing Qiu; Ling Zheng; Pan Li; Shizhuang Weng (Food Control, 2024)

l-Cysteine and barium titanate co-modified enteromorpha biochar as effective peroxymonosulfate activator for atrazine treatment - Sheng Xiong; Hao Zeng; Rongdi Tang; Naif Abdullah Al-Dhabi; Wenbo Li; Zhanpeng Zhou; Ling Li; Wangwang Tang; Daoxin Gong; Yaocheng Deng (Bioresource Technology, 2024)

Study of the cooling performance of an anti-condensation radiant cooling unit with an infrared-transparent silicon wafer - Xudong Tang; Danping Pang; Riqin Nong; Xiaosong Su; Lei Fang; Ling Zhang (Building and Environment, 2024)

Enhanced Removal of Sulfonated Lignite from Oilfield Wastewater by Soft Colloidal Templated Porous Structure of MgAl-LDH - Ying Tang; Bingbing Bai; Ya Wu; Bo Yang; Ling Zhou; Chentun Qu (Water, Air, & Soil Pollution, 2024)

Enhancing mechanisms of N-doped biomass carbon on the vanadium-based catalyst for furan degradation at low temperature - Ling Wang; Minghui Tang; Hongxian Li; Jiamin Ding; Juan Qiu; Shengyong Lu (Waste Disposal & Sustainable Energy, 2024)

Hessian Regularized $$L_{2,1}$$-Nonnegative Matrix Factorization and Deep Learning for miRNA–Disease Associations Prediction - Guo-Sheng Han; Qi Gao; Ling-Zhi Peng; Jing Tang (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Spatial–temporal characteristics and driving factors’ contribution and evolution of agricultural non-CO2 greenhouse gas emissions in China: 1995–2021 - Yuan-yue Chu; Xi-ling Zhang; Yang-chen Guo; Li-juan Tang; Chao-yong Zhong; Ji-wen Zhang; Xin-long Li; De-wen Qiao (Environmental Science and Pollution Research, 2024)

Reduced arsenic availability in paddy soil through Fe-organic ligand complexation mediated by bamboo biochar - Li Tang; Ling Xiong; Haiyan Zhang; Akaninyene Joseph; Yimin Wang; Jizhou Li; Xuyin Yuan; Eldon R. Rene; Ningyuan Zhu (Chemosphere, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

Enhanced atmospheric water harvesting (AWH) by Co-based MOF with abundant hydrophilic groups and open metal sites - Sihan Li; Peng Wu; Long Chen; Yiwen Tang; Yanhe Zhang; Ling Qin; Xiaofei Qin; Haibo Li (Journal of Water Process Engineering, 2024)

Preparation of homogeneous LiF-BeF2-ZrF4 molten salt with low oxygen content - Yulong Song; Miao Shen; Jing Yang; Ling Han; Rui Tang; Sufang Zhao; Yuan Qian (Journal of Fluorine Chemistry, 2024)

Rational designed of PVDF membrane based on surface modification of εPL anchored by PC for crude oil emulsion separation - Yan Liu; Yunfei Guo; Lilin Wang; Jinsong He; Ling Luo; Weixu Tang; Chengyi Huang; Chao Chen; Fei Shen; Yanzong Zhang (Journal of Environmental Chemical Engineering, 2024)

Ignition and combustion mechanism of alcohol/aluminum suspension nano-fluid droplets - Ying Zhao; Xiao-He Wang; Yu-Xiao Cheng; Zheng Mei; Xue-Bo Chen; Shuang-Ling Tang (Fuel, 2024)

In vitro digestion under simulated saliva, gastric and small intestinal conditions and fermentation of nicotinamide mononucleotide, and its effects on the gut microbiota - Zhaocheng Tang; Peng Bao; Xitie Ling; Zeyu Qiu; Baolong Zhang; Tingting Hao (Food Research International, 2024)

Molecular simulation combined with DFT calculation guided heteroatom-doped biochar rational design for highly selective and efficient CO2 capture - Hongxian Li; Minghui Tang; Ling Wang; Qi Liu; Fan Yao; Zhiyuan Gong; Yunchao Li; Shengyong Lu; Jianhua Yan (Chemical Engineering Journal, 2024)

GW4064 inhibits migration and invasion through cathepsin B and MMP2 downregulation in human bladder cancer - Chien-Chang Kao; Chien-Rui Lai; Yi-Hsuan Lin; Tzu-Min Chen; Yu-Ling Tsai; Wen-Chiuan Tsai; Tze-Yun Ong; Hisao-Hsien Wang; Sheng-Tang Wu; Ying Chen (Chemico-Biological Interactions, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Specific metabolic and cellular mechanisms of the vegetative desiccation tolerance in resurrection plants for adaptation to extreme dryness - Jie Liu; Yuanyuan Wang; Xiuxiu Chen; Ling Tang; Yang Yang; Zhaolin Yang; Runze Sun; Petko Mladenov; Xiaohua Wang; Xiaoqiang Liu; Songsong Jin; Hui Li; et al. (Planta, 2024)

Genome-wide identification of GATA transcription factor family and the effect of different light quality on the accumulation of terpenoid indole alkaloids in Uncaria rhynchophylla - Yingying Shao; Yu Zhou; Li Yang; Detian Mu; Iain W. Wilson; Yao Zhang; Lina Zhu; Xinghui Liu; Ling Luo; Jialong He; Deyou Qiu; Qi Tang (Plant Molecular Biology, 2024)

A high-efficient protoplast transient system for screening gene editing elements in Salvia miltiorrhiza - Jin Shao; Bowen Peng; Yaojie Zhang; Xin Yan; Xinghao Yao; Xinyi Hu; Ling Li; Xueqing Fu; Han Zheng; Kexuan Tang (Plant Cell Reports, 2024)

Blockade of ZFX Alleviates Hypoxia-Induced Pulmonary Vascular Remodeling by Regulating the YAP Signaling - Ling Tang; Xiao Zhou; Aili Guo; Lizhang Han; Silin Pan (Cardiovascular Toxicology, 2024)

Correlation study of SNP of glycogen degradation metabolism related genes and glycogen content in Haliotis discus hannai - Xueying Tang; Sisi Li; Ling Zhuo; Qingya Zhang; Fucun Wu; Siheng Lin (Aquaculture, 2024)

Development of shield model test system for studying the bias load of shield in soil-rock compound strata - Xiangxun Kong; Liang Tang; Xianzhang Ling; Hui Li (Tunnelling and Underground Space Technology, 2024)

Evolution of rattlers under different confining pressures and its influence on shear strength - Tiantian Hu; Daosheng Ling; Yao Tang; Xiukai Wang; Jing Wang (Transportation Geotechnics, 2024)

Atmospheric CO2 controls on the MIS 6 glaciation: 10Be chronology of moraines in the Haizishan area, southeastern Tibetan Plateau - Guocheng Dong; Weijian Zhou; Feng Xian; Yunchong Fu; Li Zhang; Ling Tang; Pengkai Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Enhancing the removal efficiency of microplastics in drinking water treatment - Shuyuan Tang; Ling Gao; Tianrui Zhao; Aisi Tian (Journal of Water Process Engineering, 2024)

Solar-driven methanol steam reforming for low carbon and efficient hydrogen production: A review - Xu Ma; Wei-Wei Yang; Xin-Yuan Tang; Ya-Ling He (Journal of Cleaner Production, 2024)

A bibliometric analysis of global research hotspots and progress on microplastics in soil‒plant systems - Pengxinyue Huang; Yanyan Zhang; Naseer Hussain; Ting Lan; Guangdeng Chen; Xiaoyan Tang; Ouping Deng; Chaorui Yan; Yang Li; Ling Luo; Wenyu Yang; Xuesong Gao (Environmental Pollution, 2024)

Sources of atmospheric oxygenated volatile organic compounds in different air masses in Shenzhen, China - Zhi-Jie Li; Ling-Yan He; Hao-Nan Ma; Xing Peng; Meng-Xue Tang; Ke Du; Xiao-Feng Huang (Environmental Pollution, 2024)

Fluorine modification regulation of D-A ambipolar conducting polymers towards high-performance energy storage device - Weiwei Hou; Shenglian Yao; Yusheng Chen; Dianyu Tang; Yijing Gao; Xiangyu Zhang; Ling Zhang; Zhenliang Zhang; Mi Ouyang; Junlei Liu; Lin Gu; Cheng Zhang (Chemical Engineering Journal, 2024)

Supramolecular fluorescence sensor array used for the analysis of tyrosine kinase inhibitors in biological fluids and cell imaging - Hong-Ling Yi; Ru-Pei Yang; Qing Tang; Zhu Tao; Ying Huang (Analytica Chimica Acta, 2024)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Author correction to “nirS and nosZII bacterial denitrifiers as well as fungal denitrifiers are coupled with N2O emissions in long-term fertilized soils” [Sci. Total Environ. 897-165426] - Ziwei Wan; Ling Wang; Guoqin Huang; Fahd Rasul; Masood Iqbal Awan; Huanming Cui; Kailou Liu; Xichu Yu; Haiying Tang; Shubin Wang; Huifang Xu (Science of The Total Environment, 2023)

Molecular catalysts with electronic axial stretching for high-performance lean-oxygen seawater batteries - Quanjun Tang; Liang Bai; Chen Zhang; Rongwei Meng; Li Wang; Chuannan Geng; Yong Guo; Feifei Wang; Yingxin Liu; Guisheng Song; Guowei Ling; Haitao Sun; et al. (Science Bulletin, 2023)

Greenhouse gas emissions mitigation potential of municipal solid waste management: A case study of 13 prefecture-level cities in Jiangsu Province, China - Binxian Gu; Hui Ling; Mange Zhang; Huimin Hang; Qingsong Hu; Zhigang Wang; Xinyi Tang; Xingyou Bu; Yanchao Bai (Journal of Cleaner Production, 2023)

Ultrasound-assisted enzymatic hydrolysis enhances anti-inflammatory and hypoglycemic activities of edible Bird's nest - Pei Ling Tang; Xian Jian Koh (Food Bioscience, 2023)

Dose assessment on the impact of accidents with Fukushima nuclear meltdown emission levels at the four nuclear power plants in Taiwan - Mei-Ling Tang; Ben-Jei Tsuang; Pei-Hsuan Kuo; Yi-Sheng Wang; Xin-Yu Liu; Kai-Chen Ku (Energy and Climate Change, 2023)

Metal-free chiral molecular ferroelectric photovoltaics - Shulin Jiao; Haidong Jiang; Changchun Fan; Cuiping Xu; Junjie Jiang; Yanming Xu; Zheng Tang; Xiaofan Sun; Peiqi Ji; Xingming Yang; Kongmeng Ye; Libo Xu; et al. (Chemical Engineering Journal, 2023)

Permanent deformation prediction model for freeze–thaw coarse–fine mixture of geomaterials with varying fine content: Influence of loading frequency - Shuang Tian; Ke Wang; Liang Tang; Xianzhang Ling; Hongye Yan; Min Liu (Cold Regions Science and Technology, 2023)

Sea-land breezes in the Guangdong- Hong Kong- Macau Greater Bay Area coastal zone from 2013 to 2022 - Jielan Xie; Jiaren Sun; Yanyan Li; Pak Wai Chan; Lei Li; Caijing Huang; Ling Tang; Shaojia Fan; Youren Zheng; Zhenan Fan (Atmospheric Research, 2023)

Engineering of formate dehydrogenase for improving conversion potential of carbon dioxide to formate - Hong-Ling Shi; Shu-Wei Yuan; Xiao-Qi Xi; Yu-Li Xie; Chao Yue; Ying-Jun Zhang; Lun-Guang Yao; Chuang Xue; Cun-Duo Tang (World Journal of Microbiology and Biotechnology, 2023)

Food quality upgrade of carbon from submerged macrophytes by flagellates via a heterotrophic pathway can stimulate growth of Daphnia magna - Yali Tang; Ling Su; Shuping Liang; Shun Liu; Zhengwen Liu; Erik Jeppesen (Oecologia, 2023)

PPAR-γ promotes the polarization of rat retinal microglia to M2 phenotype by regulating the expression of CD200-CD200R1 under hypoxia - Yiyi Hong; Li Jiang; Fen Tang; Mingyuan Zhang; Ling Cui; Haibin Zhong; Fan Xu; Min Li; Changzheng Chen; Lifei Chen (Molecular Biology Reports, 2023)

Comparative transcriptome analysis of eyes reveals the adaptive mechanism of mantis shrimp (oratosquilla oratoria) induced by a dark environment - Xiaoli Sun; Ling He; Bujin Ayi; Yuyang Qiu; Jiayue Xu; Wei Yu; Tinghao Yan; Ge Ding; Boping Tang; Gang Wang; Daizhen Zhang (Genetica, 2023)

Low acrosin activity is associated with decreased Spam1/acrosin expression and GSH deficiency-caused premature acrosome release of human sperm cells - Mengyuan Lin; Pengyun Ling; Qingwen He; Daozhen Chen; Lianshuai Zheng; Lisha Tang; Shi-Wen Jiang (Cell and Tissue Research, 2023)

Mapping the number of mangrove trees in the Guangdong-Hong Kong-Macao Greater Bay Area - Tang Liu; Benjamin J. Zhou; Hou Jiang; Ling Yao (Marine Pollution Bulletin, 2023)

Seismic response and failure modes analysis of pile foundations in liquefiable soils using various design criteria - Xiaofeng Man; Liang Tang; Xijun Jia; Shengyi Cong; Xianzhang Ling (Soil Dynamics and Earthquake Engineering, 2023)

nirS and nosZII bacterial denitrifiers as well as fungal denitrifiers are coupled with N2O emissions in long-term fertilized soils - Ziwei Wan; Ling Wang; Guoqin Huang; Fahd Rasul; Masood Iqbal Awan; Huanming Cui; Kailou Liu; Xichu Yu; Haiying Tang; Shubin Wang; Huifang Xu (Science of The Total Environment, 2023)

Environmental cadmium exposure facilitates mammary tumorigenesis via reprogramming gut microbiota-mediated glutamine metabolism in MMTV-Erbb2 mice - Yang Yue; Huadong Zhang; Ping Deng; Miduo Tan; Chengzhi Chen; Bo Tang; Jingdian Li; Fengqiong Chen; Qi Zhao; Ling Li; Rongrong Hao; Hui Wang; et al. (Science of The Total Environment, 2023)

Theoretical and experimental investigation on rapid and efficient adsorption characteristics of microplastics by magnetic sponge carbon - Hongxian Li; Minghui Tang; Jun Wang; Lulu Dong; Ling Wang; Qi Liu; Qunxing Huang; Shengyong Lu (Science of The Total Environment, 2023)

The fate of microplastic pollution in the Changjiang River estuary: A review - Yifei Li; Qingbing Lu; Jian Yang; Yi Xing; Wei Ling; Kai Liu; Qizhen Yang; Hongjie Ma; Zengxin Pei; Tianqi Wu; Haochen Guo; Ziyuan Gao; et al. (Journal of Cleaner Production, 2023)

Health effects of future dioxins emission mitigation from Chinese municipal solid waste incinerators - Jing Guo; Xin Bo; Yang Xie; Ling Tang; Jun Xu; Zhongzhi Zhang; Ruxing Wan; Haiyun Xu; Zhifu Mi (Journal of Environmental Management, 2023)

Cost-benefits analysis of ultra-low emissions standard on air quality and health impact in thermal power plants in China - Ruxing Wan; Ling Tang; Jing Guo; Wenhui Zhai; Ling Li; Yang Xie; Xin Bo; Jun Wu (Journal of Environmental Management, 2023)

Metagenomics reveals taxon-specific responses of soil nitrogen cycling under different fertilization regimes in heavy metal contaminated soil - Xinwei Shi; Weilan Tan; Shuting Tang; Qiujie Ling; Chijian Tang; Peiqing Qin; Shiyu Luo; Yinjun Zhao; Fangming Yu; Yi Li (Journal of Environmental Management, 2023)

The study on morphological evolution process of gully headcut erosion in granite red soil hilly area based on an in situ scouring experiment - Zhe Lin; Dalan Liao; Ling He; Qiuyue Tang; Jiangxing Wei; Zuoli Wu; Yusong Deng (Geomorphology, 2023)

Utilizing cetyltrimethylammonium bromide assisted alkali pretreatment to improve monosaccharide production of wheat straw by intensifying lignin extraction - Wei Tang; Zhe Ling; Caoxing Huang; Yu-Cai He (Fuel, 2023)

One-dimensional magnetotelluric parallel inversion using a ResNet1D-8 residual neural network - Weiwei Ling; Kejia Pan; Zhengyong Ren; Wenbo Xiao; Dongdong He; Shuanggui Hu; Zhengguang Liu; Jingtian Tang (Computers & Geosciences, 2023)

Performance improvement of Na4SiO4 doped with Li2CO3-K2CO3 for high-temperature CO2 capture and thermochemical energy storage - Changjian Ling; Zirui Wang; Zhongfeng Tang (Chemical Engineering Journal, 2023)

Fabrication of diamond/copper composite thin plate based on a single-layer close packed diamond particles network for heat dissipation - Jia-wan Peng; Feng-lin Zhang; Yu-mei Zhou; Ling-kang Xiong; Yao-jie Huang; Hong-qun Tang (Chemical Engineering Journal, 2023)

Optical and electrical dual-mode tactile sensor with interlinked interfaces recording normal force and slip for closed-loop robotics - Kedong Shang; Changliu He; Jian Zhou; Peng Ling; Xulei Lu; Chunqiao Fu; Yong Zhang; Chuan Tang; Linmao Qian; Tingting Yang (Chemical Engineering Journal, 2023)

Stable anode interface regulation of solid sodium battery through oxygen potential regulation - Weidong Meng; Weibo Han; Lei Dai; Ling Wang; Xianjian Tang; Shan Liu (Chemical Engineering Journal, 2023)

CD44 targeting nanodrug based on chondroitin sulfate for melanoma therapy by inducing mitochondrial apoptosis pathways - Yan Li; Huiwen Hou; Zengmei Liu; Wen Tang; Jie Wang; Lu Lu; Jiaai Fu; Didi Gao; Feiyan Zhao; XinQing Gao; Peixue Ling; Fengshan Wang; et al. (Carbohydrate Polymers, 2023)

In Silico and Expression Analysis of Papain-Like Cysteine Proteinases (PLCP) Genes in Vitis vinifera to Predict Their Involvement in Hormonal Signaling and Disease Resistance - Ting Zhao; Jing Yan; Ziyang Qu; Ling Wang; Yujin Tang; Chaohong Zhang; Yan Li (Journal of Plant Growth Regulation, 2023)

High site elevation enhanced nitrogen fixation and the stability of diazotrophic community in planted Sonneratia apetala mangrove sediments - Xiaofang Huang; Jianxiang Feng; Qingsong Yang; Luxiang Chen; Jian Zhang; Bing Yang; Xiaoyu Tang; Chenxi Yu; Juan Ling; Junde Dong (Applied Soil Ecology, 2023)

Digital-twin-enabled JIT design of rock tunnel: Methodology and application - Xiaojun Li; Li Tang; Jiaxin Ling; Chao Chen; Yi Shen; Hehua Zhu (Tunnelling and Underground Space Technology, 2023)

Artificial neural network-based investigation on high-speed train-induced embankment vibration in frozen regions - Shuang Tian; Liang Tang; Ting Li; Xianzhang Ling (Soil Dynamics and Earthquake Engineering, 2023)

On conflict of natural resources-carbon emissions nexus in China: The role of economic policy uncertainty - Maoran Ye; Ling Tang; Lin Huang; Mei Li (Resources Policy, 2023)

Piezoelectricity ameliorates high-valent iron oxo species production in peroxymonosulfate activation for refractory atrazine remediation - Sheng Xiong; Hao Zeng; Rongdi Tang; Ling Li; Zhanpeng Zhou; Wenbo Li; Daoxin Gong; Yaocheng Deng (Journal of Hazardous Materials, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Multiple path-dominated activation of peroxymonosulfate by MOF-derived Fe2O3/Mn3O4 for catalytic degradation of tetracycline - Chensi Tang; Min Cheng; Cui Lai; Ling Li; Zhen Wei; Dengsheng Ma; Li Du; Guangfu Wang; Lu Yang; Lin Tang (Journal of Environmental Chemical Engineering, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Space charge region induced self-evolution dehydrogenation of polymorphic magnesium-based hydrides - Qinke Tang; Jiangchuan Liu; Mengran Li; Rui Shi; Yunfeng Zhu; Yao Zhang; Jiguang Zhang; Yana Liu; Yijin Wu; Ling Li; Xiaohui Hu; Liquan Li (Chemical Engineering Journal, 2023)

Titanium oxide nanotubes intercalated two-dimensional MXene composite membrane with exceptional antifouling and self-cleaning properties for oil/water separation - Qianqian Zeng; Die Ling Zhao; Liguo Shen; Hongjun Lin; Ning Kong; Lei Han; Cheng Chen; Jiaheng Teng; Chuyang Tang; Tai-Shung Chung (Chemical Engineering Journal, 2023)

Facet engineering of BiVO4 photocatalyst for the synergetic adsorption and activation of persulfate for organic pollutants degradation - Ling-Ling Zheng; Lei Tian; Dengke Wang; Ying Chen; Qian-Qian Tang; Qiu-Ju Xing; Xiao-Zhen Liu; Dai-She Wu; Jian-Ping Zou (Chemical Engineering Journal, 2023)

Insight into the selective oxidation behavior of organic pollutants via Ni-N4-C mediated electron transfer pathway - Huchuan Yan; Cui Lai; Shiyu Liu; Dongbo Wang; Xuerong Zhou; Mingming Zhang; Ling Li; Dengsheng Ma; Fuhang Xu; Xiuqin Huo; Lin Tang; Ming Yan; et al. (Chemical Engineering Journal, 2023)

Photoassisted synthesis of high-crystallinity TS-1 with triblock copolymer F127 and its application for photodegradation of erythromycin - Fanjun Meng; Yujie Ling; Yanan Li; Mingrui Guo; Kunze Wei; Mingfei Zhang; Chong Yang; Xifeng Shi; Bo Tang (Chemical Engineering Journal, 2023)

Facile design of surface electric field driven tourmaline/g-C3N4 layered stacked photocatalysts with enhanced photocatalytic activity for antibiotic removal - Xiangwei Tang; Rongdi Tang; Zhanpeng Zhou; Ling Li; Yaocheng Deng; Daoxin Gong; Lihua Yang; Tianwei Song; Mingxuan He (Chemosphere, 2023)

Variations of different PAH fractions and bacterial communities during the biological self-purification in the soil vertical profile - Lei Tang; Zhongkang Bao; Xuqiang Zhao; Xinbo Wang; Yanzheng Gao; Chao Lu; Wanting Ling (Journal of Hazardous Materials, 2023)

Tuning the intrinsic catalytic sites of magnetite to concurrently enhance the reduction of H2O2 and O2: Mechanism analysis and application potential evaluation - Ling Li; Min Cheng; Eydhah Almatrafi; Lei Qin; Shiyu Liu; Huan Yi; Lu Yang; Zhexin Chen; Dengsheng Ma; Mingming Zhang; Xuerong Zhou; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

Synergistic enhancement of reaction and separation for a solar membrane reactor by topology optimization of catalyst bed - Xin-Yuan Tang; Wei-Wei Yang; Xu Ma; Ya-Ling He (Chemical Engineering Journal, 2023)

In situ deposition of double Fe-based Fenton catalysts on the porous membrane for the development of multi-defense against various foulants toward highly efficient water purification - Yu-Ling Yang; Gang Wang; Ping Zhu; Lei Tang; Zhi-Xiang Zeng; Li-Jing Zhu (Chemical Engineering Journal, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Nafamostat mesilate prevented caerulein-induced pancreatic injury by targeting HDAC6-mediated NLRP3 inflammasome activation - Peng Chen; Li-Jun Zhao; Ling Huang; Wen-Qi He; Ying-Rui Tang; Yi Liu; Jian-Dong Ren (Inflammation Research, 2023)

Distribution and diversity of the sympatric macroalgae of the pelagic Sargassum horneri in the Yellow and East China seas - Yong-Juan Liu; Jie Xiao; Shi-Liang Fan; Xiao-Xiang Miao; Chao Yuan; Yu Zang; Zong-Ling Wang; Bao-Tang Zhang; Xiao-Jun Ma; Xue-Lei Zhang (Aquatic Botany, 2023)

A novel city-level carbon emission quota allocation method for carbon peak and neutrality targets - Ling Tang; Junai Yang; Zixuan Li; Shuying Zhu; Xiaomeng Zhang; Bofeng Cai (Environment, Development and Sustainability, 2023)

Review on developments of catalytic system for methanol steam reforming from the perspective of energy-mass conversion - Wei-Wei Yang; Xu Ma; Xin-Yuan Tang; Pei-Yuan Dou; Yong-Jian Yang; Ya-Ling He (Fuel, 2023)

Variations on the diazotrophic community in the rhizosphere soil of three dominant plant species in a lead–zinc mine area - Yi Li; Xuan Chen; Chijian Tang; Meng Zeng; Songying Li; Qiujie Ling; Kehui Liu; Jiangming Ma; Shuting Tang; Fangming Yu (Plant and Soil, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Crop – Livestock integration via maize straw recycling increased carbon sequestration and crop production in China - Ling Liu; Hui-fang Zheng; Zhen Liu; Yu-Zhao Ma; Hui-fang Han; Tang-yuan Ning (Agricultural Systems, 2023)

Culturing reef-building corals on a laboratory dish: a simple experimental platform for stony corals - Shinya Shikina; Tzu-Chieh Lin; Yu-Ling Chu; Yin-Chu Cheng; Yu-En Chang; Naohisa Wada; Sen-Lin Tang; Yoshiyuki Iizuka; Yi-Ling Chiu (Frontiers in Marine Science, 2023)
Development and maintenance of coral reef ecosystems rely on daily micro-biological activities of healthy corals. Although a comprehensive understanding of coral biological properties, as well as factors negatively affecting coral growth, are essential to conserve existing corals, the current lack of a tractable culture and experimental platform has delayed acquisition of such knowledge. Here we show a highly versatile culture system, “coral-on-a-laboratory dish” (CLD), allowing long-term culturing of various corals in plastic/glass Petri dishes with maintenance of their biological properties. Under optimized conditions, coral microcolonies (~5 mm x 5 mm fragments) of Pocillopora damicornis were cultured for several months in dishes with high survivorship and characteristic growth. These microcolonies maintained their biological properties, such as reproduction, skeleton formation, coral-algal symbiosis, ingestion, and digestion. Thus far, CLD has been used to maintain at least 4 other coral species from 4 other families, including the Acroporidae, the Pocilloporidae, the Poritidae, and the Merulinidae for more than 2 months with 100% survivorship. CLD is applicable to a variety of biophysiological studies, including coral-algal symbiosis and impact assessment of marine pollutants, e.g., a sunscreen substance, oxybenzone, and an organic biocide, Irgarol 1051, at cellular-level resolution. The CLD platform, which allows easy and inexpensive coral maintenance in a laboratory incubator, represents a technological breakthrough that will greatly advance coral studies.

Two new isoquinolines from Corydalis saxicola - Zhi-Wei Ouyang; Ji-Man He; Feng Qin; Ling Li; Wen-Di Tang; Dian-Peng Li; Jiang-Ke Qin (Natural Product Research, 2023)

Fluoride occurrence in geothermal water of fault zone area, Southeast China - Xuelian Huang; Yongjie Han; Zhicai Xiao; Shuai Wang; Sijia Wang; Min Zhang; Turong Zeng; Ling Tang; Hailong Li; Shihua Qi (Chemosphere, 2023)

Transcriptional regulatory network of high-value active ingredients in medicinal plants - Han Zheng; Xueqing Fu; Jin Shao; Yueli Tang; Muyao Yu; Ling Li; Luqi Huang; Kexuan Tang (Trends in Plant Science, 2023)

Experimental investigation and prediction model of permeability in solidified coarse-grained soil under freeze-thaw cycles in water-rich environments - Ke Wang; Liang Tang; Shuang Tian; XianZhang Ling; Degou Cai; Min Liu (Transportation Geotechnics, 2023)

The coagulation behavior and removal efficiency of microplastics in drinking water treatment - Shuyuan Tang; Ling Gao; Aisi Tian; Tianrui Zhao; Donglei Zou (Journal of Water Process Engineering, 2023)

Distribution of bound-PAH residues and their correlations with the bacterial community at different depths of soil from an abandoned chemical plant site - Lei Tang; Xuqiang Zhao; Xuwen Chen; Yi Jiang; Fredrick Gudda; Yunhao Wang; Wanting Ling (Journal of Hazardous Materials, 2023)

Metamorphic evolution and zircon ages of a Barrovian metamorphic series in central-western Inner Mongolia, China: Insights into the tectonic evolution of the Central Asian Orogenic Belt - Jinrui Zhang; Shuang Tang; Chunjing Wei; Wenliang Xu; Hang Chu; Ling Jiang (Journal of Asian Earth Sciences, 2023)

Microplasma and quenching-induced Co doped NiMoO4 nanorods with oxygen vacancies for electrochemical determination of glucose in food and serum - Jiaying Wu; Xin Tang; Shan Zhao; Yu Zhang; Chengshuang Ling; Yun Xing; Huimin Yu; Ke Huang; Zhirong Zou; Xiaoli Xiong (Food Chemistry, 2023)

Enhancing cellulosic digestibility of wheat straw by adding sodium lignosulfonate and sodium hydroxide to hydrothermal pretreatment - Wei Tang; Caoxing Huang; Zhe Ling; Yu-Cai He (Bioresource Technology, 2023)

Chitinolyticbacter albus sp. Nov., A Novel Chitin-Degrading Bacterium Isolated from Ancient Wood Rhizosphere Soil - Meng-Yu Zhang; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Jing Tang; Song-Guo Liang; Jian-Yu Li; Xiao-Di Liu; Lu-Yao Feng; Pei-Wen Yang; Zhu-Feng Shi; Zhang-Gui Ding; et al. (Current Microbiology, 2023)

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

Rainstorm sediment events in heterogeneous karst small watersheds: Process characteristics, prediction modeling and management enlightenment - Jun Jing; Jiang Yuan; Rui Li; Zaike Gu; Li Qin; Jiayong Gao; Linlv Xiao; Zhenyi Tang; Ling Xiong (Science of The Total Environment, 2023)

VviKFB07 F-box E3 ubiquitin ligase promotes stilbene accumulation by ubiquitinating and degrading VviCHSs protein in grape - Ting Zhao; Congbo Huang; Shengzhi Li; Mengqiong Jia; Ling Wang; Yujin Tang; Chaohong Zhang; Yan Li (Plant Science, 2023)

Propionate poses antivirulence activity against Botrytis cinerea via regulating its metabolism, infection cushion development and overall pathogenic factors - Chuanxi Zhu; Yan Tang; Dandan Ren; Weiheng Ren; Yongjun Xue; Aruppillai Suthaparan; Jufen Li; Yiwen Wang; Ling Xu; Pinkuan Zhu (Food Chemistry, 2023)

Synergistic effect of high-valent cobalt oxo species and piezoelectricity on enhanced peroxymonosulfate activation for atrazine removal - Sheng Xiong; Hao Zeng; Rongdi Tang; Ling Li; Zhanpeng Zhou; Jiajia Wang; Chunxia Ding; Daoxin Gong; Yaocheng Deng (Chemical Engineering Journal, 2023)

A notable reversible thermochromic (3,3-difluoropyrrolidinium)2[CuCl4] with ferroelectricity and ferroelasticity - Shulin Jiao; Zheng Tang; Dong Li; Cuiping Xu; Zhu Yang; Peng Chen; Xiaofan Sun; Hong-Ling Cai; Xiaoshan Wu (Chemical Engineering Journal, 2023)

An efficient biochar adsorbent for CO2 capture: Combined experimental and theoretical study on the promotion mechanism of N-doping - Hongxian Li; Minghui Tang; Xinlei Huang; Ling Wang; Qi Liu; Shengyong Lu (Chemical Engineering Journal, 2023)

Path planning for percutaneous lung biopsy based on the loose-Pareto and adaptive heptagonal optimization method - Qi Liu; Geyi Zhou; Jianquan Zhong; Ling Tang; Yao Lu; Jing Qin; Ling He; Jing Zhang (Medical & Biological Engineering & Computing, 2023)

Mixed with Broadleaf Tree Species Improved Soil Aggregate Stability in Chinese Fir (Cunninghamia lanceolata) Plantations: Based on the Le Bissonnais Method - Lili Tang; Ling Mao; Zhiyao Wang; Shaoming Ye; Shengqiang Wang (Journal of Soil Science and Plant Nutrition, 2023)

Pseudomonas subflava sp. nov., a new Gram-negative bacterium isolated from Guishan in Yunnan province, south–west China - Cheng Ling; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Xiao-Di Liu; Lu-Yao Feng; Pei-Wen Yang; Yao Lu; et al. (Antonie van Leeuwenhoek, 2023)

The investigation of the physiochemical factors and bacterial communities indicates a low-toxic infectious risk of the Qiujiang River in Shanghai, China - Xiaochuan Hou; Yina Zhu; Ling Wu; Jie Wang; Wei Yan; Songyu Gao; Yi Wang; Yushi Ma; Yongfang Wang; Zhaoyun Peng; Ye Tao; Qinglong Tang; et al. (Environmental Science and Pollution Research, 2023)

Application potential of Vaccinium ashei R. for cadmium migration retention in the mining area soil - Jianjincang Song; Yongyun Li; Hao Tang; Chengshu Qiu; Ling Lei; Maolin Wang; Heng Xu (Chemosphere, 2023)

Experimental investigation of the particle breakage of coarse-grained materials under impact loading - Yangsheng Ye; Degou Cai; Shuang Tian; Xianzhang Ling; Zuzheng Chen; Liang Tang; Xianglong Zhu (Transportation Geotechnics, 2023)

One-step rapid synthesis of Ni0.5Co0.5-CPO-27 nanorod array with oxygen vacancies based on DBD microplasma: As an effective non-enzymatic glucose sensor for beverage and human serum - Qiaoyan Dong; Chengshuang Ling; Shan Zhao; Xin Tang; Yu Zhang; Yun Xing; Huimin Yu; Ke Huang; Zhirong Zou; Xiaoli Xiong (Food Chemistry, 2023)

Construction of carbon nitride-based heterojunction as photocatalyst for peroxymonosulfate activation: Important role of carbon dots in enhancing photocatalytic activity - Pei Yang; An Shen; Ziqi Zhu; Ling Wang; Ruixin Tang; Kai Yang; Minzhi Chen; Hongqi Dai; Xiaoyan Zhou (Chemical Engineering Journal, 2023)

Design of a highly efficient Cu-based catalyst with two functional areas: The role of Cu0 and oxygen vacancies in Fenton-like system - Cui Lai; Lu Yang; Ling Li; Dengsheng Ma; Min Cheng; Shiyu Liu; Mingming Zhang; Huchuan Yan; Chensi Tang; Zhexin Chen; Lin Tang (Chemical Engineering Journal, 2023)

Rab37 Promotes Endothelial Differentiation and Accelerates ADSC-Mediated Diabetic Wound Healing through Regulating Secretion of Hsp90α and TIMP1 - Haili Huang; Ling Liang; Dan Sun; Jin Li; Wentao Wang; Lixia Zha; Jiaqi Yang; Kunyan Pan; Xianmou Fan; Chengzhang He; Xudong Tang; Peihua Zhang (Stem Cell Reviews and Reports, 2023)

Prediction of Cr and Ni contents in soil from hyperspectral data combined with Al-Fe minerals - Changcheng Tang; Rongbo Xiao; Bohua Ling; Peng Wang; Jiatong Zheng; Fei Huang; Weizhan Liu (International Journal of Remote Sensing, 2023)

Toxicological characteristics of drinking water in two large-scale municipal water supply systems of a metropolitan city in Central China - Huai-Ji Wang; Chen-Wei Peng; Xue Han; Yan Wang; Jie Zhang; Jun-Ling Liu; Meng-Xuan Zhou; Fei Tang; Ai-Lin Liu (Environmental Science and Pollution Research, 2023)

Abundance and characteristics of microplastics in the Wanquan River estuary, Hainan Island - Tuan-Tuan Wang; Wang-Qing Tang; Dong-Hai Wu; Xin-Rui Yu; Guang-Yu Wang; Xing-Wei Cai; Shuai Shao; Sai Wang; Ling Mo; You-Sheng Liu; Guang-Guo Ying; Zhong-Bing Chen (Marine Pollution Bulletin, 2023)

Transcriptional regulatory network of high-value active ingredients in medicinal plants - Han Zheng; Xueqing Fu; Jin Shao; Yueli Tang; Muyao Yu; Ling Li; Luqi Huang; Kexuan Tang (Trends in Plant Science, 2023)

Timing and seismic origin of the historic Luanshibao rock avalanche in the Maoyaba basin, SE Tibetan Plateau: New evidence from 10Be exposure-ages - Jiangtao Wang; Weijian Zhou; Guocheng Dong; Feng Xian; Yunchong Fu; Li Zhang; Ling Tang; Pengkai Ding; Guoqing Zhao (Quaternary Geochronology, 2023)

AaWIN1, an AP2/ERF protein, positively regulates glandular secretory trichome initiation in Artemisia annua - Chen Wang; Tiantian Chen; Yongpeng Li; Hang Liu; Wei Qin; Zhangkuanyu Wu; Bowen Peng; Xiuyun Wang; Xin Yan; Xueqing Fu; Ling Li; Kexuan Tang (Plant Science, 2023)

Two new dicyclic C-geranylflavanones isolated from Paulownia fortunei and their cytotoxicity - Wei-guo Liu; Cheng-mei Xiao; Jun Li; Su-ying Wu; Wen-chao Zhang; Ling-tao Kong; Wen-Zhao Tang; Xian-hui Jia (Phytochemistry Letters, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

Genome-resolved metagenomics reveals depth-related patterns of microbial community structure and functions in a highly stratified, AMD overlaying mine tailings - Zhen-Hao Luo; Qi Li; Nan Chen; Ling-Yun Tang; Bin Liao; Tao-Tao Yang; Li-Nan Huang (Journal of Hazardous Materials, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

Formation of Fe(IV) over a wide pH range via iron-carbon composite-catalyzed persulfate activation - Hong Li; Rongliang Qiu; Yetao Tang; Xiaoguang Duan; Yanling Gu; Hailan Yang; Qiang Chen; Zihan Shu; Ling Xiang; Shaobo Liu; Xiaofei Tan (Chemical Engineering Journal, 2023)

Dual polymer electrochromic sunglasses with black to anti-blue-ray conversion based on new anti-blue-ray transparent polymer - Haichang Fu; Yixiao Tang; Feng Zhan; Ling Zhang; Wang Zhan; Yujie Dong; Weijun Li; Cheng Zhang (Chemical Engineering Journal, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Aflatoxin B1 damaged structural barrier through Keap1a/Nrf2/ MLCK signaling pathways and immune barrier through NF-κB/ TOR signaling pathways in gill of grass carp (Ctenopharyngodon idella) - Xiang-Ning He; Zhen-Zhen Zeng; Lin Feng; Pei Wu; Wei-Dan Jiang; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Aquatic Toxicology, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Carbonyl and defect of metal-free char trigger electron transfer and O2•− in persulfate activation for Aniline aerofloat degradation - Hailan Yang; Rongliang Qiu; Yetao Tang; Shujing Ye; Shaohua Wu; Fanzhi Qin; Ling Xiang; Xiaofei Tan; Guangming Zeng; Ming Yan (Water Research, 2023)

Responses of medaka (Oryzias latipes) ammonia production and excretion to overcome acidified environments - Hsin-Ju Chuang; Ling Chiu; Jia-Jiun Yan; Chun-Yung Chang; Yu-Hsin Tang; Ming-Yi Chou; Hon-Tsen Yu; Pung-Pung Hwang (Journal of Hazardous Materials, 2023)

Genome-wide transcriptome analysis uncovers gene networks regulating fruit quality and volatile compounds in mango cultivar 'Tainong' during postharvest - Li Li; Ping Yi; Jian Sun; Jie Tang; Guoming Liu; Jinfeng Bi; Jianwen Teng; Meijiao Hu; Fang Yuan; Xuemei He; Jinfeng Sheng; Ming Xin; et al. (Food Research International, 2023)

Glutathione inhibited starch digestion: Structural and kinetic analysis of substrate and α-amylase - Yi-Fan Tang; Wen-Xi Zhan; Mi-Zhuan Li; Lei Wang; Jie-Ying Wei; Jun-ling Deng; Zhong-Xiu Chen (Food Chemistry, 2023)

Assessment of surface current measured by HF radars within a suspended kelp aquaculture zone in China - Xiangyang Zheng; Yana Ding; Yandong Xu; Tao Zou; Ling Meng; Cheng Tang; Qianguo Xing (Estuarine, Coastal and Shelf Science, 2023)

Variability and driving factors of the soil saturated hydraulic conductivity along the horizontal and vertical directions in the upper catchment of Benggang - Qiuyue Tang; Xiaoqian Duan; Ling He; Dalan Liao; Chongfa Cai; Yusong Deng (CATENA, 2023)

Liquid water determination by airborne millimeter cloud radar and in-situ size distribution measurements - Dongfei Zuo; Dantong Liu; Delong Zhao; Ling Yang; Yichen Chen; Wei Zhou; Mengyu Huang; Hui He; Ping Tian; Yuanmou Du; Wei Xiao; Ruijie Li; et al. (Atmospheric Research, 2023)

Applicability evaluation of ERA5 wind and wave reanalysis data in the South China Sea - Rongwei Zhai; Caijing Huang; Wei Yang; Ling Tang; Wenjing Zhang (Journal of Oceanology and Limnology, 2023)

Coseismic landslide sediment increased by the “9.5” Luding earthquake, Sichuan, China - Jiang Xiong; Hua-yong Chen; Lu Zeng; Feng-huan Su; Ling-feng Gong; Chen-xiao Tang (Journal of Mountain Science, 2023)

Response of zooplankton to inputs of terrestrial dissolved organic matter: Food quality constraints induced by microbes - Yali Tang; Ling Su; Ruohua Xu; Sirui Wang; Yaling Su; Zhengwen Liu; Jinlei Yu; Henri J. Dumont; Erik Jeppesen (Limnology and Oceanography, 2023)
Terrestrial inputs of dissolved organic matter (DOM) stimulate microbial growth by supplying organic carbon and DOM‐associated nutrients, and thus increase food availability for zooplankton. Terrestrial inputs of DOM might decrease the content of eicosapentaenoic acid (EPA) in particular organic matter (POM) due to an increase in biomass of EPA‐poor microbes, for example, heterotrophic bacteria and autotrophic cyanobacteria, thereby reducing food quality and filter‐feeding zooplankton's biomass. We performed a 26‐d mesocosm experiment where terrestrial DOM was manipulated by adding (treatments) and kept without adding (controls) 13 C‐labeled maize leachate to evaluate the effect of food quality changes induced by terrestrial DOM inputs on zooplankton. DOM addition treatments had significantly higher concentrations of POM and Chlorophyll a relative to controls, but significant lower EPA content of POM, responding to increased biomass of bacteria and chlorophytes. Biomass and EPA content of filter‐feeding cladoceran Chydorus sphaericus was significantly reduced by terrestrial DOM addition. Stable isotope analyses showed 13 C enrichments in bacteria and cryptophytes in the treatment of 13 C‐labeled maize leachate, indicating a growth stimulation of heterotrophic microbes by organic carbon addition. Although the 13 C enrichment in Chydorus evidenced the extensive use of terrestrial DOM by this cladoceran, positive relationships between Chydorus biomass and EPA content of POM suggest that terrestrial DOM inputs increase food quality constrains on filter‐feeding zooplankton. Our study suggests that the response of filter‐feeding zooplankton to inputs of terrestrial DOM depends on how the terrestrial inputs change the microbial communities and thus the food quality in the receiving aquatic ecosystems.

Adsorption of multicomponent VOCs on various biomass-derived hierarchical porous carbon: A study on adsorption mechanism and competitive effect - Xinlei Huang; Minghui Tang; Hongxian Li; Ling Wang; Shengyong Lu (Chemosphere, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Alleviation of hypoxia stress induced oxidative damage, endoplasmic reticulum stress (ERS) and autophagy in grass carp (Ctenopharyngodon idellu) by TTO (Melaleuca alternifolia essential oil) - Ruoying Hu; Shiyu Wang; Lin Feng; Weidan Jiang; Pei Wu; Yang Liu; Xiaowan Jin; Shengyao Kuang; Ling Tang; Lu Zhang; Xiaoqiu Zhou (Aquaculture, 2023)

Dual-response fluorescent probe based on nitrogen-doped carbon dots and europium ions hybrid for ratiometric and on-site visual determination of oxytetracycline and tetracycline - Huifang Wu; Yubing Chen; Mengqi Xu; Yuwei Ling; Shiying Ju; Yanfeng Tang; Changlun Tong (Science of The Total Environment, 2023)

Characterizing formation mechanisms of secondary aerosols on black carbon in a megacity in South China - Jing Wei; Ying-Bo Niu; Meng-Xue Tang; Yan Peng; Li-Ming Cao; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2023)

Phospholipase A2 induces acute kidney injury by complement mediated mitochondrial apoptosis via TNF-α/NF-κB signaling pathway - Xin Tang; Tiantian Wei; Mingjing Guan; Peiyun Li; Yajun Pu; Lixin Cheng; Zhifeng Zhou; Ping Fu; Ling Zhang (Food and Chemical Toxicology, 2023)

Air pollutant emissions and reduction potentials from municipal solid waste incineration in China - Ling Tang; Jing Guo; Ruxing Wan; Min Jia; Jiabao Qu; Ling Li; Xin Bo (Environmental Pollution, 2023)

Unveiling the origin of high-efficiency charge transport effect of C3N5/C3N4 homojunction for activating peroxymonosulfate to degrade atrazine under visible light - Yaocheng Deng; Ling Li; Hao Zeng; Rongdi Tang; Zhanpeng Zhou; Yuchen Sun; Chengyang Feng; Daoxin Gong; Jiajia Wang; Ying Huang (Chemical Engineering Journal, 2023)

Enhancing ethylene glycol and ferric chloride pretreatment of rice straw by low-pressure carbon dioxide to improve enzymatic saccharification - Song Tang; Yan-ling Yu; Rukuan Liu; Shenghua Wei; Qin Zhang; Jie Zhao; Song Li; Qian Dong; Yan-bin Li; Yuanli Wang (Bioresource Technology, 2023)

Janus kinase inhibitor Tofacitinib alleviated acute hepatitis induced by lipopolysaccharide/D-galactosamine in mice - Xinyue Zhang; Ling Lin; Longjiang Li; Kai Hu; Ruyue Shao; Li Zhang; Li Tang; Min Zhu; Yuhua Ma; Yongqiang Yang (Molecular Biology Reports, 2023)

Phylogeny, gene structures, and expression patterns of the auxin response factor (GhARF2) in upland cotton (Gossypium hirsutum L.) - Maoni Chao; Jie Dong; Genhai Hu; Yanyan Li; Ling Huang; Jinbao Zhang; Jihua Tang; Qinglian Wang (Molecular Biology Reports, 2023)

Vitamin D deficiency leads to the abnormal activation of the complement system - Huan Li; Xiaomin Xie; Guirong Bai; Dan Qiang; Li Zhang; Huili Liu; Yanting He; Yanpan Tang; Ling Li (Immunologic Research, 2023)
Vitamin D deficiency can damage the human immune system, and the complement system is a key component of the immune system. This study aimed to elucidate the mechanism by which vitamin D affects the immune system by analyzing the changes in the protein expression of the complement system under different vitamin D levels. We selected 40 participants and divided them into three groups according to their serum levels of 25-hydroxyvitamin D (25(OH)VD): group A, 25(OH)VD ≥ 40 ng/mL; group B, 30 ng/mL ≤ 25(OH)VD < 40 ng/mL; and group C, 25(OH)VD < 30 ng/mL. Serum samples were subjected to biochemical analysis, followed by proteomic analysis using high-throughput untargeted proteomic techniques. Vitamin D deficiency increased the levels of fasting blood sugar, fasting serum insulin, and homeostasis model assessment (HOMA) of insulin resistance and decreased the secretion of HOMA of β-cell function, which led to insulin resistance and glucose metabolism disorder. Moreover, vitamin D deficiency resulted in the abnormal expression of 56 differential proteins, among which the expression levels of complement factor B, complement component C9, inducible co-stimulator ligand, and peptidase inhibitor 16 significantly changed with the decrease in vitamin D content. Functional enrichment analysis of these differential proteins showed that they were mainly concentrated in functions and pathways related to insulin secretion and inflammation. In conclusion, vitamin D deficiency not only contributes to insulin resistance and glucose metabolism disorder but also causes abnormal protein expression, resulting in the abnormal activation of the complement system. This study provides a novel theoretical basis for further studies on the relationship between vitamin D and the immune system.

An integrated monitoring system for disaster-causing organisms in the water intake areas of coastal nuclear power plants - Chao Li; Jian-ling Huo; Yu-ze Song; Lei Yang; Song-tang Liu (Frontiers in Marine Science, 2023)
Nowadays, nuclear power plays an important role in the energy structure of many countries. However, A bloom of a disaster-causing organism (DCO) in the cold-water intake area of a coastal nuclear power plant can block the water cooling system and seriously affect the operational safety of the nuclear power unit. Currently, the traditional method of protection is to estimate the DCO abundance by regular manual investigation and sampling, but that method cannot give continuous real-time data. Instead, proposed and implemented here is a seafloor in situ integrated monitoring system for DCOs (known as IMSDCO), which is equipped with an optical microscopic imager (OMI) and hydrometric sensors to monitor automatically the DCO abundance and hydrology. All the data are transmitted to a terminal in the shore station through a photoelectric composite cable for real-time display. When the DCO abundance reaches a preset threshold, software automatically raises an alarm. Since placing IMSDCO at the cold-water intake of the Changjiang nuclear power plant, a six-month field trial has been completed, during which large amounts of hydrology data and DCO images were obtained. IMSDCO successfully identified and estimated the abundances of various DCOs (e.g., Phaeocystis globosa , Acetes chinensis , and small fish) and predicted their movements based on hydrology data. Based on the analysis of the experimental data, we discussed the reasons for the error in the abundance estimation of DCO and the methods to reduce the error. The experimental results show that the OMI-based IMSDCO can monitor and give early warning of DCOs in the water intake areas of costal nuclear power plants and is worthy of long-term deployment.

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Morphological image analysis of biofilm evolution with quantitative analysis in a moving bed biofilm reactor - Xiaodong Wang; Shanshan Chen; Xuejun Bi; Ning Chen; Tang Yang; Ling Wang; Zakhar Maletskyi; Harsha Ratnaweera (Science of The Total Environment, 2023)

Impact of environmental factors on the ammonia-oxidizing and denitrifying microbial community and functional genes along soil profiles from different ecologically degraded areas in the Siding mine - Shuting Tang; Yin Rao; Shulian Huang; Yue Xu; Kaiyue Zeng; Xin Liang; Qiujie Ling; Kehui Liu; Jiangming Ma; Fangming Yu; Yi Li (Journal of Environmental Management, 2023)

Physical and mechanical properties of recycled aggregates modified by microbially induced calcium carbonate precipitation - Qiang Tang; Angran Tian; Cheng Ling; Yucheng Huang; Fan Gu (Journal of Cleaner Production, 2023)

Dietary cinnamaldehyde improves muscle protein content by promoting muscle fiber growth via PTP1B/IGF1/PI3K/AKTs-TOR/FOXO3a signaling pathway in grass carp (Ctenopharyngodon idella) - Yang Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Yan Peng; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

A novel machine learning method for evaluating the impact of emission sources on ozone formation - Yong Cheng; Xiao-Feng Huang; Yan Peng; Meng-Xue Tang; Bo Zhu; Shi-Yong Xia; Ling-Yan He (Environmental Pollution, 2023)

Engineering of Bi2O2CO3/Ti3C2Tx heterojunctions co-embedded with surface and interface oxygen vacancies for boosted photocatalytic degradation of levofloxacin - Ling Zhang; Lu Tan; Zhenxi Yuan; Boqi Xu; Weirui Chen; Yiming Tang; Laisheng Li; Jing Wang (Chemical Engineering Journal, 2023)

Alleviating the self-discharge and enhancing the polysulphides conversion kinetics with LaCO3OH nanocrystals decorated hierarchical porous carbon - Yuhang Lin; Weiqiang Tang; Siyu Wu; Yongzheng Zhang; Zhenkai Kong; Chunyin Shen; Yanli Wang; Liang Zhan; Licheng Ling (Chemical Engineering Journal, 2023)

An S-scheme CdS/K2Ta2O6 heterojunction photocatalyst for production of H2O2 from water and air - Cui Lai; Mengyi Xu; Fuhang Xu; Bisheng Li; Dengsheng Ma; Yixia Li; Ling Li; Mingming Zhang; Danlian Huang; Lin Tang; Shiyu Liu; Huchuan Yan; et al. (Chemical Engineering Journal, 2023)

Thin-walled vesicular Triazole-CN-PDI with electronic n→π* excitation and directional movement for enhanced atrazine photodegradation - Rongdi Tang; Hao Zeng; Daoxin Gong; Yaocheng Deng; Sheng Xiong; Ling Li; Zhanpeng Zhou; Jiajia Wang; Chengyang Feng; Lin Tang (Chemical Engineering Journal, 2023)

Insights into the dual Z-scheme and piezoelectricity co-driven photocatalyst for ultra-speed degradation of nitenpyram - Sheng Xiong; Hao Zeng; Yaocheng Deng; Chengyang Feng; Rongdi Tang; Zhanpeng Zhou; Ling Li; Jiajia Wang; Daoxin Gong (Chemical Engineering Journal, 2023)

Transcriptome analyses reveal the effects of mixed saline–alkali stress on indoleacetic acid and cytokinins in Malus hupehensis Rehd. leaves - Xin-Liang Wang; Ling Peng; Jian Wang; Jing-Lei Liu; Jing-Jing Jia; Li-Ping Tang (Physiology and Molecular Biology of Plants, 2023)

The putative ABCG transporter VviABCG20 from grapevine (Vitis vinifera) is strongly expressed in the seed coat of developing seeds and may participate in suberin biosynthesis - Ling Wang; Wang Yao; Xue Zhang; Yujin Tang; Steve Van Nocker; Yuejin Wang; Chaohong Zhang (Physiology and Molecular Biology of Plants, 2023)

A quantitative study of the influence of soil organic carbon and pore characteristics on the stability of aggregates of the karst peak-cluster depression area in Southwest China - Hui Wei; Yusong Deng; Juan Huang; Ling He; Qiuyue Tang; Yan Xiao (Journal of Soils and Sediments, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Brevibacillus daliensis sp. nov., Isolated From Soil in Machangqing Nature Reserve - Shi-Qiang Ye; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; Zhu-Feng Shi; et al. (Current Microbiology, 2023)

Transcriptome Analysis Provides an Overview of Genes Involved in the Peculiar Food Preference at First-Feeding Stage in Mandarin Fish (Siniperca chuatsi) - Ling Li; Shu-Lin Tang; Shan He; Xu-Fang Liang (Fishes, 2022)
The mandarin fish (Siniperca chuatsi) is an important economic fish species in China. Many carnivorous fish larvae feed on zooplankton or microdiets. However, the mandarin fish larvae feed on live prey fish exclusively, while refusing zooplankton or microdiets. A stable supply of palatable live prey fish results in high costs. Moreover, the application of live prey fish might bring the risk of pathogens. However, little is known about the genes underlying the food preference of mandarin fish larvae. Partial offspring of the domesticated strain could feed brine shrimp from three days post-hatching (dph), the open mouth day. In the present study, the mandarin fish larvae were randomly divided into three groups, then treated differently at 3 dph: (1) unfed; (2) fed with live prey fish; (3) fed with brine shrimp (Artemia). Differentially expressed genes were identified by RNA-seq. The differential expression of the transcription factors involved in retinal photoreceptor development and differentiation might contribute to the intake of brine shrimp in mandarin fish larvae. Meanwhile, the digestive enzyme genes involved in protein, fat, and carbohydrate digestion have been expressed in mandarin fish larvae at 3 dph, contributing to the digestion of ingested food. Our study provides an overview of genes and biological processes involved in the peculiar food preference at the first-feeding stage in mandarin fish larvae and has critical importance to the future application of non-fish live feeds in the culture of mandarin fish larvae.

Enhanced visible light-driven photodegradation of tetracycline by salicylic acid-modified graphitic carbon nitride and toxicity assessment - Mengmeng Chen; Mengxue Li; Peng Li; Stephanie Ling Jie Lee; Juanjuan Tang; Qian Li; Sijie Lin (Environmental Science and Pollution Research, 2022)

Effects of the Dicranopteris linearis root system and initial moisture content on the soil disintegration characteristics of gully erosion - Ling He; Yu-song Deng; Qiu-yue Tang; Da-lan Liao; Chao Wang; Xiao-qian Duan (Journal of Mountain Science, 2022)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Orphan nuclear receptor NUR77 relieves insulin resistance in HTR-8/SVneo trophoblast cells through activation of autophagy and insulin signaling - Ling Li; Yu Bai; Runyu Du; Lei Tang; Ling Li (Journal of Physiology and Biochemistry, 2022)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

Genome-Wide Identification and Expression Analysis of Thioredoxin (Trx) Genes in Seed Development of Vitis vinifera - Jingru Zhang; Ting Zhao; Fengdan Yan; Ling Wang; Yujin Tang; Yuejin Wang; Chaohong Zhang (Journal of Plant Growth Regulation, 2022)

Two new clerodane diterpenoids and a new pyran-2-one derivative with anti-neuroinflammatory activities from Croton crassifolius - Zhi-Peng Ling; Qing Tang; Can-Jie Li; Jin-Lin Tan; Hai-Yue Zhao; Yi-Kun Hao; Zhao-Chun Zhan; Zhong-Nan Wu; Yu-Bo Zhang; Qing Zheng; Guo-Cai Wang (Journal of Natural Medicines, 2022)

Stabilization of coarse-grained saline soil using microbially enhanced calcium carbonate deposition - Shengyi Cong; Liang Tang; Bo Wang; Xianzhang Ling; Lin Geng; Wenqiang Xing (Bulletin of Engineering Geology and the Environment, 2022)

β-Cyclodextrin-Grafted Chitosan Enhances Intestinal Drug Absorption and Its Preliminary Mechanism Exploration - Linghui Zou; Zhongbin Zhang; Jinqing Chen; Xu Yang; Yuyang Li; Jing Tang; Xiaolu Du; Ling Tang; Dan Liang; Xiaoyong Zhu; Jianfang Feng; Wenya Ding (AAPS PharmSciTech, 2022)

Comprehensive Transcriptome Analysis of Tea Crabapple (Malus hupehensis Rehd.) Roots Subjected to Mixed Saline–Alkali Stress - Xin-Liang Wang; Ling Peng; Jian Wang; Jing-Jing Jia; Li-Ping Tang (Plant Molecular Biology Reporter, 2022)

Halomonas faecis sp. nov., a halophilic bacterium isolated from human faeces - Zhu-Xiang Liu; Jin-Hua Chen; Ling-Ling Yang; Yu-Zhou Feng; Li-Ying Deng; Jian-Wu He; Shu-Kun Tang; Yi-Guang Chen (Extremophiles, 2022)

Cohnella mopanensis sp. nov., a new Gram-negative bacterium isolated from soil in Xinping Mountain National Forest Park - Jing Tang; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Shi-Qiang Ye; Cheng Ling; Meng-Yu Zhang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; et al. (Archives of Microbiology, 2022)

Efficient de novo assembly and modification of large DNA fragments - Shuangying Jiang; Yuanwei Tang; Liang Xiang; Xinlu Zhu; Zelin Cai; Ling Li; Yingxi Chen; Peishuang Chen; Yuge Feng; Xin Lin; Guoqiang Li; Jafar Sharif; et al. (Science China Life Sciences, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Geographic distance, sedimentation, and substrate shape cryptic crustose coralline algal assemblages in the world’s largest subtropical intertidal algal reef - Shing Hei Zhan; Ling Chen; Chen‐Pan Liao; Wun‐Ruei Chang; Cheng‐Chin Li; Guang‐You Tang; Ching‐Yu Liou; Wei‐Lung Wang; Shih‐Wei Wang; Shao‐Lun Liu (Molecular Ecology, 2022)
Algal reefs, concreted by crustose coralline algae (CCA), are the main biotic reefs in temperate waters but rare in the subtropics and tropics. The world's largest known intertidal algal reef in the subtropics is the Taoyuan Algal Reef (TAR) located in the northwestern coast of Taiwan. The biodiversity and ecology of the TAR are scarcely explored, and now the reef is imperiled by industrialization. Here, we document cryptic species of CCA in Taiwan, particularly the TAR, by sequencing the psb A genes of over 1800 specimens collected across Taiwan. We also examine the ecological background of the TAR by surveying its benthic composition and measuring its environmental parameters. Our data reveal that the TAR harbours a high diversity of cryptic CCA species (27 molecular operational taxonomic units, or mOTUs), many of which are potentially new to science (18 mOTUs) and/or endemic to the TAR (9 mOTUs). Comparing the CCA species inventory of the TAR with the rest of Taiwan shows that the TAR represents a unique hotspot of CCA taxa in the waters of Taiwan. Our analyses show that variation in the CCA assemblages in the TAR is associated with geographic distance, sedimentation, and substrate type (for example, reef vs. hermit crab shell), suggesting that dispersal limitation and contemporary environmental selection shape the CCA assemblages in the TAR. The data from this study can inform the monitoring of human impacts on the health of the TAR and contribute to our understanding of the ecological processes underlying algal reef development.

Shear-wave velocity structures of the shallow crust beneath the Ordos and Sichuan Basins from multi-frequency direct P-wave amplitudes in receiver functions - Chenxiao Tang; Ling Chen; Xu Wang (Science China Earth Sciences, 2022)

A deep learning-based approach to automatic proximal femur segmentation in quantitative CT images - Yu Deng; Ling Wang; Chen Zhao; Shaojie Tang; Xiaoguang Cheng; Hong-Wen Deng; Weihua Zhou (Medical & Biological Engineering & Computing, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Removal of toluene and SO2 by hierarchical porous carbons: a study on adsorption selectivity and mechanism - Xinlei Huang; Hongxian Li; Ling Wang; Minghui Tang; Shengyong Lu (Environmental Science and Pollution Research, 2022)

Effect of jet airflow deflection on cleaning performance of filter cartridge - Ling Ren; Na Yuan; Longyuan Lin; Chunhong He; Cuiying Tang; Zhiyong Xu (Environmental Science and Pollution Research, 2022)

Screening and identification of HLA-A2-restricted neoepitopes for immunotherapy of non-microsatellite instability-high colorectal cancer - Ranran Shi; Yubing Li; Ling Ran; Yu Dong; Xiuman Zhou; Jingwen Tang; Lu Han; Mingshuang Wang; Liwei Pang; Yuanming Qi; Yahong Wu; Yanfeng Gao (Science China Life Sciences, 2022)

Effect of confining pressure on mechanics and deformation behavior of sandstone containing a single inclined joint - Jin-Zhou Tang; Sheng-Qi Yang; Wen-Ling Tian; Yan Tao (European Journal of Environmental and Civil Engineering, 2022)

Electroacupuncture Enhance Therapeutic Efficacy of Mesenchymal Stem Cells Transplantation in Rats With Intracerebral Hemorrhage - Li Deng; Ling Zhou; Yan Zhu; Guangbi Fan; Huajun Tang; Yujie Zheng; Xiaoqing Gao; Kan Guo; Peng Zhou; Chaoxian Yang (Stem Cell Reviews and Reports, 2022)

Functional Mechanism of Antimicrobial Peptide Bomidin and Its Safety for Macrobrachium rosenbergii - Miao Zhang; Youli Yu; Lele Lian; Wanjun Li; Jianluan Ren; Ying Liang; Feng Xue; Fang Tang; Xiaohua Zhu; Jianqun Ling; Jianjun Dai (Probiotics and Antimicrobial Proteins, 2022)

Promoting larval settlement of coral Pocillopora damicornis by calcium - Qingsong Yang; Wenqian Zhang; Ying Zhang; Xiaoyu Tang; Juan Ling; Yanying Zhang; Junde Dong (Coral Reefs, 2022)

The lining responses for shallow mountain tunnels subjected to frost heaving - Xian-zhang Ling; Yuan Yu; Liang Tang; Lin Geng; Xiao Han (Journal of Mountain Science, 2022)

Long-Term Reproducibility of SIMS Zircon U-Pb Geochronology - Wenhao Zhao; Qiuli Li; Yu Liu; Guoqiang Tang; Xiaoxiao Ling; Jiao Li; Xianhua Li (Journal of Earth Science, 2022)

40Ar/39Ar Ages and Geochemistry of Seamount Basalts from the Western Pacific Province - Qian Liu; Limei Tang; Ling Chen; Peng Gao (Journal of Marine Science and Engineering, 2022)
Seamounts are features generated by hot spots and associated intraplate volcanic activity. The geochemical characteristics of igneous rocks constituting seamounts provide evidence of important details of dynamic processes in the Earth, such as mantle magma source areas, and are key to understanding how mantle plume processes control the formation and evolution of seamounts and their resulting geochemical characteristics. The Pacific Ocean contains a large number of hitherto unstudied seamounts, whose ages and geochemical characteristics remain poorly known. This study presents the geochemical characteristics of six basalt samples from five seamounts in the Western Pacific and the 40Ar/9Ar ages of three samples are determined. The new analysis yielded 40Ar/39Ar ages for seamounts samples MP3D21, MP5D11, and MP5D15A of 95.43 ± 0.33, 62.4 ± 0.26, and 99.03 ± 0.4 Ma, respectively. The geochemical profiles of seamounts samples MP3D04, MP3D21, MP5D11, MP5D15A, MPID201, and MPID202 are consistent with alkaline basalts, as evidence by alkali-rich, silicon-poor compositions along with high titanium concentrations. The primitive mantle normalized rare-earth elements and trace elements spider pattern are similar to those of ocean island basalts. The Ta/Hf and Nb/Zr ratios and La/Zr-Nb/Zr discriminant diagrams indicate that the six seamounts formed from magma that originated in the deep mantle.

Lack of miRNA-17 family mediates high glucose-induced PAR-1 upregulation in glomerular mesangial cells - Zhuang-Zhuang Tang; Pan-Pan Gu; Xiao-Fei An; Ling-Shan Gou; Yao-Wu Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Recent advancements in enzyme engineering via site-specific incorporation of unnatural amino acids - Hang-Qin Zhu; Xiao-Ling Tang; Ren-Chao Zheng; Yu-Guo Zheng (World Journal of Microbiology and Biotechnology, 2021)

Standard litterbags underestimate early-stage lower-order root decomposition rate in a subtropical forest, China - Guan-tao Chen; Yu-qin Chen; Yong Peng; Hong-ling Hu; Jiu-long Xie; Gang Chen; Yin-long Xiao; Li Liu; Yi Tang; Li-hua Tu (Plant and Soil, 2021)

Characteristics and distribution of microplastics in the surface water of the Songhua River in China - Shuyuan Tang; Ling Gao; Hongze Gao; Donglei Zou (Environmental Science and Pollution Research, 2021)

Identification of HvLRX, a new dehydration and light responsive gene in Tibetan hulless barley (Hordeum vulgare var. nudum) - Junjun Liang; Haili Zhang; Ling Yi; Yawei Tang; Hai Long; Maoqun Yu; Guangbing Deng (Genes & Genomics, 2021)

Effects of Selenium on the Immunotoxicity of Subacute Arsenic Poisoning in Chickens - Zhihua Ren; Qiang Wu; Huidan Deng; Yueru Yu; Wenjiao Tang; Youtian Deng; Ling Zhu; Ya Wang; Junliang Deng (Biological Trace Element Research, 2021)

Petrogenesis and tectonic implication of lavas from the Yap Trench, western Pacific - Ling Chen; Limei Tang; Jichao Yang; Xiaohu Li; Wei Wang; Fengyou Chu; Jie Zhang (Acta Oceanologica Sinica, 2021)

Carbon transfer from the submerged macrophyte Hydrilla verticillata to zooplankton: a 13C-labeled mesocosm study - Ling Su; Zongan Jin; Lichao Xie; Yali Tang; Zhengwen Liu; Ping Zhong; Yaling Su; Qiuqi Lin (Hydrobiologia, 2021)

Influence of wet flue gas desulfurization on the pollutants monitoring in FCC flue gas - Feng Ju; Cong Wu; Hui Luan; Zhihe Tang; Helin Pan; Hui Pan; Guangli Xiu; Hao Ling (Environmental Science and Pollution Research, 2021)

LncRNA LINC00689 Promotes the Tumorigenesis of Glioma via Mediation of miR-526b-3p/IGF2BP1 Axis - Wen-Liang Zhan; Ning Gao; Guo-Long Tu; Hong Tang; Ling Gao; Ying Xia (NeuroMolecular Medicine, 2021)

Molecular identification and characterization of ‘Candidatus Phytoplasma asteris’-related strain associated with pepper (Capsicum annuum L.) yellow crinkle disease in China - Shao-shuai Yu; Qing-hua Tang; Deng-qiang Fu; Rui-ling Zhao; Wei-wei Song; Wei Yan; Wei-quan Qin (Journal of General Plant Pathology, 2021)

Modulation of the 5-HT 3 A receptor current by desacylbaldrinal - Li-Xia Wang; Hu-Lan Chen; Hong-Ling Yan; Fei Tang; Hai Zhang; Hong-Xiang Li; Qiang Ye; Cheng Peng; Yu-Zhu Tan (Natural Product Research, 2021)

The major photoprotective role of anthocyanins in leaves of Arabidopsis thaliana under long-term high light treatment: antioxidant or light attenuator? - Xiao-Ting Zheng; Zheng-Chao Yu; Jun-Wei Tang; Min-Ling Cai; Yi-Lin Chen; Cheng-Wei Yang; Wah Soon Chow; Chang-Lian Peng (Photosynthesis Research, 2021)

Face stability of the slurry shield–driven tunnel with an impermeable filter cake in saturated medium sand - Xianzhang Ling; Xiangxun Kong; Liang Tang; Wenchong Tang; Shengyi Cong; Juan Zhang; Xiangping Zhao (Arabian Journal of Geosciences, 2021)

Assessing the impact of climate change on the distribution of Osmanthus fragrans using Maxent - Fen Kong; Ling Tang; Huan He; Fuxia Yang; Jun Tao; Weicheng Wang (Environmental Science and Pollution Research, 2021)

Role of the mitochondrial citrate-oxoglutarate carrier in lipid accumulation in the oleaginous fungus Mortierella alpina - Fengzhu Ling; Xin Tang; Hao Zhang; Yong Q. Chen; Jianxin Zhao; Haiqin Chen; Wei Chen (Biotechnology Letters, 2021)

Efficient strategies to enhance plasmid stability for fermentation of recombinant Escherichia coli harboring tyrosine phenol lyase - Xiao-Ling Tang; Wen-Ye Hu; Zhi-Chao Wang; Ren-Chao Zheng; Yu-Guo Zheng (Biotechnology Letters, 2021)

Characterization of Organic Aerosol at a Rural Site in the North China Plain Region: Sources, Volatility and Organonitrates - Qiao Zhu; Li-Ming Cao; Meng-Xue Tang; Xiao-Feng Huang; Eri Saikawa; Ling-Yan He (Advances in Atmospheric Sciences, 2021)

Effects of the Deep Pool on Groundwater Flow and Salinization in Coastal Reservoir and Adjacent Aquifer - Yuming Mo; Guangqiu Jin; Chenming Zhang; Jing Xu; Hongwu Tang; Chengji Shen; Alexander Scheuermann; Ling Li (Water Resources Management, 2021)

Genome-Wide Identification and Expression Analysis of Heavy Metal Stress–Responsive Metallothionein Family Genes in Nicotiana tabacum - Qin Yu; Linshen He; Chunsong Huo; Xiaohan Jiang; Hua Chen; Run Wang; Minzhi Tang; Ling Dong; Ji Chen; Yonghao Li; Shunqin Zhu; Wanhong Liu (Plant Molecular Biology Reporter, 2021)

Correction to: Effects of zinc oxide nanoparticles on arsenic stress in rice (Oryza sativa L.): germination, early growth, and arsenic uptake - Fan Wu; Qing Fang; Shiwei Yan; Ling Pan; Xianjin Tang; Wenling Ye (Environmental Science and Pollution Research, 2021)

Simplified calculation method for cumulative deformations of marine structured clay under cyclic loading - Meng Zang; Ling-wei Kong; Rong-tang Zhang; Wei-wei Wang (Arabian Journal of Geosciences, 2021)

Vallisneria natans detritus supports Daphnia magna somatic growth and reproduction under addition of periphyton - Yali Tang; Daiying Zhou; Ling Su; Zhengwen Liu; Xiufeng Zhang; Henri J. Dumont (Aquatic Ecology, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

A Functional Polymorphism in HIF-3α Is Related to an Increased Risk of Ischemic Stroke - Xi-Xi Gu; Zhuan-Zhi Tang; Yong-Ling He; Zhi-Neng Zeng; Wu-Xiang Shi; Yong-Chao Qiao; Ye-Sheng Wei (Journal of Molecular Neuroscience, 2021)
Hypoxia-inducible factor-3α ( HIF-3α ), a member of HIF family, can mediate adaptive responses to low oxygen and ischemia. It is believed that HIF plays crucial roles in stroke-related diseases. However, there are no reports on the association between HIF-3α genetic variants and ischemic stroke (IS) susceptibility. Therefore, we examined the association between HIF- 3α gene polymorphisms (rs3826795, rs2235095, and rs3764609) and IS risk. The study population included 302 controls and 310 patients with ischemic stroke. Three polymorphisms in HIF- 3α (rs3826795, rs2235095, and rs3764609) were genotyped using SNPscan technique. Our study showed a strong association of rs3826795 in HIF-3α with the risk of IS. The genotype and allele frequencies were shown to differ between the two groups. The rs3826795 in an intron of HIF-3α was related to a prominent increased IS risk (AA vs GG adjusted odd ratio [OR], 2.21; 95% confidence intervals [95% CI], 1.10–4.44; P = 0.03; AA vs AG/GG OR = 1.74, 95% CI, 1.02–2.97, P = 0.04; A vs G OR = 1.48, 95% CI, 1.05–2.07, P = 0.02). Logistic regression analysis suggested that rs3826795 posed a risk factor for IS in addition to common factors. Furthermore, when compared to controls, increased levels of homocysteic acid and level of non-esterified fatty acid were found in the cases ( P < 0.01). However, no significant association was found between rs2235095 or rs3264609 and IS risk. These findings indicated that the rs3826795 polymorphism may be a potential target for predicting the risk of IS.

Physical interactions facilitate sex change in the protogynous orange‐spotted grouper, Epinephelus coioides - Jiaxing Chen; Cheng Peng; Jingjun Huang; Herong Shi; Ling Xiao; Lin Tang; Haoran Lin; Shuisheng Li; Yong Zhang (Journal of Fish Biology, 2021)
Sex change in teleost fishes is commonly regulated by social factors. In species that exhibit protogynous sex change, such as the orange‐spotted grouper Epinephelus coioides , when the dominant males are removed from the social group, the most dominant female initiates sex change. The aim of this study was to determine the regulatory mechanisms of socially controlled sex change in E. coioides . We investigated the seasonal variation in social behaviours and sex change throughout the reproductive cycle of E. coioides , and defined the behaviour pattern of this fish during the establishment of a dominance hierarchy. The social behaviours and sex change in this fish were affected by season, and only occurred during the prebreeding season and breeding season. Therefore, a series of sensory isolation experiments was conducted during the breeding season to determine the role of physical, visual and olfactory cues in mediating socially controlled sex change. The results demonstrated that physical interactions between individuals in the social groups were crucial for the initiation and completion of sex change, whereas visual and olfactory cues alone were insufficient in stimulating sex change in dominant females. In addition, we propose that the steroid hormones 11‐ketotestosterone and cortisol are involved in regulating the initiation of socially controlled sex change.

Resveratrol-induced apoptosis is associated with regulating the miR-492/CD147 pathway in malignant melanoma cells - Shuang Zhao; Ling Tang; Wangqing Chen; Juan Su; Fangfang Li; Xiang Chen; Lisha Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Rescue effects of Se-enriched rice on physiological and biochemical characteristics in cadmium poisoning mice - Yang Su; Ling Li; Muhammad Umer Farooq; Xin Huang; Tengda Zheng; Yu Jie Zhang; Hla Hla Ei; Faiz Hussain Panhwar; Zhichen Tang; Rui Zeng; Yuanke Liang; Xiaoying Ye; et al. (Environmental Science and Pollution Research, 2021)

Regulating CH4, N2O, and NO emissions from an alkaline paddy field under rice–wheat rotation with controlled release N fertilizer - Ting Lan; Heng Zhang; Yong Han; Ouping Deng; Xiaoyan Tang; Ling Luo; Jian Zeng; Guangdeng Chen; Changquan Wang; Xuesong Gao (Environmental Science and Pollution Research, 2021)

Activity evolution of landslides and debris flows after the Wenchuan earthquake in the Qipan catchment, Southwest China - Qing-yun Shi; Chuan Tang; Ling-feng Gong; Ming Chen; Ning Li; Wei Zhou; Jiang Xiong; Hai Tang; Xiao-di Wang; Ming-wei Li (Journal of Mountain Science, 2021)

2,3,5,6-Tetramethylpyrazine protects retinal photoreceptors against endoplasmic reticulum stress by modulating ATF4-mediated inhibition of PRP aggregation - Hao Huang; Xiaobo Zhu; Hao Cheng; Xielan Kuang; Chongde Long; Xizhi Deng; Yuxiu Zou; Han Zhang; Yue Xing; Xiangtian Ling; Renchun Wang; Han Tang; et al. (Journal of Molecular Medicine, 2021)

Upregulation of miR-144-3p protects myocardial function from ischemia–reperfusion injury through inhibition of TMEM16A Ca2+-activated chloride channel - Guoxun Yang; Xiao Tang; Ling Tan; Danpeng Nong; Peng Yang; Haien Ning (Human Cell, 2021)

Silver Nanoparticles Induced Oxidative Stress and Mitochondrial Injuries Mediated Autophagy in HC11 Cells Through Akt/AMPK/mTOR Pathway - Jin Hou; Ling Zhao; Huaqiao Tang; Xiaoli He; Gang Ye; Fei Shi; Min Kang; Helin Chen; Yinglun Li (Biological Trace Element Research, 2021)

A coupled UV photolysis-biodegradation process for the treatment of decabrominated diphenyl ethers in an aerobic novel bioslurry reactor - Yi-Tang Chang; Huei-Chen Chen; Hsi-Ling Chou; Hui Li; Stephen A. Boyd (Environmental Science and Pollution Research, 2021)

Post-mining failure characteristics of rock surrounding coal seam roadway and evaluation of rock integrity: a case study - Qiang-ling Yao; Qiang Xu; Jiang-feng Liu; Liu Zhu; Dong-wei Li; Chuan-jin Tang (Bulletin of Engineering Geology and the Environment, 2021)

Study on Characteristics of Shear Modulus of Zhanjiang Structured Clay During Triaxial Shearing - Meng Zang; Ling-wei Kong; Rong-tang Zhang; Wei-wei Wang (Geotechnical and Geological Engineering, 2021)

MicroRNA-143–5p modulates pulmonary artery smooth muscle cells functions in hypoxic pulmonary hypertension through targeting HIF-1α - Bi Tang; Ming-ming Tang; Qing-mei Xu; Jian-lu Guo; Ling Xuan; Jing zhou; Xiao-jing Wang; Heng Zhang; Pin-fang Kang (Journal of Biosciences, 2020)

Comparative analysis of microsatellite and SNP markers for parentage testing in the golden snub-nosed monkey (Rhinopithecus roxellana) - Chen Ling; Wu Lixia; Hou Rong; Shen Fujun; Zhang Wenping; Tang Yao; Yuan Yaohua; Zhao Bo; Zhang Liang (Conservation Genetics Resources, 2020)
Microsatellite markers are popular for assigning parentage, but single-nucleotide polymorphisms (SNPs) have only been applied in this area recently. To evaluate these two markers which have been previously studied in golden snub-nosed monkeys, we genotyped 12 individuals using 37 microsatellite loci and 37 SNP markers. The data showed that 32 of 37 microsatellite loci were polymorphic, and most microsatellite loci were high informative (mean PIC = 0.599). Meanwhile, 24 of 37 SNP markers were polymorphic and most were low informative (mean PIC = 0.244). For microsatellites, the combined exclusion probability with one-parent-unknown/known (CE-1P/CE-2P) nearly reached 1, while for the SNP markers, CE-2P only reached 0.9582. Under the condition of one parent known/unknown, the CE-2P and CE-1P could meet the international human parental standard (0.9973) by using five or nine microsatellite loci respectively. For SNP markers, we doubled the loci (n = 48) and simulated parentage testing, and the data showed that the CE-2P was 0.998 while the CE-1P was still low. This result indicated that the SNP loci which we used here had low polymorphism and that more loci need to be developed in the future. In addition, we corrected one case of failed identification by excluding siblings and reducing the range of candidate paternities.

Performance, kinetics characteristics and enhancement mechanisms in anammox process under Fe(II) enhanced conditions - Si-min Tang; Ze-hao Xu; Ya-lei Liu; Guang-feng Yang; Jun Mu; Ren-cun Jin; Qiao Yang; Xiao-ling Zhang (Biodegradation, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Sleep deprivation aggravated lipopolysaccharide/d-galactosamine-induced acute liver injury by suppressing melatonin production - Lu Liu; Li Zhang; Longjiang Li; Mengting Chen; Zhe Wang; Yi Shen; Jiayi Huang; Ling Tang (Inflammation Research, 2020)

Establishment of regeneration system of callus pathway for Iris sanguinea Donn ex Horn - Huan Liu; Lijuan Fan; Hong Song; Biao Tang; Ling Wang (In Vitro Cellular & Developmental Biology - Plant, 2020)

Geological characteristics of the Nankai Trough subduction zone and their tectonic significances - Jie Zhang; Ling Chen; Zihua Cheng; Limei Tang (Acta Oceanologica Sinica, 2020)

Transcriptome analysis of different rice cultivars provides novel insights into the rice response to bacterial leaf streak infection - Ling Lu; Dewei Yang; Dingzhong Tang; Shengping Li; Zhiwei Chen (Functional & Integrative Genomics, 2020)

Production, safety, health effects and applications of diacylglycerol functional oil in food systems: a review - Yee-Ying Lee; Teck-Kim Tang; Eng-Tong Phuah; Chin-Ping Tan; Yong Wang; Ying Li; Ling-Zhi Cheong; Oi-Ming Lai (Critical Reviews in Food Science and Nutrition, 2020)

Microscopic Experimental Analysis of the Accumulated Plastic Strain on a Silty Soil Around a Tunnel Under a Subway Loading - Chunling Yan; Ling Zhang; Yiqun Tang (Geotechnical and Geological Engineering, 2020)

Cinnamaldehyde improves the growth performance and digestion and absorption capacity in grass carp (Ctenopharyngodon idella) - Yang Zhou; Wei-Dan Jiang; Jin-Xiu Zhang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Yan Peng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

The dynamic process of dietary soybean β-conglycinin in digestion, absorption, and metabolism among different intestinal segments in grass carp (Ctenopharyngodon idella) - Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Bei-Ping Tan; Qi-Hui Yang; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Role of adjuvant (chemo)radiotherapy for resected extrahepatic cholangiocarcinoma: a meta-analysis - Xin-qi Shi; Jing-yu Zhang; Hua Tian; Ling-na Tang; Ai-lin Li (Journal of Zhejiang University-SCIENCE B, 2020)

MicroRNA-153-3p enhances the sensitivity of chronic myeloid leukemia cells to imatinib by inhibiting B-cell lymphoma-2-mediated autophagy - Yu-Ling Li; Jia-Ming Tang; Xiao-Yun Chen; Bing Luo; Guo-Hua Liang; Qian Qu; Zi-Yuan Lu (Human Cell, 2020)

Effects of zinc oxide nanoparticles on arsenic stress in rice (Oryza sativa L.): germination, early growth, and arsenic uptake - Fan Wu; Qing Fang; Shiwei Yan; Ling Pan; Xianjin Tang; Wenling Ye (Environmental Science and Pollution Research, 2020)

Molecular dynamics simulation of the interaction of water and humic acid in the adsorption of polycyclic aromatic hydrocarbons - Nan Zhao; Feng Ju; Hui Pan; Zhihe Tang; Hao Ling (Environmental Science and Pollution Research, 2020)

Identification, association, and expression analysis of ZmNAC134 gene response to phosphorus deficiency tolerance traits in maize at seedling stage - Javed Hussain Sahito; Fei Zheng; Haitao Tang; Xuan He; Bowen Luo; Xiao Zhang; Peng Ma; Xin Ding; Dan Liu; Ling Wu; Shibin Gao (Euphytica, 2020)

Short-term associations between ambient fine particulate matter pollution and hospital visits for chronic obstructive pulmonary disease in Yinzhou District, China - Cheng-yi Lin; Die Li; Jie-ming Lu; Zhe-bin Yu; Yao Zhu; Peng Shen; Meng-ling Tang; Ming-juan Jin; Hong-bo Lin; Li-ming Shui; Kun Chen; Jian-bing Wang (Environmental Science and Pollution Research, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Estimation of future extreme precipitation changes in Xinjiang based on RegCM4.4 simulations - Tang Xiang-ling; Lv Xin; Zhang Yanwei (Natural Hazards, 2020)

Experimental study on phosphorus release from sediment with fresh-water snail (Bellamya aeruginosa) bioturbation in eutrophic lakes - Yanqing Yang; Jianyun Zhang; Ling Liu; Guoqing Wang; Musong Chen; Yi Zhang; Xiongpeng Tang (Journal of Soils and Sediments, 2020)

Leukocyte immunoglobulin-like receptor B4 protects against cardiac hypertrophy via SHP-2-dependent inhibition of the NF-κB pathway - Heng Zhou; Ning Li; Yuan Yuan; Ya-Ge Jin; Qingqing Wu; Ling Yan; Zhou-Yan Bian; Wei Deng; Di-Fei Shen; Hongliang Li; Qi-Zhu Tang (Journal of Molecular Medicine, 2020)

Effects of botanical pesticide itol A against the tobacco cutworm, Spodoptera litura (Fab.) - Si-Quan Ling; Bo He; Dong-Qiang Zeng; Wen-Wei Tang (Environmental Science and Pollution Research, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Enhanced production of l-methionine in engineered Escherichia coli with efficient supply of one carbon unit - Xiao-Ling Tang; Xu-Yuan Du; Lu-Jia Chen; Zhi-Qiang Liu; Yu-Guo Zheng (Biotechnology Letters, 2020)

Two novel strains, Bacillus albus JK-XZ3 and B. velezensis JK-XZ8, with activity against Cerasus crown gall disease in Xuzhou, China - Peng Yan; Xi-Tang Zhang; Long-Jiao Hu; Ya-Hui Wang; Mei-Ling Zhu; Xiao-Qin Wu; Fei Chen (Australasian Plant Pathology, 2020)

Characterization and application of a gall midge resistance gene (Gm6) from Oryza sativa ‘Kangwenqingzhan’ - Yang Li; Yi Mo; Zhihua Li; Meng Yang; Lihua Tang; Ling Cheng; Yongfu Qiu (Theoretical and Applied Genetics, 2020)

Fungal endophytic communities of two wild Rosa varieties and the role of an endophytic Seimatosporium sp. in enhancing host plant powdery mildew resistance - Yi Zhao; Xiu-ling Ji; Ting Shen; Wen-ting Tang; Shao-shi Li; Zheng-qing Zhu; Jitendra Kumar; Hai-yan Li (Plant and Soil, 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

Enzyme-treated soy protein supplementation in low protein diet improved flesh tenderness, juiciness, flavor, healthiness, and antioxidant capacity in on-growing grass carp (Ctenopharyngodon idella) - Yan Song; LiangChao Yan; WeiDan Jiang; WeiWei Xiao; Lin Feng; Pei Wu; Yang Liu; ShengYao Kuang; Ling Tang; XiaoQiu Zhou (Fish Physiology and Biochemistry, 2020)

High dietary lipid level alters the growth, hepatic metabolism enzyme, and anti-oxidative capacity in juvenile largemouth bass Micropterus salmoides - Yue-Lang Zhou; Jia-Ling Guo; Ren-Jun Tang; Hui-Jia Ma; Yong-Jun Chen; Shi-Mei Lin (Fish Physiology and Biochemistry, 2020)

Correction to: Effect of enzymatic hydrolysate of cottonseed protein supplementation on growth performance and intestinal health of nursery pigs in Thailand - Wacharaporn Tanumtuen; Seksom Attamangkune; Ling Tang; Qiang Zhang; Wei-Wei Xiao; Sen Liu; Yuwares Ruangpanit (Tropical Animal Health and Production, 2020)

Effect of enzymatic hydrolysate of cottonseed protein supplementation on growth performance and intestinal health of nursery pigs in Thailand - Wacharaporn Tanumtuen; Seksom Attamangkune; Ling Tang; Qiang Zhang; Wei-Wei Xiao; Sen Liu; Yuwares Ruangpanit (Tropical Animal Health and Production, 2020)

Physiologically Based Pharmacokinetic Modeling of Oxycodone in Children to Support Pediatric Dosing Optimization - Liang Zheng; Miao Xu; Shi-wei Tang; Hao-xin Song; Xue-hua Jiang; Ling Wang (Pharmaceutical Research, 2019)

Geochemical behaviors of antimony in mining-affected water environment (Southwest China) - Ling Li; Han Tu; Shui Zhang; Linna Wu; Min Wu; Yang Tang; Pan Wu (Environmental Geochemistry and Health, 2019)

Capability of Fengyun-3D Satellite in Earth System Observation - Zhongdong Yang; Peng Zhang; Songyan Gu; Xiuqin Hu; Shihao Tang; Leiku Yang; Na Xu; Zhaojun Zhen; Ling Wang; Qiong Wu; Fangli Dou; Ruixia Liu; et al. (Journal of Meteorological Research, 2019)

A GARP transcription factor anther dehiscence defected 1 (OsADD1) regulates rice anther dehiscence - Yanjia Xiao; Shimin You; Weiyi Kong; Qianying Tang; Wenting Bai; Yue Cai; Hai Zheng; Chaolong Wang; Ling Jiang; Chunming Wang; Zhigang Zhao; Jianmin Wan (Plant Molecular Biology, 2019)

Stress associated protein 1 regulates the development of glandular trichomes in Artemisia annua - Yuting Wang; Xueqing Fu; Lihui Xie; Wei Qin; Ling Li; Xiaofen Sun; Shihai Xing; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Carbon-based magnetic nanocomposite as catalyst for persulfate activation: a critical review - Ya Pang; Kun Luo; Lin Tang; Xue Li; Jiangfang Yu; Junyuan Guo; Yuanyuan Liu; Zhu Zhang; Ran Yue; Ling Li (Environmental Science and Pollution Research, 2019)

OsVIN2 encodes a vacuolar acid invertase that affects grain size by altering sugar metabolism in rice - Xinyang Xu; Yulong Ren; Chunming Wang; Huan Zhang; Fan Wang; Jun Chen; Xi Liu; Tianhui Zheng; Maohong Cai; Zhaoqiong Zeng; Liang Zhou; Shanshan Zhu; et al. (Plant Cell Reports, 2019)

Soybean glycinin decreased growth performance, impaired intestinal health, and amino acid absorption capacity of juvenile grass carp (Ctenopharyngodon idella) - Ya-Lin Zhang; Xu-Dong Duan; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Wu-Neng Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2019)

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

Insights into the Origin of Natural Gas Reservoirs in the Devonian System of the Marsel Block, Kazakhstan - Qianwen Li; Xiongqi Pang; Ling Tang; Wei Li; Kun Zhang; Tianyu Zheng; Xue Zhang (Journal of Earth Science, 2019)

Neferine inhibits LPS-ATP-induced endothelial cell pyroptosis via regulation of ROS/NLRP3/Caspase-1 signaling pathway - Yang-Shuo Tang; Yan-Hua Zhao; Yong Zhong; Xiao-Zhao Li; Jia-Xi Pu; Yan-Cheng Luo; Qiao-Ling Zhou (Inflammation Research, 2019)

Molecular cloning and functional characterization of a seed-specific VvβVPE gene promoter from Vitis vinifera - Peijie Gong; Rong Wei; Yan Li; Ruipu Wang; Yujin Tang; Ling Wang; Huijun Zhu; Yuejin Wang; Chaohong Zhang (Planta, 2019)

Rice OsHAK16 functions in potassium uptake and translocation in shoot, maintaining potassium homeostasis and salt tolerance - Huimin Feng; Qiang Tang; Jin Cai; Benchao Xu; Guohua Xu; Ling Yu (Planta, 2019)

Geochemistry of peridotites from the Yap Trench, Western Pacific: implications for subduction zone mantle evolution - Ling Chen; Limei Tang; Xiaohu Li; Yanhui Dong; Xing Yu; Weiwei Ding (International Geology Review, 2019)

Distinct evolutionary origins of common multi-drug resistance phenotypes in Salmonella typhimurium DT104: a convergent process for adaptation under stress - Le Tang; Song-Ling Zhu; Xin Fang; Yong-Guo Li; Cornelis Poppe; Randal N. Johnston; Gui-Rong Liu; Shu-Lin Liu (Molecular Genetics and Genomics, 2019)

Genome-wide Identification, Phylogenetic Analysis, and Expression Profiling of CONSTANS-like (COL) Genes in Vitis vinifera - Ling Wang; Jingyi Xue; Weina Dai; Yujin Tang; Peijie Gong; Yuejin Wang; Chaohong Zhang (Journal of Plant Growth Regulation, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Polymorphisms in the APOBEC3G gene of Chinese rhesus macaques affect resistance to ubiquitination and degradation mediated by HIV-2 Vif - Zhi-Qiang Jiang; Xu-Rong Yao; Hang Yu; Yue-Er Lu; Bei-Lei Liu; Feng-Liang Liu; Ya-Bin Jin; Min Zhuo; Yong-Tang Zheng; Fei Ling (Archives of Virology, 2019)

Epidemiological trends and virological traits of hepatitis B virus infection in pregnant women and neonates - Ting-Ting Peng; Qiu-E Cai; Min Yang; Shao-Ping Chen; Feng Chen; Miao Wang; Ling Peng; Gary Wong; Chen-Guang Shen; Wen-Bing Cheng; Sai-Yun Liu; Ya-Bai Peng; et al. (Archives of Virology, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

FLOURY ENDOSPERM15 encodes a glyoxalase I involved in compound granule formation and starch synthesis in rice endosperm - Xiaoman You; Wenwei Zhang; Jinlong Hu; Ruonan Jing; Yue Cai; Zhiming Feng; Fei Kong; Jie Zhang; Haigang Yan; Weiwei Chen; Xingang Chen; Jing Ma; et al. (Plant Cell Reports, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Identification and engineering of the key residues at the crevice-like binding site of lipases responsible for activity and substrate specificity - Xu Ding; Xiao-Ling Tang; Ren-Chao Zheng; Yu-Guo Zheng (Biotechnology Letters, 2019)

Geochemistry and age of seamounts in the West Pacific: mantle processes and petrogenetic implications - Limei Tang; Yanhui Dong; Fengyou Chu; Ling Chen; Weilin Ma; Yonggang Liu (Acta Oceanologica Sinica, 2019)

AAV-Vectored Fms-Related Tyrosine Kinase 3 Ligand Inhibits CD34+ Progenitor Cell Engraftment in Humanized Mice - Lijun Ling; Xian Tang; Xiuyan Huang; Jingjing Li; Hui Wang; Zhiwei Chen (Journal of Neuroimmune Pharmacology, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Cretaceous A-type volcanic–intrusive rocks and simultaneous mafic rocks along the Gan-Hang Tectonic Belt, Southeast China: petrogenesis and implications for the transition of crust–mantle interaction - Hong-Zuo Wang; Pei-Rong Chen; Kai-Xing Wang; Hong-Fei Ling; Jun-Qi Wu; Jiang-Wei Tang; You-Dong Zhao (International Geology Review, 2018)

Nitrogen additions reduce rhizospheric and heterotrophic respiration in a subtropical evergreen broad-leaved forest - Yong Peng; Guan-tao Chen; Shun Li; Hong-ling Hu; Ting-xing Hu; Li Liu; Yi Tang; Li-hua Tu (Plant and Soil, 2018)

An investigation of the influence of near-fault ground motion parameters on the pile’s response in liquefiable soil - Shuqing Hui; Liang Tang; Xiaoyu Zhang; Youqing Wang; Xianzhang Ling; Bowen Xu (Earthquake Engineering and Engineering Vibration, 2018)

Prognostic significance of combining high mobility group Box-1 and OV-6 expression in hepatocellular carcinoma - Jihui Zhu; Han Yu; Shuzhen Chen; Pinghua Yang; Zihui Dong; Yan Ling; Hao Tang; Shilei Bai; Wen Yang; Liang Tang; Feng Shen; Hongyang Wang; et al. (Science China Life Sciences, 2018)

Alternations of Metabolic Profile and Kynurenine Metabolism in the Plasma of Parkinson’s Disease - Kuo-Hsuan Chang; Mei-Ling Cheng; Hsiang-Yu Tang; Cheng-Yu Huang; Yih-Ru Wu; Chiung-Mei Chen (Molecular Neurobiology, 2018)

Identifying the driving factors of sediment delivery ratio on individual flood events in a long-term monitoring headwater basin - Ling-ling Wang; Wen-yi Yao; Jia-liang Tang; Wen-long Wang; Xin-xin Hou (Journal of Mountain Science, 2018)

Luteolin alleviates cardiac ischemia/reperfusion injury in the hypercholesterolemic rat via activating Akt/Nrf2 signaling - Jin-Ting Yang; Jue Wang; Xin-Ru Zhou; Chi Xiao; Yang-Yun Lou; Li-Hui Tang; Feng-Jiang Zhang; Ling-Bo Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Expression of BC1 Impairs Spatial Learning and Memory in Alzheimer’s Disease Via APP Translation - Tongmei Zhang; Pei Pang; Zemin Fang; Yu Guo; Hao Li; Xinyan Li; Tian Tian; Xin Yang; Wenting Chen; Shu Shu; Na Tang; Jianhua Wu; et al. (Molecular Neurobiology, 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

Antifungal activities and active ingredients of Melodinus suaveolens Champ. ex Benth. - Yanan Xu; Siquan Ling; Dongqiang Zeng; Wenwei Tang (Natural Product Research, 2018)

Rate-limiting steps in the Saccharomyces cerevisiae ergosterol pathway: towards improved ergosta-5,7-dien-3β-ol accumulation by metabolic engineering - Bin-Xiang Ma; Xia Ke; Xiao-Ling Tang; Ren-Chao Zheng; Yu-Guo Zheng (World Journal of Microbiology and Biotechnology, 2018)

Aidingibacillus halophilus gen. nov., sp. nov., a novel member of the family Bacillaceae - Yun Wang; Wei-Xun Chunyu; Gang-Qiang Jiang; Ling Huang; Bo Zhang; Yang Ji; Zhang-Gui Ding; Min Yin; Shu-Kun Tang (Antonie van Leeuwenhoek, 2018)

Westerly wind bursts simulated in CAM4 and CCSM4 - Tao Lian; Youmin Tang; Lei Zhou; Siraj Ul Islam; Chan Zhang; Xiaojing Li; Zheng Ling (Climate Dynamics, 2018)

Effects of food and grapefruit juice on single-dose pharmacokinetics of blonanserin in healthy Chinese subjects - De-Wei Shang; Zhan-Zhang Wang; Hai-Tang Hu; Yue-Feng Zhang; Xiao-Jia Ni; Hao-Yang Lu; Ming Zhang; Jin-Qing Hu; Chang Qiu; Huan Peng; Ling-Fang Shen; Yu-Guan Wen (European Journal of Clinical Pharmacology, 2018)

Protective Effect of Selenoprotein X Against Oxidative Stress-Induced Cell Apoptosis in Human Hepatocyte (LO2) Cells via the p38 Pathway - Jia-Yong Tang; Ai-Hua He; Gang Jia; Guang-Mang Liu; Xiao-Ling Chen; Jing-Yi Cai; Hai-Ying Shang; Jin-Qiu Liao; Hua Zhao (Biological Trace Element Research, 2018)

Three new isobenzofurans from the roots of Nicotiana Tabacum and their bioactivities - Pei He; Peisong Yang; Shiyun Tang; Ling Ye; Chunbo Liu; Qinpeng Shen; Dangyu Tang; Fengmei Zhang; Zhihua Liu; Yongkuan Chen; Shouzhuo Yao; Nengjun Xiang; et al. (Natural Product Research, 2017)

Periphyton growth reduces cadmium but enhances arsenic accumulation in rice (Oryza sativa) seedlings from contaminated soil - Gao Ling Shi; Hai Ying Lu; Jun Zhuo Liu; Lai Qing Lou; Xian Jin Tang; Yong Hong Wu; Hong Xiang Ma (Plant and Soil, 2017)

Enhanced dimethyl phthalate biodegradation by accelerating phthalic acid di-oxygenation - Yingxia Tang; Yongming Zhang; Ling Jiang; Chao Yang; Bruce E. Rittmann (Biodegradation, 2017)

Transcriptome profiles reveal cold acclimation and freezing tolerance of susceptible and tolerant hulless barley genotypes - Hongjun Yuan; Xingquan Zeng; Zhihao Ling; Zexiu Wei; Yulin Wang; Zhenhua Zhuang; Qijun Xu; Yawei Tang; Nyima Tashi (Acta Physiologiae Plantarum, 2017)

Fertility outcomes in infertile women with complex hyperplasia or complex atypical hyperplasia who received progestin therapy and in vitro fertilization - Miao Li; Jia-lun Song; Ying Zhao; She-ling Wu; Hong-bin Liu; Rong Tang; Lei Yan (Journal of Zhejiang University-SCIENCE B, 2017)

Erratum to: Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2017)

Olivibacter flavus sp. nov., a novel endophytic bacterium isolated from the root of Camellia sinensis - Lei Tian; Tong-Wei Guan; Ling-Ling Yang; Kai-Yang Lu; Bing-Bing Liu; Wei-Xun ChunYu; Min Yin; En-Yuan Li; Yang Ji; Xiao-Ping Zhang; Shu-Kun Tang (Archives of Microbiology, 2017)

Air pollution and hospital visits for acute upper and lower respiratory infections among children in Ningbo, China: A time-series analysis - Pei-wen Zheng; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2017)

Two-Stage Prediction on Effects of Mixtures Containing Phenolic Compounds and Heavy Metals on Vibrio qinghaiensis sp. Q67 - Ling-Yun Mo; Jie Liu; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Bulletin of Environmental Contamination and Toxicology, 2017)

Dynamic assessment of rainfall-induced shallow landslide hazard - Yang Tang; Kun-long Yin; Lei Liu; Ling Zhang; Xiao-lin Fu (Journal of Mountain Science, 2017)

Mantle source heterogeneity and magmatic evolution at Carlsberg Ridge (3.7°N): constrains from elemental and isotopic (Sr, Nd, Pb) data - Ling Chen; Limei Tang; Xing Yu; Yanhui Dong (Marine Geophysical Research, 2017)

Comprehensive Analysis of R2R3-MYB Genes During Adventitious Root Formation in Cuttings of Morus alba - Xiao Long Du; Xu Cao; Chao Rui Yin; Zhuang Tang; Wei Du; Yue Yuan Ban; Jia Ling Cheng (Journal of Plant Growth Regulation, 2017)

Involvement of the miR-462/731 cluster in hypoxia response in Megalobrama amblycephala - Cui-Hong Huang; Nan Chen; Chun-Xiao Huang; Bao Zhang; Meng Wu; Lei He; Hong Liu; Rong Tang; Wei-Min Wang; Huan-Ling Wang (Fish Physiology and Biochemistry, 2017)

Erratum to: Atmospheric Nitrogen Emission, Deposition, and Air Quality Impacts in China: an Overview - Xuejun Liu; Wen Xu; Lei Duan; Enzai Du; Yuepeng Pan; Xiankai Lu; Lin Zhang; Zhiyong Wu; Xuemei Wang; Ying Zhang; Jianlin Shen; Ling Song; et al. (Current Pollution Reports, 2017)

Atmospheric Nitrogen Emission, Deposition, and Air Quality Impacts in China: an Overview - Xuejun Liu; Wen Xu; Lei Duan; Enzai Du; Yuepeng Pan; Xiankai Lu; Lin Zhang; Zhiyong Wu; Xuemei Wang; Ying Zhang; Jianlin Shen; Ling Song; et al. (Current Pollution Reports, 2017)

Simultaneous di-oxygenation and denitrification in an internal circulation baffled bioreactor - Ling Jiang; Yingxia Tang; Weihua Sun; Na Yi; Yongming Zhang; Hanchang Shi; Bruce E. Rittmann (Biodegradation, 2017)

Promotion of artemisinin content in Artemisia annua by overexpression of multiple artemisinin biosynthetic pathway genes - Pu Shi; Xueqing Fu; Meng Liu; Qian Shen; Weimin Jiang; Ling Li; Xiaofen Sun; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Monazite RW-1: a homogenous natural reference material for SIMS U–Pb and Th–Pb isotopic analysis - Xiao-Xiao Ling; Magdalena H. Huyskens; Qiu-Li Li; Qin-Zhu Yin; Ronald Werner; Yu Liu; Guo-Qiang Tang; Ya-Nan Yang; Xian-Hua Li (Mineralogy and Petrology, 2017)

Effects of an iron-silicon material, a synthetic zeolite and an alkaline clay on vegetable uptake of As and Cd from a polluted agricultural soil and proposed remediation mechanisms - Aijun Yao; Yani Wang; Xiaodan Ling; Zhe Chen; Yetao Tang; Hao Qiu; Rongrong Ying; Rongliang Qiu (Environmental Geochemistry and Health, 2017)

Effect of nitrogen additions on root morphology and chemistry in a subtropical bamboo forest - Guan-tao Chen; Li-hua Tu; Yong Peng; Hong-ling Hu; Ting-xing Hu; Zhen-feng Xu; Li Liu; Yi Tang (Plant and Soil, 2017)

Lentiviral Vector-Induced Overexpression of RGMa in the Hippocampus Suppresses Seizures and Mossy Fiber Sprouting - Ling Chen; Baobing Gao; Min Fang; Jie Li; Xiujuan Mi; Xin Xu; Wei Wang; Juan Gu; Bo Tang; Yanke Zhang; Zhihua Wang; Ao Zhan; et al. (Molecular Neurobiology, 2017)

Pollination Syndromes of Chinese Gesneriaceae: a Comparative Study between Hainan Island and Neighboring Regions - Shao-Jun Ling; Qian-Wan Meng; Liang Tang; Ming-Xun Ren (The Botanical Review, 2017)

Differentiating Patients with Parkinson’s Disease from Normal Controls Using Gray Matter in the Cerebellum - Ling-Li Zeng; Liang Xie; Hui Shen; Zhiguo Luo; Peng Fang; Yanan Hou; Beisha Tang; Tao Wu; Dewen Hu (The Cerebellum, 2017)

Permian–Triassic boundary microbialites (PTBMs) in southwest China: implications for paleoenvironment reconstruction - Hao Tang; Stephen Kershaw; Hong Liu; Xiucheng Tan; Fei Li; Guang Hu; Cheng Huang; Lichao Wang; Chengbo Lian; Ling Li; Xuefei Yang (Facies, 2017)

The boundary conditions for simulations of a shake-table experiment on the seismic response of 3D slope - Liang Tang; Shengyi Cong; Xianzhang Ling; Nengpan Ju (Earthquake Engineering and Engineering Vibration, 2017)

Di-2-ethylhexyl phthalate induced oxidative damage involving FasL-associated apoptotic pathway in mouse spermatogenic GC-2spd cells - Xiao Tang; Kun Tong; Lishan Zhu; Guoqing Fu; Wei Chang; Ting Zhou; Zhibing Zhang; Ling Tong; Ling Zhang; Yuqin Shi (Molecular & Cellular Toxicology, 2016)

Predicting the Binding Affinity of ERβ Ligands Based on a Novel Variable Selection Method - Hong-Yan Liu; Fei Zhang; Li-Tang Qin; Zhong-Sheng Yi; Xiu-Li Wang; Ling-Yun Mo (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Genetic mapping of QTL for the sizes of eight consecutive leaves below the tassel in maize (Zea mays L.) - Cong Yang; Dengguo Tang; Jingtao Qu; Ling Zhang; Lei Zhang; Zhengjie Chen; Jian Liu (Theoretical and Applied Genetics, 2016)

Geochemical fingerprints and pebbles zircon geochronology: Implications for the provenance and tectonic setting of Lower Cretaceous sediments in the Zhucheng Basin (Jiaodong peninsula, North China) - JIN-LONG NI; JUN-LAI LIU; XIAO-LING TANG; XIAO-XIAO SHI; HONG ZHANG; SHUAI HAN (Journal of Earth System Science, 2016)

Comparison of the immunogenicity of two inactivated recombinant rabies viruses overexpressing the glycoprotein - Muhammad Tariq Navid; Yingying Li; Ming Zhou; Min Cui; Zhen F. Fu; Lijun Tang; Ling Zhao (Archives of Virology, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Down-regulation of microRNA-126-5p contributes to overexpression of VEGFA in lipopolysaccharide-induced acute lung injury - Rurong Tang; Ling Pei; Tao Bai; Junke Wang (Biotechnology Letters, 2016)

Elevated Serum Levels of Neopterin at Admission Predicts Depression After Acute Ischemic Stroke: a 6-Month Follow-Up Study - Chao-Zhi Tang; Yu-Ling Zhang; Wen-Sheng Wang; Wei-Guo Li; Ji-Peng Shi (Molecular Neurobiology, 2016)

STAT3 signal that mediates the neural plasticity is involved in willed-movement training in focal ischemic rats - Qing-ping Tang; Qin Shen; Li-xiang Wu; Xiang-ling Feng; Hui Liu; Bei Wu; Xiao-song Huang; Gai-qing Wang; Zhong-hao Li; Zun-jing Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Differential transcriptome analysis of leaves of tea plant (Camellia sinensis) provides comprehensive insights into the defense responses to Ectropis oblique attack using RNA-Seq - Ya-Nan Wang; Lei Tang; Yan Hou; Ping Wang; Hua Yang; Chao-Ling Wei (Functional & Integrative Genomics, 2016)

Oceanobacillus endoradicis sp. nov., an endophytic bacterial species isolated from the root of Paris polyphylla Smith var. yunnanensis - Ling-Ling Yang; Shu-Kun Tang; Xiao Chu; Zhao Jiang; Li-Hua Xu; Xiao-Yang Zhi (Antonie van Leeuwenhoek, 2016)

Full-length genomic characterization and molecular evolution of canine parvovirus in China - Ling Zhou; Qinghai Tang; Lijun Shi; Miaomiao Kong; Lin Liang; Qianqian Mao; Bin Bu; Lunguang Yao; Kai Zhao; Shangjin Cui; Élcio Leal (Virus Genes, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Serum Levels of High-sensitivity C-Reactive Protein at Admission Are More Strongly Associated with Poststroke Depression in Acute Ischemic Stroke than Homocysteine Levels - Chao-Zhi Tang; Yu-Ling Zhang; Wen-Sheng Wang; Wei-Guo Li; Ji-Peng Shi (Molecular Neurobiology, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

De novo transcriptome sequencing of Acer palmatum and comprehensive analysis of differentially expressed genes under salt stress in two contrasting genotypes - Liping Rong; Qianzhong Li; Shushun Li; Ling Tang; Jing Wen (Molecular Genetics and Genomics, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Synthesis and antifungal activity evaluation of new heterocycle containing amide derivatives - Xuesong Wang; Sumei Gao; Jian Yang; Yang Gao; Ling Wang; Xiaorong Tang (Natural Product Research, 2016)

Establishment and characterization of feeder cell-dependent bovine fetal liver cell lines - Neil C. Talbot; Ling Wang; Wesley M. Garrett; Thomas J. Caperna; Young Tang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Microbial degradation of decabromodiphenyl ether (DBDE) in soil slurry microcosms - Hsi-Ling Chou; Mei-Yin Hwa; Yao-Chuan Lee; Yu-Jie Chang; Yi-Tang Chang (Environmental Science and Pollution Research, 2016)

Experimental and numerical investigation on the dynamic response of pile group in liquefying ground - Liang Tang; Xiaoyu Zhang; Xianzhang Ling; Hui Li; Nengpan Ju (Earthquake Engineering and Engineering Vibration, 2016)

Erratum to: Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2016)

Neuroligin-1 Knockdown Suppresses Seizure Activity by Regulating Neuronal Hyperexcitability - Min Fang; Jin-Lai Wei; Bo Tang; Jing Liu; Ling Chen; Zhao-Hua Tang; Jing Luo; Guo-Jun Chen; Xue-Feng Wang (Molecular Neurobiology, 2016)

New Perspectives on Dietary-derived Treatments and Food Safety—Antinomy in a New Era - Si-Yuan Pan; Si-Hua Gao; Rui-Chao Lin; Shu-Feng Zhou; Hong-Guan Dong; Min-Ke Tang; Zhi-Ling Yu; Kam-Ming Ko (Critical Reviews in Food Science and Nutrition, 2015)

Erratum to: Mining for low-nitrogen tolerance genes by integrating meta-analysis and large-scale gene expression data from maize - Bowen Luo; Haitao Tang; Hailan Liu; Shunzong Su; Suzhi Zhang; Ling Wu; Dan Liu; Shibin Gao (Euphytica, 2015)

Mining for low-nitrogen tolerance genes by integrating meta-analysis and large-scale gene expression data from maize - Bowen Luo; Haitao Tang; Hailan Liu; Su Shunzong; Suzhi Zhang; Ling Wu; Dan Liu; Shibin Gao (Euphytica, 2015)

Major and trace elements of abyssal peridotites: evidence for melt refertilization beneath the ultraslow-spreading Southwest Indian Ridge (53° E segment) - Ling Chen; Feng-You Chu; Ji-Hao Zhu; Yan-Hui Dong; Xing Yu; Zheng-Gang Li; Li-Mei Tang (International Geology Review, 2015)

Speleothem annual layers revealed by seasonal SIMS δ 18O measurements - YuHui Liu; GuoQiang Tang; XiaoXiao Ling; ChaoYong Hu; XianHua Li (Science China Earth Sciences, 2015)

Endogenous hydrogen sulfide regulated by calcium is involved in thermotolerance in tobacco Nicotiana tabacum L. suspension cell cultures - Zhong-Guang Li; Wei-Biao Long; Shi-Zhong Yang; Yang-Cai Wang; Ji-Hong Tang; Ling Wen; Bing-Yu Zhu; Xiong Min (Acta Physiologiae Plantarum, 2015)

Fluorofenidone protects against renal fibrosis by inhibiting STAT3 tyrosine phosphorylation - Juan Tang; Chun-yan Liu; Miao-miao Lu; Jing Zhang; Wen-juan Mei; Wen-jun Yang; Yan-yun Xie; Ling Huang; Zhang-zhe Peng; Qiong-jing Yuan; Ji-shi Liu; Gao-yun Hu; et al. (Molecular and Cellular Biochemistry, 2015)

Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2015)

Linear regression model for predicting interactive mixture toxicity of pesticide and ionic liquid - Li-Tang Qin; Jie Wu; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Genetic map and QTL controlling fiber quality traits in upland cotton (Gossypium hirsutum L.) - Zhaoyun Tan; Xiaomei Fang; Shiyi Tang; Jian Zhang; Dajun Liu; Zhonghua Teng; Ling Li; Huijuan Ni; Fengmin Zheng; Dexin Liu; Tingfu Zhang; Andrew H. Paterson; et al. (Euphytica, 2015)

Direct and indirect effects of nitrogen additions on fine root decomposition in a subtropical bamboo forest - Li-hua Tu; Yong Peng; Gang Chen; Hong-ling Hu; Yin-long Xiao; Ting-xing Hu; Li Liu; Yi Tang (Plant and Soil, 2015)

Analysis of Cancer Marker in Tissues with Hadamard Transform Fluorescence Spectral Microscopic Imaging - Hao Xu; Chuang Chen; Yue He; Hong-Wu Tang; Zhi-Ling Zhang; Yan Li; Dai-Wen Pang (Journal of Fluorescence, 2015)

The daily fluorine and arsenic intake for residents with different dietaries and fluorosis risk in coal-burning fluorosis area, Yunnan, Southwest China - Ling Li; Kun-li Luo; Yue-gang Tang; Yong-lin Liu (Environmental Science and Pollution Research, 2015)

Stress signaling in response to polycyclic aromatic hydrocarbon exposure in Arabidopsis thaliana involves a nucleoside diphosphate kinase, NDPK-3 - Hong Liu; David Weisman; Ling Tang; Long Tan; Wen-ke Zhang; Zong-hua Wang; Yan-he Huang; Wen-xiong Lin; Xuan-ming Liu; Adán Colón-Carmona (Planta, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Differences between the platform-margin shoal reservoirs and the platform-interior shoal reservoirs of the Middle Triassic Leikoupo Formation, Sichuan Basin, China - Xiong Ding; Xiucheng Tan; Ling Li; Liang Huang; Bing Luo; Qingsong Tang; Hualing Ma (Carbonates and Evaporites, 2014)

Characterization of the biological properties and complete genome sequence analysis of a cattle-derived rabies virus isolate from the Guangxi province of southern China - Hai-Bo Tang; Zhuan-Ling Lu; Yi-Zhi Zhong; Xiao-Xia He; Tao-Zhen Zhong; Yan Pan; Xian-Kai Wei; Yang Luo; Su-Huan Liao; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2014)

Genetic relationships among buckwheat (Fagopyrum) species from southwest China based on chloroplast and nuclear SSR markers - ZIZHONG TANG; LING HUANG; JUNBO GOU; HUI CHEN; XUEYI HAN (Journal of Genetics, 2014)

Response of a pile group behind quay wall to liquefaction-induced lateral spreading: a shake-table investigation - Liang Tang; Xiaoyu Zhang; Xianzhang Ling; Lei Su; Chunhui Liu (Earthquake Engineering and Engineering Vibration, 2014)

Transcription of the Human Sodium Channel SCN1A Gene Is Repressed by a Scaffolding Protein RACK1 - Zhao-Fei Dong; Ling-Jia Tang; Guang-Fei Deng; Tao Zeng; Shu-Jing Liu; Rui-Ping Wan; Ting Liu; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2014)

Down-regulating annexin gene GhAnn2 inhibits cotton fiber elongation and decreases Ca2+ influx at the cell apex - Wenxin Tang; Yonghui He; Lili Tu; Maojun Wang; Yang Li; Yong-Ling Ruan; Xianlong Zhang (Plant Molecular Biology, 2014)

Functional analyses of a putative plasma membrane Na+/H+ antiporter gene isolated from salt tolerant Helianthus tuberosus - Qing Li; Zhong Tang; Yibing Hu; Ling Yu; Zhaopu Liu; Guohua Xu (Molecular Biology Reports, 2014)

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Berberine regulates the expression of E-prostanoid receptors in diabetic rats with nephropathy - Li Qin Tang; Sheng Liu; Shan Tang Zhang; Ling Na Zhu; Feng Ling Wang (Molecular Biology Reports, 2014)

Characterization of the Promoter of Artemisia annua Amorpha-4,11-diene Synthase (ADS) Gene Using Homologous and Heterologous Expression as well as Deletion Analysis - Mengmeng Zhu; Fangyuan Zhang; Zongyou Lv; Qian Shen; Ling Zhang; Xu Lu; Weimin Jiang; Xueqing Fu; Tingxiang Yan; Lingxian Chen; Guofeng Wang; Kexuan Tang (Plant Molecular Biology Reporter, 2014)

Breast Cancer Resistance Protein-Mediated Efflux of Luteolin Glucuronides in HeLa Cells Overexpressing UDP-Glucuronosyltransferase 1A9 - Lan Tang; Ye Li; Wei-Ying Chen; Shan Zeng; Ling-Na Dong; Xiao-Juan Peng; Wen Jiang; Ming Hu; Zhong-Qiu Liu (Pharmaceutical Research, 2014)

Increased expression of S100A6 promotes cell proliferation and migration in human hepatocellular carcinoma - Ziqiang Li; Mei Tang; Bo Ling; Shiying Liu; Yu Zheng; Chunlai Nie; Zhu Yuan; Liangxue Zhou; Gang Guo; Aiping Tong; Yuquan Wei (Journal of Molecular Medicine, 2014)

Residue Val237 is critical for the enantioselectivity of Penicillium expansum lipase - Lianghua Tang; Min Su; Liying Chi; Junling Zhang; Huihui Zhang; Ling Zhu (Biotechnology Letters, 2014)

Numerical simulations of shake-table experiment for dynamic soil-pile-structure interaction in liquefiable soils - Liang Tang; Baydaa Hussain Maula; Xianzhang Ling; Lei Su (Earthquake Engineering and Engineering Vibration, 2014)

Molecular Cloning and Characterization of a Trichome-Specific Promoter of Artemisinic Aldehyde Δ11(13) Reductase (DBR2) in Artemisia annua - Weimin Jiang; Xu Lu; Bo Qiu; Fangyuan Zhang; Qian Shen; Zongyou Lv; Xueqing Fu; Tingxiang Yan; Erdi Gao; Mengmeng Zhu; Lingxian Chen; Ling Zhang; et al. (Plant Molecular Biology Reporter, 2014)

The TNF-alpha -308G/A polymorphism is associated with type 2 diabetes mellitus: an updated meta-analysis - Yuliang Zhao; Zheng Li; Ling Zhang; Yonggang Zhang; Yingying Yang; Yi Tang; Ping Fu (Molecular Biology Reports, 2014)

Sorption characteristics of cyromazine and its metabolite melamine in typical agricultural soils of China - Hai-Yan Wang; Hui Wang; Ling-Li Tang; Yuan-Hua Dong; Ling Zhao; Gurpal Toor (Environmental Science and Pollution Research, 2014)

GSK-3β Polymorphism Discriminates Bipolar Disorder and Schizophrenia: A Systematic Meta-Analysis - Hui Tang; Na Shen; Huijuan Jin; Dan Liu; Xiaoping Miao; Ling-Qiang Zhu (Molecular Neurobiology, 2013)

Overweight and Obesity Associated With Increased Total Serum Calcium Level: Comparison of Cross-sectional Data in the Health Screening for Teaching Faculty - Xiao-hua Ren; Ying-shui Yao; Lian-ping He; Yue-long Jin; Wei-wei Chang; Jie Li; Yan Chen; Xiu-li Song; Hui Tang; Ling-ling Ding; Dao-xia Guo; Chao-ping Li (Biological Trace Element Research, 2013)

The roles of two transcription factors, ABI4 and CBFA, in ABA and plastid signalling and stress responses - Zhong-Wei Zhang; Ling-Yang Feng; Jian Cheng; He Tang; Fei Xu; Feng Zhu; Zhong-Yi Zhao; Ming Yuan; Yang-Er Chen; Jian-Hui Wang; Shu Yuan; Hong-Hui Lin (Plant Molecular Biology, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Improvement of enamel bond strengths for conventional and resin-modified glass ionomers: acid-etching vs. conditioning - Ling Zhang; Tian Tang; Zhen-liang Zhang; Bing Liang; Xiao-miao Wang; Bai-ping Fu (Journal of Zhejiang University-SCIENCE B, 2013)

In vivo study on the effects of curcumin on the expression profiles of anti-tumour genes (VEGF, CyclinD1 and CDK4) in liver of rats injected with DEN - Chu Zhu Huang; Wei Zhe Huang; Ge Zhang; Dan Ling Tang (Molecular Biology Reports, 2013)

Antiangiogenic therapy promoted metastasis of hepatocellular carcinoma by suppressing host-derived interleukin-12b in mouse models - Xiao-Dong Zhu; Hui-Chuan Sun; Hua-Xiang Xu; Ling-Qun Kong; Zong-Tao Chai; Lu Lu; Ju-Bo Zhang; Dong-Mei Gao; Wen-Quan Wang; Wei Zhang; Peng-Yuan Zhuang; Wei-Zhong Wu; et al. (Angiogenesis, 2013)

Comprehensive identification of high-frequency and co-occurring Mafa-DPA1, Mafa-DQA1, Mafa-DRA, and Mafa-DOA alleles in Vietnamese cynomolgus macaques - Ruirui Xiang; Huiling Zhang; Qing Deng; Rui Yue; Haite Tang; Yanqi Zhang; Fei Ling; Min Zhuo; Hongli Du; Shiqian Xu; Qiang Xu; Xiaoning Wang (Immunogenetics, 2013)

Rothia marina sp. nov., isolated from an intertidal sediment of the South China Sea - Zhu-Xiang Liu; Ling-Ling Yang; Ying Huang; Hu Zhao; He Liu; Shu-Kun Tang; Wen-Jun Li; Yi-Guang Chen (Antonie van Leeuwenhoek, 2013)

Functional divergence and catalytic properties of dehydroascorbate reductase family proteins from Populus tomentosa - Zhen-Xin Tang; Hai-Ling Yang (Molecular Biology Reports, 2013)

The stacked over-expression of FPS, CYP71AV1 and CPR genes leads to the increase of artemisinin level in Artemisia annua L. - Yunfei Chen; Qian Shen; Yueyue Wang; Tao Wang; Shaoyan Wu; Ling Zhang; Xu Lu; Fangyuan Zhang; Weimin Jiang; Bo Qiu; Erdi Gao; Xiaofen Sun; et al. (Plant Biotechnology Reports, 2013)

Re-Examination of the Genotoxic Activity of Water Taken From the Songhua River in P. R. China - Jia Yu; Hong-Wei Dong; Li-Tian Shi; Hui-Ling Jiang; Jian-Wen Yu; Qian-Wen Zhao; Shi-Chun Cai; Dan Han; Xuan-Yue Tang; Jia-Ren Liu (Archives of Environmental Contamination and Toxicology, 2013)

Berberine ameliorates renal injury by regulating G proteins-AC- cAMP signaling in diabetic rats with nephropathy - Li Qin Tang; Feng Ling Wang; Ling Na Zhu; Fei Lv; Sheng Liu; Shan Tang Zhang (Molecular Biology Reports, 2013)

Role of Paraoxonase-1 in the Protection of Hydrogen Sulfide-Donating Sildenafil (ACS6) Against Homocysteine-Induced Neurotoxicity - Xiao-Qing Tang; Rong-Qian Chen; Ling Dong; Yan-Kai Ren; Piero Del Soldato; Anna Sparatore; Duan-Fang Liao (Journal of Molecular Neuroscience, 2013)

Screening Chinese soybean genotypes for Agrobacterium-mediated genetic transformation suitability - Zhang-yue Song; Jing-luan Tian; Wei-zhe Fu; Lin Li; Ling-hong Lu; Lian Zhou; Zhi-hui Shan; Gui-xiang Tang; Hui-xia Shou (Journal of Zhejiang University-SCIENCE B, 2013)

Lyssavirus surveillance in bats of southern China’s Guangxi Province - Zhuan-Ling Lu; Wen Wang; Wei-Li Yin; Hai-Bo Tang; Yan Pan; Xiang Liang; Qi Liu; Yi Xiong; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2013)

Repellent and attractive effects of herbs on insects in pear orchards intercropped with aromatic plants - Guang Bo Tang; Bei Zhou Song; Ling Ling Zhao; Xu Sheng Sang; Hui Hua Wan; Jie Zhang; Yun Cong Yao (Agroforestry Systems, 2013)

Effects of glacier melting on socioeconomic development in the Manas River basin, China - Xiang-ling Tang; Li-Ping Xu; Zheng-Yong Zhang; Xin Lv (Natural Hazards, 2013)

Renoprotective effects of berberine and its possible molecular mechanisms in combination of high-fat diet and low-dose streptozotocin-induced diabetic rats - Feng Ling Wang; Li Qin Tang; Feng Yang; Ling Na Zhu; Ming Cai; Wei Wei (Molecular Biology Reports, 2013)

Meta-analysis of the Association Between DCDC2 Polymorphisms and Risk of Dyslexia - Rong Zhong; Beifang Yang; Hui Tang; Li Zou; Ranran Song; Ling-Qiang Zhu; Xiaoping Miao (Molecular Neurobiology, 2013)

Melatonin Attenuates Scopolamine-Induced Memory/Synaptic Disorder by Rescuing EPACs/miR-124/Egr1 Pathway - Xiong Wang; Zhi-Hao Wang; Yuan-Yuan Wu; Hui Tang; Lu Tan; Xiang Wang; Xin-Ya Gao; Yan-Si Xiong; Dan Liu; Jian-Zhi Wang; Ling-Qiang Zhu (Molecular Neurobiology, 2013)

Substitution of Val72 residue alters the enantioselectivity and activity of Penicillium expansum lipase - Lianghua Tang; Min Su; Ling Zhu; Liying Chi; Junling Zhang; Qiong Zhou (World Journal of Microbiology and Biotechnology, 2013)

Isolation and characterization of 16 polymorphic microsatellite markers for the mudskipper (Boleophthalmus pectinirostris) - Cong-Tao Wang; Zhi-Zhi Liu; Ling-Bo Ma; Jia-Mei Zhang; Zhen Zeng; An-Yuan He; Shou-Jie Tang; Wen-Qiao Tang (Conservation Genetics Resources, 2012)

Paenibacillus thermophilus sp. nov., a novel bacterium isolated from a sediment of hot spring in Fujian province, China - Yu Zhou; Sheng Gao; Da-Qiao Wei; Ling-Ling Yang; Xing Huang; Jie He; Yun-Jiao Zhang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Expression characterization of genes for CMS-C in maize - Ling Huang; Jie Xiang; Jiazhou Liu; Tingzhao Rong; Jing Wang; Yanli Lu; Qilin Tang; Wen Wen; Moju Cao (Protoplasma, 2012)

Characterization of a novel ERF transcription factor in Artemisia annua and its induction kinetics after hormones and stress treatments - Xu Lu; Weimin Jiang; Ling Zhang; Fangyuan Zhang; Qian Shen; Tao Wang; Yunfei Chen; Shaoyan Wu; Zongyou Lv; Erdi Gao; Bo Qiu; Kexuan Tang (Molecular Biology Reports, 2012)

Toxins from a symbiotic fungus, Leptographium qinlingensis associated with Dendroctonus armandi and their in vitro toxicities to Pinus armandi seedlings - Xiao-Jun Li; Jin-Ming Gao; Hui Chen; An-Ling Zhang; Ming Tang (European Journal of Plant Pathology, 2012)

MTHFR C677T and A1298C polymorphisms and cervical carcinoma susceptibility: meta-analyses based on 4421 individuals - Wen-Lei Zhuo; Liang Zhang; Jun-Jun Ling; Yi Zhu; Zheng-Tang Chen (Molecular Biology Reports, 2012)

Identification of Putative Artemisia annua ABCG Transporter Unigenes Related to Artemisinin Yield Following Expression Analysis in Different Plant Tissues and in Response to Methyl Jasmonate and Abscisic Acid Treatments - Ling Zhang; Xu Lu; Qian Shen; Yunfei Chen; Tao Wang; Fangyuan Zhang; Shaoyan Wu; Weimin Jiang; Pin Liu; Lida Zhang; Yueyue Wang; Kexuan Tang (Plant Molecular Biology Reporter, 2012)

Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2012)

The connection between GRKs and various signaling pathways involved in diabetic nephropathy - Feng-Ling Wang; Li-Qin Tang; Wei Wei (Molecular Biology Reports, 2012)

Analysis of Arabidopsis genes encoding putative class III lipases - Wei Li; Hua Ling; Fei Zhang; Hongyan Yao; Xiaofen Sun; Kexuan Tang (Journal of Plant Biochemistry and Biotechnology, 2012)

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

Accumulated deformation characteristics of silty soil under the subway loading in Shanghai - Chun-Ling Yan; Yi-Qun Tang; Yuan-Dong Wang; Xing-Wei Ren (Natural Hazards, 2012)

A Role of the Mammalian Target of Rapamycin (mTOR) in Glutamate-Induced Down-regulation of Tuberous Sclerosis Complex Proteins 2 (TSC2) - Wenjuan Ru; Yanxi Peng; Ling Zhong; Shao-Jun Tang (Journal of Molecular Neuroscience, 2012)

Thermoactinospora rubra gen. nov., sp. nov., a thermophilic actinomycete isolated from Tengchong, Yunnan province, south–west China - En-Min Zhou; Shu-Kun Tang; Carsten Sjøholm; Zhao-Qi Song; Tian-Tian Yu; Ling-Ling Yang; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Streptomyces manipurensis sp. nov., a novel actinomycete isolated from a limestone deposit site in Manipur, India - Salam Nimaichand; Wen-Yong Zhu; Ling-Ling Yang; Hong Ming; Guo-Xing Nie; Shu-Kun Tang; Debananda S. Ningthoujam; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Association between ATM 5557G>A polymorphism and breast cancer risk: a meta-analysis - Chen Mao; Vincent C. H. Chung; Ben-Fu He; Rong-Cheng Luo; Jin-Ling Tang (Molecular Biology Reports, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Effects of applied urea and straw on various nitrogen fractions in two Chinese paddy soils with differing clay mineralogy - Shao-Jun Qiu; Pei-Qin Peng; Ling Li; Ping He; Qiang Liu; Jin-Shui Wu; Peter Christie; Xiao-Tang Ju (Biology and Fertility of Soils, 2012)

Clinical characteristics of critical patients with pandemic influenza A (H1N1) virus infection in Chengdu, China - Li-hui Deng; Yi-lan Zeng; Ping Feng; Ya-ling Liu; Li-chun Wang; Yun Bai; Hong Tang (Journal of Zhejiang University-SCIENCE B, 2012)

Channelized fluids in subducted continental crust: constraints from δD–δ 18 O of quartz and fluid inclusions in quartz veins from the Chinese Continental Scientific Drilling Project - Xiaoming Sun; Li Xu; Weidong Sun; Wei Zhai; Yeheng Liang; Qian Tang; Jinlong Liang; Zeming Zhang; Kun Shen; Fangyue Wang; Mingxing Ling; Robert E. Zartman (International Geology Review, 2011)

Synthesis and evaluation of κ-opioid receptor agonistic activity and antinociceptive effect of novel morphine analogues, 7α-phenyl-6α,14α-endo-etheno-tetrahydrothebaine with substituted o-, m- and p-amino group - Hong Qi; Wei Li; Yu Qiu; Yong-yao Cui; Jian Ma; Xiao-ling Gao; Yi-bin Zeng; Jie Yang; Yun Tang; Xing-hai Wang; Wei Sheng; Qiong Xie; et al. (Medicinal Chemistry Research, 2011)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Seismic wavefront evolution of multiply reflected, transmitted, and converted phases in 2D/3D triangular cell model - Chao-ying Bai; Xiao-ling Li; Xiao-ping Tang (Journal of Seismology, 2011)

Two new 3-oxo-α-ionol glucosides from Urtica laetevirens Maxim. - Yuan Zhou; Bao-Min Feng; Li-Ying Shi; Hui-Guo Wang; Ling Tang; Yong-Qi Wang (Natural Product Research, 2011)

Lactoferrin: an iron-binding antimicrobial protein against Escherichia coli infection - Chih-Ching Yen; Chih-Jie Shen; Wu-Huei Hsu; Yi-Hsin Chang; Hsin-Tang Lin; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2011)

Transgenic Brassica napus L. lines carrying a two gene construct demonstrate enhanced resistance against Plutella xylostella and Sclerotinia sclerotiorum - Hongbo Liu; Xiang Guo; Muhammad S. Naeem; Dan Liu; Ling Xu; Wenfang Zhang; Guixiang Tang; Weijun Zhou (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Identification and characterization of Sox genes in the silkworm, Bombyx mori - Ling Wei; Daojun Cheng; Dong Li; Meng Meng; Lina Peng; Lin Tang; Minhui Pan; Zhonghuai Xiang; Qingyou Xia; Cheng Lu (Molecular Biology Reports, 2011)

Analysis of 19-nortestosterone residue in animal tissues by ion-trap gas chromatography-tandem mass spectrometry - Jin-qing Jiang; Lei Zhang; Guang-ling Li; Hai-tang Zhang; Xue-feng Yang; Jun-wei Liu; Ren-feng Li; Zi-liang Wang; Jian-hua Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Bioavailability Study of Berberine and the Enhancing Effects of TPGS on Intestinal Absorption in Rats - Wei Chen; Yu-Qiang Miao; Dong-Jiao Fan; Shen-Shen Yang; Xia Lin; Ling-Kuo Meng; Xing Tang (AAPS PharmSciTech, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Identification of QTLs for maize seed vigor at three stages of seed maturity using a RIL population - Liu Jing-bao; Fu Zhi-yuan; Xie Hui-ling; Hu Yan-min; Liu Zong-hua; Duan Liu-jing; Xu Shang-zhong; Tang Ji-hua (Euphytica, 2011)

Purification and identification of carvacrol from the root of Stellera chamaejasme and research on its insecticidal activity - Xiaorong Tang; Shaoling Chen; Ling Wang (Natural Product Research, 2011)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

Species and Gender Differences Affect the Metabolism of Emodin via Glucuronidation - Wei Liu; Lan Tang; Ling Ye; Zheng Cai; Bijun Xia; Jiajie Zhang; Ming Hu; Zhongqiu Liu (The AAPS Journal, 2010)

In vitro induction and identification of tetraploid plants of Paulownia tomentosa - Zhi-Qiang Tang; Dong-Ling Chen; Zhao-Jian Song; Yu-Chi He; De-Tian Cai (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

The Gab2 in signal transduction and its potential role in the pathogenesis of Alzheimer’s disease - Xiao-Ling Pan; Ru-Jing Ren; Gang Wang; Hui-Dong Tang; Sheng-Di Chen (Neuroscience Bulletin, 2010)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Molecular cloning and characterization of hatching enzyme-like gene in the silkworm, Bombyx mori - Fu-hao Lu; Shun-ming Tang; Xing-jia Shen; Na Wang; Qiao-ling Zhao; Guo-zheng Zhang; Xi-jie Guo (Molecular Biology Reports, 2010)

Shake table test of soil-pile groups-bridge structure interaction in liquefiable ground - Liang Tang; Xianzhang Ling; Pengju Xu; Xia Gao; Dongsheng Wang (Earthquake Engineering and Engineering Vibration, 2010)

QSPR model for bioconcentration factors of nonpolar organic compounds using molecular electronegativity distance vector descriptors - Li-Tang Qin; Shu-Shen Liu; Hai-Ling Liu (Molecular Diversity, 2010)

Evaluation of the geology-environmental capacity of buildings based on the ANFIS model of the floor area ratio - Zhen-Dong Cui; Yi-Qun Tang; Xue-Xin Yan; Chun-Ling Yan; Han-Mei Wang; Jian-Xiu Wang (Bulletin of Engineering Geology and the Environment, 2010)

Secretion of citrate from roots in response to aluminum and low phosphorus stresses in Stylosanthes - Xiao Feng Li; Fang Hua Zuo; Gui Zhi Ling; Yao Yan Li; Yong Xiong Yu; Pei Quan Yang; Xing Lian Tang (Plant and Soil, 2009)

Abscisic acid (ABA) treatment increases artemisinin content in Artemisia annua by enhancing the expression of genes in artemisinin biosynthetic pathway - Fuyuan Jing; Ling Zhang; Meiya Li; Yueli Tang; Yuliang Wang; Yueyue Wang; Quan Wang; Qifang Pan; Guofeng Wang; Kexuan Tang (Biologia, 2009)

Expression and purification of Zantedeschia aethiopica agglutinin in Escherichia coli - Ling Lin; Xue-Fen Liu; Ling-Chuan Hu; Yin Zhou; Xiao-Fen Sun; Ke-Xuan Tang (Molecular Biology Reports, 2009)

Lysosomal cysteine peptidase cathepsin L protects against cardiac hypertrophy through blocking AKT/GSK3β signaling - Qizhu Tang; Jun Cai; Difei Shen; Zhouyan Bian; Ling Yan; You-Xin Wang; Jie Lan; Guo-Qing Zhuang; Wen-Zhan Ma; Wei Wang (Journal of Molecular Medicine, 2009)

Genetic basis of nutritional content of stover in maize under low nitrogen conditions - Hui-ling Xie; Hong-qiang Ji; Zong-hua Liu; Guo-wei Tian; Chun-li Wang; Yan-min Hu; Ji-hua Tang (Euphytica, 2009)

Lignan and flavonoid glycosides from Urtica laetevirens Maxim. - Yuan Zhou; Wei Wang; Ling Tang; Xing-guo Yan; Li-ying Shi; Yong-qi Wang; Bao-min Feng (Journal of Natural Medicines, 2009)

Interethnic differences of PEPT2 (SLC15A2) polymorphism distribution and associations with cephalexin pharmacokinetics in healthy Asian subjects - Rui Liu; Audrey May Yi Tang; Yen Ling Tan; Lie Michael George Limenta; Edmund Jon Deoon Lee (European Journal of Clinical Pharmacology, 2009)

Molecular cloning and characterization of a mannose-binding lectin gene from Pinellia cordata - Ling Lin; Jie Lu; Hainian Zeng; Zhifeng Liang; Yin Zhou; Juan Lin; Xiaofen Sun; Kexuan Tang (Molecular Biology Reports, 2008)

Lack of variation of ATTCT pentanucleotide repeats at ATXN10 gene between clinically diagnosed ataxia patients and normal individuals originated from Chinese Han - Jun-Ling Wang; Hong Jiang; Shen Zhang; Qian Xu; Ya-Fang Zhou; Shu-Sheng Liao; Lu Shen; Xin-Xiang Yan; Huai-Xu Zhu; Qian Pan; Kun Xia; Bei-Sha Tang (Journal of Genetics, 2008)

Vanadium-enriched chickpea sprout ameliorated hyperglycemia and impaired memory in streptozotocin-induced diabetes rats - Xueqin Mao; Ling Zhang; Qing Xia; Zhaofeng Sun; Xiaomin Zhao; Hongxin Cai; Xiaoda Yang; Zuoli Xia; Yujing Tang (BioMetals, 2008)

Molecular cloning and characterization of 1-hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate reductase gene from Ginkgo biloba - Jie Lu; Weisheng Wu; Shuwen Cao; Henan Zhao; Hainian Zeng; Ling Lin; Xiaofen Sun; Kexuan Tang (Molecular Biology Reports, 2008)

Bone regeneration by BMP-2 enhanced adipose stem cells loading on alginate gel - Yunfeng Lin; Wei Tang; Ling Wu; Wei Jing; Xiaoyu Li; Yao Wu; Lei Liu; Jie Long; Weidong Tian (Histochemistry and Cell Biology, 2008)

Antinociceptive effect of CNS peroxynitrite scavenger in a mouse model of orofacial pain - Jin-Fei Yeo; Su-Fung Ling; Ning Tang; Wei-Yi Ong (Experimental Brain Research, 2008)

Ectopic adipogenesis of preconditioned adipose-derived stromal cells in an alginate system - Wei Jing; Yunfeng Lin; Ling Wu; Xiaoyu Li; Xin Nie; Lei Liu; Wei Tang; Xiaohui Zheng; Weidong Tian (Cell and Tissue Research, 2007)

Osteogenic differentiation of adipose derived stem cells promoted by overexpression of osterix - Ling Wu; Yao Wu; Yunfeng Lin; Wei Jing; Xin Nie; Ju Qiao; Lei Liu; Wei Tang; Weidong Tian (Molecular and Cellular Biochemistry, 2007)

Multiplex specific PCR for identification of the genera Actinopolyspora and Streptomonospora, two groups of strictly halophilic filamentous actinomycetes - Xiao-Yang Zhi; Ling-Ling Yang; Jin-Yuan Wu; Shu-Kun Tang; Wen-Jun Li (Extremophiles, 2007)

Inhibition of Cyanide-Insensitive Respiration in Klebsiella oxytoca SYSU-011 by 8-Hydroxyquinolone - Chih Ming Kao; You Cheng Hseu; Yen Ling Huang; Peturs Tang; Ssu Ching Chen (Current Microbiology, 2007)

Isolation and bioinformatics analyses of a COR413-like gene from Gossypium barbadense - Jin Wang; Kai-Jing Zuo; Jie Qin; Lida Zhang; Lan Su; Junrong Liu; Hua Ling; Jing-Ya Zhao; You-Fang Cao; Ke-Xuan Tang (Acta Physiologiae Plantarum, 2007)

Pluripotency potential of human adipose-derived stem cells marked with exogenous green fluorescent protein - Yunfeng Lin; Lei Liu; Zhiyong Li; Ju Qiao; Ling Wu; Wei Tang; Xiaohui Zheng; Xizhe Chen; Zhengbin Yan; Weidong Tian (Molecular and Cellular Biochemistry, 2006)

Improvement of Expression Level and Bioactivity of Soluble Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand (Apo2L/TRAIL) by a Novel Zinc ion Feeding Strategy - Ai-You Sun; Ya-Ling Shen; Ji-Cheng Yin; Hong Zhang; Ya-Nan Tang; Dong-Zhi Wei (Biotechnology Letters, 2006)

Overexpression ofGbERF confers alteration of ethylene-responsive gene expression and enhanced resistance toPseudomonas syringae in transgenic tobacco - Jie Qin; Kaijing Zuo; Jingya Zhao; Hua Ling; Youfang Cao; Chengxiang Qiu; Fupeng Li; Xiaofen Sun; Kexuan Tang (Journal of Biosciences, 2006)

Sowing seasons and drying methods during post-harvest influence the seed vigour of soybean (Glycine max (L.) Merr.) - Guixiang Tang; Wenjian Song; Ling Xu; Zonglai Jin; Kasirajan Subrahmaniyan; Weijun Zhou (Acta Physiologiae Plantarum, 2006)

Stable RNA Interference in Spodoptera frugiperda Cells by a DNA Vector-based Method - Chih-Chien Lin; John T. -A. Hsu; Kai-Ling Huang; Hung-Kuan Tang; Yiu-Kay Lai (Biotechnology Letters, 2006)

Phenotypic and functional characteristics of dendritic cells derived from human peripheral blood monocytes - Ling-ling Tang; Zhe Zhang; Jie-sheng Zheng; Ji-fang Sheng; Ke-zhou Liu (Journal of Zhejiang University-SCIENCE B, 2005)

Deaths from nasopharyngeal cancer among waiters and waitresses in Chinese restaurants - Ignatius TS Yu; Yuk-lan Chiu; Tze-wai Wong; Jin-ling Tang (International Archives of Occupational and Environmental Health, 2004)

Development of mariculture and its impacts in Chinese coastal waters - Yang Yu Feng; Li Chun Hou; Nie Xiang Ping; Tang Dan Ling; Chung Ik Kyo (Reviews in Fish Biology and Fisheries, 2004)

Studies on the Synthetic Methodology of Head to Tail Cyclization of Linear Peptides - Yun-hua Yep; Xing-ming Gao; Mian Liu; Yan-chun Tang; Gui-ling Tian (International Journal of Peptide Research and Therapeutics, 2003)

Characterization, physical location and expression of the genes encoding calcium/calmodulin-dependent protein kinases in maize ( Zea mays L.) - Ling Wang; Shuping Liang; Ying-Tang Lu (Planta, 2001)

Design of environmental decision support system and its application to water quality management - Zeng Fan-tang; Du Ling; Lin Kui; Shen Qian (Journal of Geographical Sciences, 2001)